Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; professional development

Keeping Kenya Learning: The importance of caregiver engagement in supporting learning beyond the classroom - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Since the Covid-19 pandemic began, parents, teachers, students and policymakers have been exploring how to support students to learn at home. The emphasis on education at home has made evident the need to better equip caregivers to support their children’s learning.  The Keep Kenya Learning (KKL) initiative is helping parents and caregivers build their capacity and confidence to support learning…
Keywords: _EdTechHub_Output

EdTech in Kenya: A Rapid Scan - Otieno, J.; Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private-sector partnerships, and the digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Kenya. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Kenya; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Kenya: Off-grid Solar Access Project for Underserved Counties - World Bank (2020)
Kenya: Off-grid Solar Access Project for Underserved Counties

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Piper, Benjamin; Jepkemei, Evelyn; Kwayumba, Dunston; Kibukho, Kennedy (FIRE: Forum for International Research in Education, 2015)
Kenya is investing in information and communication technology (ICT) to improve children's learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students. All three showed significant impacts in English and Kiswahili above the results of the control group. The impacts of the three interventions were not statistically significantly different from each other. Based on the findings, we recommend that Kenyan policy makers embed ICT interventions in a larger instructional reform, using ICT to support particular instructional improvement challenges. We also suggest that policy makers incorporate empirically derived cost-effectiveness analysis into investment decisions, to ensure that ICT provides value for money.
Keywords: African Languages; Control Groups; Cost Effectiveness; ERIC, Current Index to Journals in Education (CIJE); Educational Policy; Educational Practices; Elementary Secondary Education; English (Second Language); Experimental Groups; Foreign Countries; Handheld Devices; Intervention; Kenya; Literacy; Outcomes of Education; Program Effectiveness; Randomized Controlled Trials; Reading Achievement; Student Improvement; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096974; ___working_potential_duplicate; __finaldtb

Inclusive educational practices in Kenya: Evidencing practice of itinerant teachers who work with children with visual impairment in local mainstream schools - Lynch, Paul; McCall, Steve; Douglas, Graeme; McLinden, Mike; Mogesa, Bernard; Mwaura, Martha; Muga, John; Njoroge, Michael (International Journal of Educational Development, 2011)
This article presents a findings from an investigation of the work of 38 specialist itinerant teachers (ITs) supporting the educational inclusion of children with visual impairment in Kenya. The research was designed around a participatory action research framework involving in-country researchers and participants (teachers) working in collaboration with researchers in the United Kingdom. Following an introductory training workshop, participants kept research journals over a 2-month period in which they recorded details of their itinerant duties (including the processes and content of their visits). Findings provide information about local practices of ITs support for children with visual impairment in mainstream schools and raise broader questions about the barriers to learning and development facing children with disabilities in mainstream schools in Kenya and other developing countries.
Keywords: Inclusive education; Itinerant teachers; Kenya; Participatory action research; Visual impairment

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.

Genetics problem solving in high school testing in Kenya: Effects of metacognitive prompting during testing - Aurah, Catherine M; Cassady, Jerrell Craig; McConnell, Tom John (Electronic Journal for Research in Science and Mathematics Education, 2014)
This study investigated the effectiveness of using metacognitive prompts during testing for improving results in a Genetics Problem Solving Test (GPST). The study, a pre-test post-test, control group quasi-experimental design involving 2x2x2 analysis of covariance (ANCOVA) also investigated the moderating effects of gender and school type. A total of 2,138 high school students purposively selected from seventeen high schools in Western province, Kenya, participated in the study using three validated instruments; Biology Ability Test (BAT), Genetics Problem Solving Test (GPST), and Metacognitive Prompting Questionnaire (MPQ). Findings showed that metacognitive prompting (MP) had a significant effect on students’ genetics problem solving ability, F(1, 2137) = 10.909, p < 0.001. The findings also revealed gender differences, with girls outperforming boys on the genetics problem solving test. Furthermore, a significant interaction between metacognitive prompting and school type showed that students in provincial schools benefited from MPs more than students from district schools. This study established a foundation for instructional methods for biology teachers and recommendations are made for implementing metacognitive prompting in a problem-based learning environment in high schools and science teacher education programs in Kenya.
Keywords: ⛔ No DOI found

Improving Literacy Instruction in Kenya Through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial - Jukes, Matthew C. H.; Turner, Elizabeth L.; Dubeck, Margaret M.; Halliday, Katherine E.; Inyega, Hellen N.; Wolf, Sharon; Zuilkowski, Stephanie Simmons; Brooker, Simon J. (Journal of Research on Educational Effectiveness, 2017)
We evaluated a program to improve literacy instruction on the Kenyan coast using training workshops, semiscripted lesson plans, and weekly text-message support for teachers to understand its impact on students’ literacy outcomes and on the classroom practices leading to those outcomes. The evaluation ran from the beginning of Grade 1 to the end of Grade 2 in 51 government primary schools chosen at random, with 50 schools acting as controls. The intervention had an impact on classroom practices with effect sizes from 0.57 to 1.15. There was more instruction with written text and more focus on letters and sounds. There was a positive impact on three of four primary measures of children’s literacy after two years, with effect sizes up to 0.64, and school dropout reduced from 5.3% to 2.1%. This approach to literacy instruction is sustainable, and affordable and a similar approach has subsequently been adopted nationally in Kenya.
Keywords: Africa; Classroom Observation Techniques; Dropout Rate; ERIC, Current Index to Journals in Education (CIJE); Early Childhood Education; Effect Size; Elementary Education; Elementary School Students; Elementary School Teachers; Faculty Development; Foreign Countries; Grade 1; Grade 2; Handheld Devices; Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs; Intelligence Tests; Intervention; Interviews; Kenya; Literacy Education; Maximum Likelihood Statistics; Pretests Posttests; Primary Education; Program Effectiveness; Promising Interventions Are Great, but Are They Enough?; Questionnaires; RCT; Randomized Controlled Trials; Raven Progressive Matrices; Rural Schools; Statistical Analysis; Teacher Improvement; Teaching Methods; Telecommunications; What We Are Learning About Early Education in Sub-Saharan Africa; __:import:01; __:match:final; __:matched; __:study_id:2096051; ___working_potential_duplicate; __finaldtb; early grade reading; literacy instruction

Improving procedural and conceptual mathematics outcomes: evidence from a randomised controlled trial in Kenya - Piper, Benjamin; Ralaingita, Wendi; Akach, Linda; King, Simon (Journal of Development Effectiveness, 2016)
To improve learning outcomes, an intervention in Kenya called the Primary Math and Reading (PRIMR) Initiative provided pupil learning materials, teachers’ guides and modest teacher professional development in mathematics. This paper presents the causal impact of PRIMR’s mathematics intervention on pupil achievement indices for procedural and conceptual numeracy, using a diﬀerences-in-diﬀerences analytic strategy. The mathematics intervention produced modest, statistically signiﬁcant results: generally similar results for males and females, a larger impact in grade 2 than grade 1, a larger impact in nongovernment schools than public schools, and smaller outcomes in mathematics than for English or Kiswahili. These ﬁndings have relevant policy implications in Kenya given an impending national mathematics programme.
Keywords: Kenya; Numeracy; elementary school; instruction; international education; mathematics

The influence of infrastructure, training, content and communication on the success of NEPAD’S pilot e-Schools in Kenya - Nyagowa, Hesbon O; Ocholla, Dennis N; Mutula, Stephen M (Information Development, 2014)
This study was conducted to evaluate the contribution of four of the seven e-School dimensions to the success of the pilot phase of the New Partnership for Africa’s Development (NEPAD) e-School project in Kenya. The study employed survey research methodology. All six of the NEPAD e-Schools in Kenya were included and the teachers and students in those schools formed the study population. Of the 5,186 students and teachers, a representative sample of 1,508 was selected using probabilistic techniques. Data was collected using observations and a survey questionnaire. It was established that all six of the e-Schools had installed the basic computing facilities required for integrating information and communication technologies (ICT) in teaching and learning; all the e-Schools were observed to have the Very Small Aperture Terminal (VSAT) for Internet access in computer laboratories where a variable number of computers were installed. The ICT infrastructure provided modest communication capabilities. But while teachers received technical (ICT) training, they did not receive training on pedagogies for ICT integration in teaching and learning. We conducted hypothesis testing and confirmed that the four dimensions of E-School Success Model, investigated in the current study, positively contribute towards the success of the e-School. We therefore concluded that ICT infrastructure quality, content and communication quality, training effectiveness and use make considerable contributions to the success of the pilot phase of the NEPAD e-School project in Kenya. We recommend that stakeholders should continue investing in the NEPAD e-School project. Further studies on the impact of the other three dimensions of the e-Schools are recommended.
Keywords: Kenya; New Partnership for Africa’s Development; e-schools

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

2019 Kenya Population and Housing Census Volume IV: Distribution of Population by Socio-Economic Characteristics - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)

Kenya Population and Housing Census Results - Kenya National Bureau of Statistics (Kenya National Bureau of Statistics, 2019)
The total enumerated population was 47,564,296 Of which 23,548,056 were Males, 24,014,716 were Females and 1,524 were Intersex Females accounted for 50.5% of the total population The population has grown to 47.6 Million in 2019 from 37.7 Million in 2009 The intercensal growth rate has declined to 2.2% in 2019, from 2.9% in 2009 Average …

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientiﬁc literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; ___working_potential_duplicate; __finaldtb

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Does technology improve reading outcomes? Comparing the effectiveness and cost-effectiveness of ICT interventions for early grade reading in Kenya - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Strigel, Carmen (International Journal of Educational Development, 2016)
Education policymakers are investing in information and communications technology (ICT) without a research base on how ICT improves outcomes. There is limited research on the effects of different types of ICT investments on outcomes. The Kenya Primary Math and Reading (PRIMR) study implemented a randomized controlled trial comparing the effects and cost of three interventions – e-readers for students, tablets for teachers, and the base PRIMR program with tablets for instructional supervisors. The results show that the ICT investments do not improve literacy outcomes significantly more than the base non-ICT instructional program. Our findings show that cost considerations should be paramount in selecting ICT investments in the education sector.
Keywords: Education policy; International education; Kenya; Literacy; Reading; Technology; __:import:01; __:match:final; __:matched; __:study_id:2457283; ___working_potential_duplicate; __finaldtb

Kenya: extreme inequality in numbers - Oxfam (Oxfam International, 2020)

Multilingual Literacy Skill Development in Kenya: Results from Medium Scale Randomized Controlled Trials. - Piper, Benjamin (Society for Research on Educational Effectiveness, 2016)
Keywords: ⛔ No DOI found

Kenya GPE COVID-19 Learning Continuity in Basic Education: Stakeholder Engagement Plan - Ministry of Education, Kenya (2020)

Developing a systemic approach to teacher education in sub-Saharan Africa: emerging lessons from Kenya, Tanzania and Uganda - Hardman, Frank; Ackers, Jim; Abrishamian, Niki; O’Sullivan, Margo (Compare: A Journal of Comparative and International Education, 2011)
While many countries in Eastern and Southern Africa are on track for meeting the Education for All targets, there is a growing recognition of the need to improve the quality of basic education and that a focus on pedagogy and its training implications needs to be at the heart of this commitment. By drawing on three East African countries, Kenya, Tanzania and Uganda, which are at different stages of development with regard to the reforming of teacher education, this paper explores the challenges and the lessons learned from each of the countries with regard to the development and strengthening of pre- and in-service training. The tension between quality, breadth and cost-effectiveness is explored together with a broader discussion of key principles to be taken into account when enhancing teacher education in the region as a whole.
Keywords: C:Kenya / Uganda / Tanzania; Education; Education for All; Education reform; Kenya; Pedagogy; Principles; Quality of education; Tanzania; Teacher education; Uganda; ___working_potential_duplicate; basic education; pre-service and in-service training; quality education; sub-Saharan Africa; teacher education reform

Technology adoption in secondary mathematics teaching in Kenya: An explanatory mixed methods study - Kamau, Leonard Mwathi (Syracuse University, 2014)
Keywords: ⛔ No DOI found

Kenya Basic Education COVID-19 Emergency Response Plan - State Department of Early Learning and Basic Education, Kenya (2020)

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Kenya Vision 2030: A Globally Competitive and Prosperous Kenya - Government of Kenya (Republic of Kenya, 2007)

Kenya Public Expenditure Review 2020: Options for Fiscal Consolidation after the COVID-19 Crisis - World Bank (World Bank, 2020)
The objective of this public expenditure review (PER) is to provide the government with options for fiscal consolidation and support macroeconomic stability in the medium-term. This PER addresses the broad topic of expenditure efficiency and examines options for expenditure rationalization to help return Kenya’s fiscal accounts to a prudent trajectory in the medium-term. The PER is being undertaken as a programmatic analytical product with two modules. The first module focuses on identifying options for expenditure rationalization and measures to strengthen within-year expenditure control for better expenditure management. The second module to be delivered in FY21 will focus on efficiency, effectiveness, and equity of spending within public services delivery sectors of education, health, and disaster risk financing. The report builds upon several other Bank-led reports that contribute to the discussion around improving public expenditure and strengthening expenditure controls in Kenya. It complements an ongoing governance for enabling service delivery and public investments in Kenya (GESDeK) project, which is at the forefront in supporting numerous reforms highlighted in this PER to improve efficiency in spending and strengthen expenditure controls. The report is organized as follows: chapter one contains the macro context, trends, and composition of spending, overall balance and debt. Chapter two contains the fiscal and debt sustainability analysis while chapter three presents options for expenditure rationalization in Kenya. Chapter four ties it all together with fiscal savings and policy recommendations.
Keywords: Debt Sustainability; Expenditure Control System; Fiscal Sustainability; Fiscal Trends; Public Debt; Public Expenditure; Public Investment Management; Public Procurement; Public Wage Bill; Revenue

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a national education system - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using Information and Communication Technology, 2017)
Previous large-scale education technology interventions have shown only modest impacts on student achievement. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed the National Tablets Program. The National Tablets Program is integrated into the Tusome activity by providing tablets to each of more than 1,200 instructional coaches in the country to use when they visit teachers. This enables a national database of classroom instructional quality, which is used by the education system to monitor overall education quality. The tools provided on the tablets are designed to help coaches increase the quality of their instructional support to teachers, and deepen the shallow accountability structures in Kenya’s education system. Using results of a national survey, we investigated the ability of the National Tablets Program to increase the number of classroom observations done by coaches and to improve student learning outcomes. Survey results showed high levels of tablet program utilization, increased accountability, and improvements in learning outcomes. We share recommendations regarding large-scale ICT interventions and literacy programs.
Keywords: Accountability; C:Kenya; Classrooms; Clinical trials; Developing countries--LDCs; Digital divide; Digital literacy; ERIC, Current Index to Journals in Education (CIJE); Education; Education reform; Educational Practices; Educational Quality; Educational Technology; Educational technology; Foreign Countries; Handheld Devices; Initiatives; Intervention; Interviews; Kenya; Learning; Literacy; Literacy programs; Literature reviews; Maine; National Surveys; Observation; Outcomes of Education; Portugal; Quality; Questionnaires; Reading; Schools; Software; South Korea; Statistical Analysis; Statistical Significance; Students; Teachers; Teaching; Technology Uses in Education; Telecommunications; Texas; Turkey; Uruguay; __:import:01; __:match:final; __:matched; __:study_id:2096038; __finaldtb; ⛔ No DOI found

Teaching Practices in the 21st Century in Kenya: A Qualitative Approach - Kaume-Mwinzi, Regina K. (International Journal of Educational Excellence, 2018)
Education is an engine for the growth and progress of any society and it is responsible for building human capital which sets technological and economic growth. In the pre-technology education context, the teacher controlled the instructional process, the content was delivered to the entire class and the teacher emphasized factual knowledge. However, the current global demands in education require the use of approaches that are learner-centered and embracing integration of ICT. The purpose of this study is to establish the pedagogy used in Kenya for the 21st century learner. The case study design was used to collect qualitative data from three teachers who were purposively sampled from three education sub-sectors in Kenya: primary, secondary and university. The interview was guided by three research questions: Which teaching practices are used in Kenya? Which are the ‘best’ teaching practices in Kenya in the 21st century? What are the barriers for the ‘best’ teaching practices in Kenya? The findings were that the teaching methods currently in use were mainly teacher-centered although the respondents revealed that the ‘best’ teaching practices for the 21st century learner were student-centered. However, the barriers were large classes, lack of resources and facilities among other factors. The study recommends realignment of education policies to give priority to build pedagogical capabilities of teachers, provide digital tools and other resources. This would enable the 21st century learners’ opportunity to unleash their potential.

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a national education system - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using Information and Communication Technology, 2017)
Previous large-scale education technology interventions have shown only modest impacts on student achievement. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed the National Tablets Program. The National Tablets Program is integrated into the Tusome activity by providing tablets to each of more than 1,200 instructional coaches in the country to use when they visit teachers. This enables a national database of classroom instructional quality, which is used by the education system to monitor overall education quality. The tools provided on the tablets are designed to help coaches increase the quality of their instructional support to teachers, and deepen the shallow accountability structures in Kenya’s education system. Using results of a national survey, we investigated the ability of the National Tablets Program to increase the number of classroom observations done by coaches and to improve student learning outcomes. Survey results showed high levels of tablet program utilization, increased accountability, and improvements in learning outcomes. We share recommendations regarding large-scale ICT interventions and literacy programs.
Keywords: Accountability; C:Kenya; Classrooms; Clinical trials; Developing countries--LDCs; Digital divide; Digital literacy; ERIC, Current Index to Journals in Education (CIJE); Education; Education reform; Educational Practices; Educational Quality; Educational Technology; Educational technology; Foreign Countries; Handheld Devices; Initiatives; Intervention; Interviews; Kenya; Learning; Literacy; Literacy programs; Literature reviews; Maine; National Surveys; Observation; Outcomes of Education; Portugal; Quality; Questionnaires; Reading; Schools; Software; South Korea; Statistical Analysis; Statistical Significance; Students; Teachers; Teaching; Technology Uses in Education; Telecommunications; Texas; Turkey; Uruguay; __:import:01; __:match:final; __:matched; __:study_id:2096038; __finaldtb; ⛔ No DOI found

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The ICT Landscape in Northern Kenya: Challenges & Opportunities - Mugendi, Jacob; Valbuena, Gustavo (Engineering For Change, 2020)
EDITORIAL TEAM: Carolina Rojas, E4C Expert Fellow; Mariela Machado, E4C Program Manager; Grace Burleson, E4C Research Manager DISCLAIMER: Any views and/or opinions expressed in this post by individual authors or contributors are their personal views and/or opinions and do not necessarily reflect the views and/or opinions of Huawei Technologies or iGov Africa. Click here to view the full report. The northern region of Kenya, which is arid and semi-arid in nature, forms...

Balloons to Deliver Emergency Internet Across Kenya - Alison, Buckholtz (2020)
Telkom Kenya-Loon partnership will result in country-wide 4G connectivity during pandemic, boosting government services.

Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Kibukho, K.; Kwayumba, Dunston; Jepkemei, Evelyn; Piper, Benjamin (2014)
Kenya is investing in information and communication technology (ICT) to improve children’s learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Liquid Telecom Kenya (Liquid telecom, 2020)
Liquid Telecom in Kenya is a full-service data communications carrier offering a host of services including IP, broadband transport, infrastructure services and co-location services.

Kenya Overview - World Bank (2019)
The World Bank’s work in Kenya supports the government’s Vision 2030 development strategy, which aims to accelerate sustainable growth, reduce inequality, and manage resource scarcity.

Reform Policy to Boost Kenya’s Mobile Connectivity Says GSMA - GSMA (2020)
48 Per Cent of the Population of Kenya Remains Unconnected to Mobile Networks   Nairobi: Kenya is making excellent progress to achieve its target of universal broadband coverage by 2030 and there is an opportunity for the government to accelerate the country’s digital transformation with more supportive policies. This was the key finding of a […]

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a National Education System - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using ICT, 2017)
Previous large-scale education technology interventions have shown only modest results. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed a national tablets program. The program provides tablets to each of more than 1200 instructional coaches in the country and includes a national database of classroom quality, which is used by the education system to monitor education quality. The tablets program helps coaches to...
Keywords: ⛔ No DOI found

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a National Education System - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using ICT, 2017)
Previous large-scale education technology interventions have shown only modest results. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed a national tablets program. The program provides tablets to each of more than 1200 instructional coaches in the country and includes a national database of classroom quality, which is used by the education system to monitor education quality. The tablets program helps coaches to...
Keywords: ⛔ No DOI found

Improving Early-Grade Literacy in East Africa: Experimental Evidence from Kenya and Uganda - Lucas, Adrienne M.; McEwan, Patrick J.; Ngware, Moses; Oketch, Moses (Journal of Policy Analysis and Management, 2014)
Primary school enrollments have increased rapidly in sub-Saharan Africa, spurring concerns about low levels of learning. We analyze field experiments in Kenya and Uganda that assessed whether the Reading to Learn intervention, implemented by the Aga Khan Foundation in both countries, improved early-grade literacy as measured by common assessments. We find that Ugandan literacy (in Lango) increased by 0.2 standard deviations. We find a smaller effect (0.08) on a Swahili literacy test in Kenya. We find no evidence that differential effects are explained by baseline differences across countries in student test scores, classroom attributes, or implementation fidelity. A plausible explanation that cannot be directly tested is differential effective exposure to the literacy treatment in the tested languages. Students in Kenya were tested in Swahili, which is not necessarily the main language of instruction in primary schools, despite official policy.

Digital 2020: Kenya - DataReportal (2020)
All the data, statistics, and trends you need to understand digital use in Kenya in 2020, including the latest reported figures for the number of internet users, social media users, and mobile connections, and key indicators for ecommerce use.
Keywords: ___working_potential_duplicate

E-learning in secondary Schools in Kenya: A Case of the NEPAD E-schools - Ayere, Mildred; Odera, F; Agak, John (Educational Research and Reviews, 2010)
The New Partnership for Africa's Development (NEPAD) schools were set up as centres of excellence in Information and Communication Technology (ICT) integration, so that other schools could copy their model in e-learning. It was for this reason that they were provided with computers, e-materials, internet appliances and trained personnel. But to gauge their levels of success as e-learning centres there was need to compare them to other schools offering ICT education in Kenya. It was for this reason that this study compared the application of the e-learning in NEPAD and non-NEPAD schools in Kenya. Specifically, the study: Identified significant differences in levels of integration of ICT in curriculum subjects; surveyed the differences in use of e-materials in education research; examined availability of e-libraries; identified significant differences in academic performance of NEPAD and non-NEPAD schools attributed to e-learning. The study used a combination of an exploratory approach using descriptive survey and ex-post-facto design. It was carried out in six of the eight provinces in Kenya, where the NEPAD schools are located. It targeted 1600 form four students from 35 secondary schools involved in ICT education (NEPAD schools included). Saturated sampling was used for the six NEPAD schools while six non-NEPAD schools were selected through simple random sampling. The sample consisted of three officials from the ministry of education, twelve principals and twelve heads of ICT department (HODs), and 570 of the form four students. The main data collection instrument was the questionnaire; administered to the students, the principals, and the HODs. The interview schedule was administered to the ministry of education personnel while an observation checklist was used as a confirmatory tool. Analysis was done using both descriptive and inferential statistics. The study found that, there was a significant difference in the application of e-learning in NEPAD and non-NEPAD schools. Based on these findings, it was recommended that schools involved in ICT education should intensify teacher facilitation and support teacher roles that are required in e-learning Key words: E-Learning, ICT integration, ICT education, new partnership for Africa's development (NEPAD).
Keywords: ⛔ No DOI found

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Information Literacy in Kenya - Tilvawala, Khushbu; Myers, Michael D.; Andrade, Antonio Díaz (The Electronic Journal of Information Systems in Developing Countries, 2009)
There are a growing number of information and communications technologies (ICT) initiatives in developing countries. These initiatives are usually undertaken on the basis that they are important for social and economic development. However, one barrier to the efficient utilisation of ICT in developing countries is the relatively low level of information literacy. Without the ability to manipulate and use information effectively, investments in ICT-for-development projects may be unsuccessful. In this research project, three ICT initiatives in Kenya are analysed in the light of the dimensions of information literacy. Implications for other developing countries are discussed.
Keywords: Information and communications technology; Kenya; developing countries; information literacy

Integration of ICT in Education in a Secondary School in Kenya: A Case Study - Kisirkoi, Florence (Literacy Information and Computer Education Journal, 2015)
Amidst reports that there was very little integration of Communication Information Technology (ICT) in curriculum delivery in many secondary schools in Kenya, it was reported that one secondary school was using ICT in instruction and practicing learner centered instructional approaches and there was improved learning outcomes. The school’s mean score in the Kenya Certificate of Secondary Education had improved from 6.2 to 8.4 between 2007 and 2013. This study teacher computer literacy levels, motivation for integration, perceived reason for the intervention and the impact on teaching and learning. A case study was conducted and observation and interview schedules were used to collect data. The study population was the 535 students and the 28 teachers in the school. Simple random sampling was used to sample 30 students and 18 teachers. It was established that the students and teachers were computer literate and were able to manage computer applications for teaching and learning. The Learning process was found to be practical with learner interactions and activities based learning. The motivation was desire to teach better coupled with visionary, supportive school leadership. The school was using ICT as teaching learning tool and there was improvement of learning environment and outcomes. Many schools ought to emulate the school.

The effect of internet services on child education outcomes: evidence from poa! Internet in Kenya - Okyere, Charles Yaw (Journal of Development Effectiveness, 2022)
In 2016-2018 poa! Internet, a private internet service provider, distributed free internet services across schools in Nairobi, Kenya. Using inverse probability weighting (IPW) method, the study finds that the intervention significantly increases students’ internet use and training, receipt of information on educational content, and participation in information and communication technologies (ICTs) education programmes. However, the study does not find evidence that internet services increase school attendance. The results suggest that facilitating access to internet services in schools can significantly increase child computer and internet skills and training in developing countries, even if those investments have limited gains on school attendance.
Keywords: Internet services; Kenya; education; gender; quasi-experimental design

Computerizing Primary Schools in Rural Kenya: Outstanding Challenges and Possible Solutions - Ogembo, Javier Gordon; Ngugi, Benjamin; Pelowski, Matthew (The Electronic Journal of Information Systems in Developing Countries, 2012)
This paper investigates the outstanding challenges facing primary schools’ computerization in rural Kenya. Computerization of schools is often envisaged as a ‘magic’, or at least a particularly efficient, solution to many of the problems that developing countries face in improving primary school education. However, while a great deal of consideration is given to the technical issues surrounding computer implementation, government policy makers, administrators, aid organizations and individuals participating in school computerization programs often have not carefully considered the contextual questions surrounding this endeavour. Specifically: 1.) what problems do rural schools actually want to solve with computerization; 2.) is computerization the most important priority for rural schools; 3.) are schools ready, in terms of infrastructure, for a computer in the classroom; or 4.) might there be better avenues for implementing access to the benefits of the digital age? These questions and the issue of school computerization are considered via results from a survey of thirty-seven rural Kenyan primary public schools. Results indicate that, while all schools had low ICT status making them primary targets for computerization, only eleven percent had at least one ICT compliant teacher, of which all were considered to require further training. In addition we found inadequate infrastructural preparedness – lack of access to electricity, internet; no classroom computer space, few desks, secure walls and protective roofing – posing severe challenges to the outstanding conception of computerization. We consider these results and make recommendations for better adapting programs for computer introduction, and also suggest the use of new innovative devices, such as cell phones, which might already have overcome many of the technical challenges found.
Keywords: ICT; cell phone; classrooms; computerization; primary schools; techno-literacy

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Designing for Scale: Reflections on Rolling Out Reading Improvement in Kenya and Liberia - Gove, Amber; Poole, Medina Korda; Piper, Benjamin (New Directions for Child and Adolescent Development, 2017)
Since 2008, the Ministries of Education in Liberia and Kenya have undertaken transitions from small-scale pilot programs to improve reading outcomes among primary learners to the large-scale implementation of reading interventions. The effects of the pilots on learning outcomes were significant, but questions remained regarding whether such large gains could be sustained at scale. In this article, the authors dissect the Liberian and Kenyan experiences with implementing large-scale reading programs, documenting the critical components and conditions of the program designs that affected the likelihood of successfully transitioning from pilot to scale. They also review the design, deployment, and effectiveness of each pilot program and the scale, design, duration, enabling conditions, and initial effectiveness results of the scaled programs in each country. The implications of these results for the design of both pilot and large-scale reading programs are discussed in light of the experiences of both the Liberian and Kenyan programs.

Effect of Covid-19 Pandemic on the Education System in Kenya - Kathula, Domeniter Naomi (Journal of Education, 2020)
Education is an integral part of human society, its importance in life cannot be ignored as lack of education gives birth to numerous social problems like poor health, internal conflict, poor living standards and many more, education helps people to find a better solution to their problems. Education lets people realize the true value of contribution and help become the backbone of the society. Innovation and creativity can only occur when people are skilled enough to know how to operate with different technologies. Since the first case of the novel coronavirus (COVID-19) was announced in Kenya, many aspects of society and the education sector have been dramatically affected. On March 15th 2020, the Kenyan government closed all learning institutions countrywide to contain the spread of the virus. As the numbers of those infected by coronavirus rose to over 8,000, the ministry of education announced on July 7th that, the 2020 school calendar year will be considered lost due to COVID-19 restrictions. The purpose of this study was therefore to determine the effect of Covid-19 pandemic on the education systems in Kenya. The study was anchored on Classical Liberal Theory of Equal Opportunities. Mixed method design which involved a combination of both quantitative and qualitative approaches was adopted. In?quantitative the study used a survey research design, specifically the study adopted a cross-sectional survey research design. Cross-sectional survey design involves collecting data from a large group of people of different stages of growth at one point in time. The target population for this study included teachers, students and parents. The sample size for the study comprised of 100 teachers, 25 parents and 100 students who were purposively selected across the country. This study used both questionnaire and interview guide to collect primary data. The questionnaires were served to teachers and students online using Google forms while interview guide was administered to the parents using online Google forms as well. The quantitative data collected was analyzed using SPSS. Quantitative analysis involved the use of descriptive analysis, while qualitative data was analyzed using content analysis. The results were presented on tables. The findings revealed that Covid-19 had seriously affected learning among students in Kenya. The study found that the effects of Covid-19 were so severe that some teachers and parents lost their jobs or source of livelihoods. Most of the students were not able to access online learning due to lack of electricity, lack of learning materials and some were forced to relocate to the country side. The study hence concluded that as a result of the challenges presented by the coronavirus and the likely impact of future pandemics the government’s ability to ensure continuation of learning will depend on the ability to swiftly harness available technology, provide adequate infrastructure and mobilize stakeholders to prepare alternative learning programmes. The study concludes that as a result of the emergence of Covid-19 pandemic, teaching and learning activities in all learning institutions in Kenya just like other parts of the world have severely been disrupted. The worst hit learners are the primary and secondary school candidates who should sit for their national examinations at the end of 2020. Based on the conclusion the study recommended that there is need for the government through the ministry of education together with all the stakeholders in education sector in Kenya to navigate through challenges presented by Covid-19 to ensure continued access to provision of quality, equitable and inclusive education during and after the pandemic. Effective implementation of the proposed interventions by education managers and stakeholders will ensure uninterrupted learning in educational institutions in future. This study in addition recommends that it is important to ensure that the Ministry of Education, parents and teachers support vulnerable students to ensure they are not exploited and that no learning loss occurs even as schools delay re-full opening until January 2021 despite grades 4, class 8 and form 4s being back in schools already. Keywords: Covid-19, Pandemic, Education system, Students, teachers, Parents, Kenya.
Keywords: Covid-19; Education system; Kenya; Pandemic; Parents; Students; teachers; ⛔ No DOI found

Status of Teachers' Technology Uptake and Use of GeoGebra in Teaching Secondary School Mathematics in Kenya - Mwingirwa, Irene Mukiri; Marguerite, Miheso Khakasa (International Journal of Research in Education and Science, 2016)
The uptake of technology and specifically, GeoGebra software, in teaching mathematics has had mixed success in spite of its documented benefits. This study investigated teachers’ perspective towards training and eventual use of GeoGebra as a tool to enhance learning of mathematics. In this article we share findings from a larger study that was conducted in Kajiado County in Kenya (Africa) on GeoGebra use in teaching Secondary School Mathematics. This article presents the relationship between observed teachers’ perceptions towards the uptake of GeoGebra, a technology based tool and the actual uptake of GeoGebra using the Diffusion Innovation theoretical framework. Data was collected from practicing mathematics teachers who were exposed to GeoGebra through a series of training sessions. The findings after training sessions with the mathematics teachers showed willingness to use GeoGebra in their classes. The teachers identified Geometry as the topic where use of GeoGebra would be most relevant due to its abstract nature. Teachers’ responses indicated that GeoGebra was perceived as useful for teaching and learning Mathematics and that it would help learners grasp concepts in Geometry. However, the study also found out that systemic support would sustain teachers’ engagement with GeoGebra at classroom level as actualization of Geogebra use did differ significantly from teachers’ perceptions.

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: ___working_potential_duplicate

Can Facebook groups enhance continuing professional development of teachers? Lessons from Kenya - Bett, Harry; Makewa, Lazarus (Asia-Pacific Journal of Teacher Education, 2020)
Continuing Professional Development (CPD) for teachers in Kenya suffers from challenges such as inadequate resources, poor planning, competing interests, among others. Besides being traditional in approach, most CPD sessions are far between to be meaningfully helpful. With increasing uptake of technology and number of social media users in Kenya, Facebook can be a potential platform to enhance teachers’ professional development. This exploratory cross-sectional survey focussed on discussions teachers had in the month of February 2015 on one Facebook Group named ‘Teachers of English’. A directed content analysis of the 647 posts following Shulman’s category of teacher knowledge base revealed that interactions on the group centred on the teaching of English and Literature, as well as on other education-related matters. This study concludes that that Facebook Groups can be fertile avenues for teachers’ ongoing professional development, especially in developing countries where such opportunities are scarce.
Keywords: Content analysis; Education--Teaching Methods And Curriculum; English teachers; Facebook Groups; Kenya; Professional development; Social networks; Teacher education; Teachers; __:import:02; __:match:final; __:matched; __:study_id:2425933; __finaldtb; professional development

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge. [ABSTRACT FROM AUTHOR]
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; __finaldtb

Determinants of Implementation of Public Sector Projects in Kenya: A Case of Laptop Project in Public Primary Schools in Kangundo Sub-County, Machakos County - Muinde, Samuel Mutisya; Mbataru, Patrick (2019)
In One-to-one laptop programs are becoming popular across the globe. However available evidence suggests that their implementations in schools are often faced with challenges. For example, even though the government of Kenya began supplying laptops to public primary schools in 2016; reports indicate that the gadgets have not fully been put into use in many schools. Most of the empirical studies done in this area have majorly focused on the level of success and factors influencing implementation of the project and not the extent to which specific variables determine implementation of the project, thus resulting to a research gap. In order to fill this gap, study focused on the determinants of implementation of the laptop project in public primary schools in Kangundo Sub-county. The study was guided by 4 research objectives: i.) To assess the extent to which teachers’ perception determine implementation of the laptop project; ii) To establish the extent to which teachers’ capacity in ICT determine implementation of the laptop project; iii) To establish the extent to which availability of facilities determine the implementation of the laptop project; and iv) To establish the extent to which availability of digital subject content determine implementation of the laptop project. The study was premised on three (3) theories; Technology Acceptance Model, Constructivist Learning Theory and Resource Based Theory. The study adopted descriptive survey design. It targeted all the public primary schools, all teachers in lower primary and all the Ministry of Education officials heading the four zones that constitute Kangundo Sub-county. The study targeted all the 74 public primary schools which have 222 lower primary teachers, 74 head teachers and 4 MOEST officials making a total target population of 300. It adopted stratified random sampling in stratifying the schools into four zones and randomly selected 22 schools. All 22 school heads and all 66 lower primary school teachers of the participating schools were purposively sampled. Additionally, the 4 MOEST officials heading the four zones were included, making a sample of 92 participants. Tools of data collection included questionnaires for teachers and school heads, an interview guide for MOEST officials and an observation checklist. The data analysis was conducted using SPSS. Content analysis was adopted in analyzing qualitative data whereas descriptive statistics such as frequencies and percentages were used in analyzing quantitative data. Tables and figures were used to present the study results. The inferential analysis conducted shows that there was a significant relationship between independent and dependent variables. Both teachers’ capacity on ICT and availability of facilities were found to have significant effect on implementation of the laptop project while teachers’ perception and availability of digital subject content were found to have insignificant effect on the project in public primary schools in Kangundo Sub-County.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Kenya: Heavy Rains and Flooding Update #7 (19 June 2024) - OCHA (2024)

Basic Education Infrastructure - Kenya Vision 2030 (2020)

Digital Economy Blueprint - Kenya Digital Economy (2019)

Draft Value Added Tax (Digital Marketplace Supply) Regulations, 2020 - Kenya Revenue Authority (2020)

National Education Sector Strategic Plan - Ministry of Education, Kenya (2018)

National Information and Communication Technology Strategy for Education and Training - Ministry of Education, Kenya (2006)

Digital Learning Programme - Ministry of Education, Kenya (2016)

Second Quarter Statistics Report for the Financial Year 2019/2020 - Communications Authority of Kenya (2019)

National Education Sector Strategic Plan v2 - Ministry of Education, Kenya (2018)

Radio Timetable 2020 - Kenya Institute of Curriculum Development (2020)

Edu TV Channel 2020 - Kenya Institute of Curriculum Development (2020)

Survey Report on Socio Economic Impact of COVID-19 on Households - Kenya National Bureau of Statistics (2020)

Changing pedagogical practice in Kenyan primary schools: the impact of school‐based training - Hardman, Frank; Abd‐Kadir, Jan; Agg, Catherine; Migwi, James; Ndambuku, Jacinta; Smith, Fay (Comparative Education, 2009)
Keywords: C:Kenya

National Pre-primary Education Policy Standard Guidelines - Republic of Kenya Ministry of Education (Republic of Kenya Ministry of Education, 2018)

National Pre-Primary Education Policy 2017 - Republic of Kenya Ministry of Education (Republic of Kenya Ministry of Education, 2017)

School-cooperation Kenya - Norway: friendship and learning through social media? - Pedersen, Hege (86 s., 2015)
Keywords: ⛔ No DOI found

National Information, Communications and Technology (ICT) Policy - Ministry of Information, Communications and Technology, Kenya (2019)

Social Pillar | Kenya Vision 2030 - Government of Kenya (2008)

The Promise of Inclusive Digital Learning in Kenya - Government of Kenya (2022)

Kenya Digital Master Plan 2022-2032 - Republic of Kenya ICT Authority (2022)

Keep Kenya Learning (KKL): Training to Engage Caregivers in Digital Learning - Keep Kenya Learning (2022)

Vision 2030 Collaboration with Central Planning and Projects Monitoring Units | Kenya Vision 2030 - Government of Kenya (2007)

Kenya Basic Education COVID-19 Emergency Response Plan - Ministry of Education, Republic of Kenya (2020)

Kenya National Education Sector Strategic Plan 2018 - 2022 - Ministry of Education, Republic of Kenya (2018)

Kenya Basic Education COVID-19 Emergency Response Plan - Ministry of Education, Republic of Kenya (2020)

Preparing a Workforce for the Evolving Information Economy: A Survey on ICT Access and Use in Kenya Secondary Schools. Summit Strategies Limited, Nairobi. - Kenya Schoolnet (2003)

Report of the Presidential Working Party on Education Reform: ​​Transforming education, training and research for sustainable development in Kenya - Government of Kenya (2023)

Policy on Information and Communication Technology in Education and Training | Ministry of Education - Kenya - Republic of Kenya Ministry of Education (2021)

Adolescents (age 10 - 19) presenting with pregnancy at health facilities - Kenya Health Information System (KHIS) (African Institute for Development Policy, 2020)
Rates of adolescent pregnancy are once again on the rise in Kenya.  The sudden surge threatens to cut short the pursuit for education and opportunities for especially vulnerable girls in the country.

Promises to keep: impact of COVID-19 on adolescents in Kenya - Presidential Policy and Strategy Unit (Kenya); Population Council (2021)

Home - Ministry of Education, Kenya (2016)

Education Sector Budget Proposal Report 2023/24 - Government of Kenya (Government of Kenya, 2023)

Brief 1 - How DPL can support FLN and equitable learning in Kenya - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Helping improve the Kenya Education Cloud with a SWOT analysis - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
In early 2021, EdTech Hub partnered with the Kenya Institute of Curriculum Development to support them to analyse the strengths, weaknesses, opportunities and threats of the Kenya Education Cloud. This blog highlights what we learnt, and lessons that can inform the development of Virtual Learning Environments around the world.  Governments all over the world responded to Covid-19 school closures by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Equality of Usage of Personalised Learning Software: Key Findings from EdTech Hub and EIDU’s Sandbox in Kenya - Rahman, Asad; Tanveer, Rabia; Olwala, Tess; Musungu Ongadi, Allan; Freidberg, Aidan; Munialo, Indrah (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Algorithmic design in EdTech: Investigating adaptivity for learners and teachers in a digital personalised learning tool in Kenya - Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Sun, Chen (EdTechHub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Raising readers: Kenya schools use of technology to improve parent and carers' engagement in literacy learning: Inception Report - Nicolai, Susan; Zubairi, Asma; Bapna, Akanksha; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learners and Caregivers' Barriers and Attitudes to SMS-based Mobile Learning in Kenya: Key findings from a telephone survey - Jordan, Katy; Damani, Kalifa; Myers, Christina; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

SWOT Analysis of the Kenya Education Cloud - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _cover:v3; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Government-led edtech initiatives to improve learning outcomes in Kenya (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Kenya Broadcasting Corporation (2017)

Telkom Kenya Limited (2019)

Kenya Publishers Association (2019)

Kenya National Examination Council (2018)

Elimika (Kenya Education Cloud) (2019)

Kenya Institute of Curriculum Development (2020)

Kenya Institute of Special Education (2020)

Access to electricity (% of population) - Kenya - World Bank (2020)

Low-Tech Personalised Learning to Improve Girls' Education in Kenya - EdTech Hub (EdTech Hub, 2021)

Inequalities in Human Development in the 21st Century, Kenya - UNDP (2019)

Reading Skill Transfer across Languages: Outcomes from Longitudinal Bilingual Randomized Control Trials in Kenya and Haiti. - Piper, Benjamin; Bulat, Jennae; Johnston, Andrew (Society for Research on Educational Effectiveness, 2015)
Keywords: ⛔ No DOI found

GPE 2020 Country-level Prospective Evaluations: First annual Report Kenya - Rawal, Prepared Shenila; Aslam, Monazza; Outhred, Rachel (2018)
Keywords: ⛔ No DOI found

USAID/Kenya Primary Math and Reading (PRIMR) Initiative: Kisumu Information and Communication Technology (ICT) Intervention. Endline Report. - Piper, B.; Kwayumba, D. (Research Triangle Institute (RTI), 2014)

Examining the secondary effects of mother-tongue literacy instruction in Kenya: Impacts on student learning in English, Kiswahili, and mathematics - Piper, Benjamin; Zuilkowski, Stephanie Simmons; Kwayumba, Dunston; Oyanga, Arbogast (International Journal of Educational Development, 2018)

Empowering self-help groups for caregivers of children with disabilities in Kilifi, Kenya: Impacts and their underlying mechanisms - Bunning, Karen; Gona, Joseph K.; Newton, Charles R.; Andrews, Frances; Blazey, Chantelle; Ruddock, Hannah; Henery, Jessica; Hartley, Sally (PLOS ONE, 2020)
Bringing up a child with disabilities in a low-income setting is challenged by inadequate resources, limited psycho-social support and poverty. Not surprisingly, many caregivers experience fatigue, distress and isolation. To address and investigate these issues, action was taken to set up twenty self-help groups focusing on caregiver empowerment. A realist evaluation design was adopted to evaluate impacts associated with the self-help process and to identify mechanisms determining the outcomes. Monthly monitoring visits were conducted to the groups during a ten-month set-up period, at the end of which eleven active groups remained, nine having dissolved due to disputes, corruption and extreme environmental conditions. A facilitated intervention was delivered to the active groups (N = 154) over a six-month period. The members were guided to review and discuss topics such as economic empowerment, personal situation, peer support, community inclusion, access to health and education. Evaluation employed mixed methods using questionnaires (n = 75) and semi-structured interviews (n = 36) pre- and post-intervention. At baseline, the burden of caregiving was characterised by aloneness, challenges, stigma and discrimination. Post-intervention, caregiver agency was defined by togetherness, capacity-building, acceptance and well-being. Significant impacts associated with caregiver perceptions included increased social support, reduced severity of child’s disability and decreased effects of extrinsic factors affecting the caregiver’s role. Mechanisms of ‘handling goods and money’ and ‘social ties and support’ appeared to underpin the outcomes. Caregiver empowerment was associated with newly developed skills, social connectedness and resource mobilisation. Documentation of group processes contributes to the evidence on community-based inclusive development.
Keywords: Caregivers; Child abuse; Children; Disabilities; Finance; Food; Human families; Social discrimination

M-Shule - Together we learn, together we succeed - M-Schule LTd (2018)
M-Shule is the first adaptive, mobile learning management platform designed to improve performance for millions of primary school students across Kenya and Sub-Saharan Africa

Out of 47.6 million Kenyans, 35.7 million are under the age of 35 - Ndungu, Tonny (Citizen Digital, 2020)
Kenya is a country of the youth according to the 2019 Census results which shows that 75% of the  47.6 million population is under the age of 35.

A second chance to dream: initiating ODeL in secondary school re-entry programs for young adult secondary school dropouts the case of Mumias District, Western Kenya - Musita, Richard; Ogange, Betty O.; Lugendo, Dorine (Distance Education, 2018)
The Kenyan education system has very limited re-entry options for learners who drop out before attaining secondary school certificate. It is very difficult to access training and or secure a job that requires at least secondary school education. This study examined the prospects of initiating Open and Distance e-Learning(ODeL) in re-entry programmes into high school for out of school Young Adult Secondary School Dropouts (Y.A.S.S.D). The study focused on the enablers and challenges of initiating ODeL in the secondary school re-entry programmes. An alternative flexible and sustainable community based ODeL model that potentially can address re-entry for the Y.A.S.S.D is proposed. A qualitative phenomenological design was used; focus group discussion and interviews were conducted from a purposeful sample of participants. The study revealed that the potential of ODeL in addressing re-entry into secondary school for Y.A.S.S.D great. Majority of the participants were aware of the existing secondary school re-entry options, however, ODeL appeared new. Despite there being challenges in introducing the ODeL mode of study in secondary school re-entry programmes, it is viable and requires further exploration. The enablers of this mode of study are largely in place to the extent appreciated by participants in the study.
Keywords: Re-entry; dropouts; open distance e-learning

Learning English Language by Radio in Primary Schools in Kenya - Odera, Florence (2011)
Learning English Language by Radio in Primary Schools in Kenya By Florence Y. Odera (PhD) P.O.Box 2303, Kisumu, Kenya Introduction and background information One of the
Keywords: ___working_potential_duplicate

Experimental evidence on scaling up education reforms in Kenya - Bold, Tessa; Kimenyi, Mwangi; Mwabu, Germano; Ng’ang’a, Alice; Sandefur, Justin (Journal of Public Economics, 2018)
What constraints arise when translating successful NGO programs to improve public services in developing countries into government policy? We report on a randomized trial embedded within a nationwide reform of teacher hiring in Kenyan government primary schools. New teachers offered a fixed-term contract by an international NGO significantly raised student test scores, while teachers offered identical contracts by the Kenyan government produced zero impact. Observable differences in teacher characteristics explain little of this gap. Instead, data suggests that bureaucratic and political opposition to the contract reform led to implementation delays and a differential interpretation of identical contract terms. Additionally, contract features that produced larger learning gains in both the NGO and government treatment arms were not adopted by the government outside of the experimental sample.
Keywords: Contract teachers; Education; External validity; Kenya; Randomized evaluation; State capacity

How school closures during COVID-19 further marginalize vulnerable children in Kenya - Jepkemei, Damaris Seleina Parsitau and Evelyn (Brookings, 2020)
School closures in Kenya have devastating consequences for marginalized learners.

Improving Early Grade Education Across Kenya - RTI International (RTI, 2022)
Tusome focuses on four key interventions developed and proven to improve literacy outcomes in Kenya. Learn about the impact of this program.

Drought situation in the Kenya ASAL areas now at crisis level - Kenya | ReliefWeb - ASAL Humanitarian Network (2022)
News and Press Release in English on Kenya about Agriculture, Climate Change and Environment, Drought and more; published on 5 Oct 2022 by ASAL Humanitarian Network

Mobile Penetration and Growth in Kenya - Kibuacha, Frankline (GeoPoll, 2021)
Kenya is one of the most technology-advanced countries in Africa, which has had many christen it the Silicon Savannah, powered by its mobile penetration.

Engaging parents and caregivers in EdTech is critical to foundational learning in Kenya - Nicolai, Susan; Khan, Amina; Mwachi, Joan; Otieno, Jennifer Cotter (EdTech Hub, 2022)
Kenya, sometimes called the ‘Silicon Savannah’ of Africa, is home to one of the most vibrant EdTech ecosystems in Africa (see Otieno & Taddesse, 2020). Building on government initiatives such as the flagship Digital Literacy Programme (DLP), the country’s Covid-19 education response (Ngware & Ochieng, 2020) included tremendous efforts to provide distance learning solutions. This week, the Kenya EdTech Summit 2022 is bringing together many of those who have been making this happen to discuss the role of evidence and collaboration to accelerate the pace of progress in Kenya.

Virtual learning under lockdown casts doubt on Kenya as the Silicon Savannah - Miller, Noah (Africa at LSE, 2020)
Kenya's response to the COVID-19 epidemic challenges its reputation as the Silicon Savannah when it comes to the switch to digital education.

Tusome Early Grade Reading Activity - RTI International (RTI, 2016)
Across Kenya, literacy rates in primary schools are significantly lower than expected despite increased access and enrollment. The Kenyan education system is seeking to improve learning outcomes by instilling better instructional practices, expanding resources for teacher training, and developing learning materials that support multilingual literacy. Kenya’s approach to the challenge of raising literacy and learning outcomes is unique in its ambitious goals and well-researched methods for achieving its goal at a national scale.

PARENTAL INVOLVEMENT IN PRIMARY SCHOOLS IN KENYA AS A MAJOR STRATEGY FOR ACADEMIC SUCCESS - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
The new Kenyan curriculum emphasizes the role of parents as essential to their children’s education and in the success of curriculum implementation. The development requires a change in how parents and the community interact with schools and education. The perception in Kenya has always been that education is the sole responsibility of the school and the teacher. And so, parental involvement in Kenya has mainly been limited to financial contributions and teacher-parent meetings. With the introduction of new curriculum, the role of parent is crucial for the academic success of the child. A literature study investigated the extent of parental involvement in primary schools in Kenya. The data is obtained from a variety of library articles addressing parental involvement in Primary schools in different counties in Kenya. The current study found that majority of parents are involved in their children’s education, however, more awareness of the parental involvement is needed and more strategies on parental involvement needs to be employed for the success of the new curriculum.  Article visualizations:
Keywords: academic achievement; parental involvement; primary schools; ⚠️ Invalid DOI

PARENTAL INVOLVEMENT IN PRIMARY SCHOOLS IN KENYA AS A MAJOR STRATEGY FOR ACADEMIC SUCCESS - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
The new Kenyan curriculum emphasizes the role of parents as essential to their children’s education and in the success of curriculum implementation. The development requires a change in how parents and the community interact with schools and education. The perception in Kenya has always been that education is the sole responsibility of the school and the teacher. And so, parental involvement in Kenya has mainly been limited to financial contributions and teacher-parent meetings. With the introduction of new curriculum, the role of parent is crucial for the academic success of the child. A literature study investigated the extent of parental involvement in primary schools in Kenya. The data is obtained from a variety of library articles addressing parental involvement in Primary schools in different counties in Kenya. The current study found that majority of parents are involved in their children’s education, however, more awareness of the parental involvement is needed and more strategies on parental involvement needs to be employed for the success of the new curriculum.  Article visualizations:
Keywords: academic achievement; parental involvement; primary schools; ⚠️ Invalid DOI

Collaboration to Realise Kenya’s National Learning Goals through EdTech - Otieno, Jennifer; Omuthe, Ronald; Ampofo, Rudolph (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

M-Lugha: Improving Student’s Access to Literacy and Numeracy by using Local Language Instruction in Northern Kenya - Cordeiro, Paula (Global Ed Leadership, 2021)
Abdinoor Alimahdi is a former telecommunications engineer from Kenya. He is an Award winning EdTech innovator and social entrepreneur. Some of the awards include:  Best 100 startups (StartupIs…

Needed: An Ecosystem for Meaningful Digital Innovation in Northern Kenya - Aslan Afrika (Aslan Afrika, 2021)
The information and communications technology (ICT) industry thrives in Kenyan cities, but vast rural tracts in Northern Kenya are stranded on the wrong side of the digital divide. One of the weakest links is a lack of infrastructure, both for […]

Putting girls’ education first in Kenya | Blog | Global Partnership for Education - GPE (2020)
With support from the Global Partnership for Education, the Government of Kenya is making strides in ensuring that all girls – including those living in the poorest and most remote areas of the country - have access to quality education.

Climate Change and Education in Kenya - Fitzpatrick, Rachael; Amenya, Donvan (Education Development Trust, 2023)
What impact does climate change have on education, especially in areas which are vulnerable to climate disasters and extreme weather events? In this report, we explore the impact of climate change on schools and learning in six counties in Kenya (Nairobi, Mombasa, Turkana, Tana River, Kwale and Kilifi).

Many Children Left Behind? Textbooks and Test Scores in Kenya - Glewwe, Paul; Kremer, Michael; Moulin, Sylvie (American Economic Journal: Applied Economics, 2009)
A randomized evaluation in rural Kenya finds, contrary to the previous literature, that providing textbooks did not raise average test scores. Textbooks did increase the scores of the best students (those with high pretest scores) but had little effect on other students. Textbooks are written in English, most students' third language, and many students could not use them effectively. More generally, the curriculum in Kenya, and in many other developing countries, tends to be oriented toward academically strong students, leaving many students behind in societies that combine a centralized educational system; the heterogeneity in student preparation associated with rapid educational expansion; and disproportionate elite power. (JEL O15, I21, I28, J13)

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Factors Affecting Adoption of E-Learning Technology in Kenya - Kingori, Rhoda Mbithe (United States International University - Africa, 2018)
Internet penetration in Africa has been accelerated, with Kenya at the fore front at over 89.5% penetration, this penetration has led to an increase in knowledge repository for Kenyans to choose from and as a result E-learning has steadily increased not only in tertiary institutions but in informal learning as well. Facebook and YouTube are some of the web based tools, – that are listed as having potential applications for teaching and learning. As a result, it is essential to understand the challenges faced in the adoption of e-learning technology. The overall purpose of this study was to investigate the factors affecting adoption of e-learning technology in Kenya with a focus on three key factors, self-efficacy, objective usability and system accessibility. This study used explanatory/hypothesis research design to investigate the factors which affect adoption of e-learning technology in Kenya. An explanatory research design was fit to the study because it will helped to ascertain not only the relationship between the different variables, but measure the effect and strength of each independent variable on the dependent variable which was the technology adoption. The target population was social media (Facebook) users in Kenya. According to Internet World Statistics there are over 6.2 million Facebook subscribers in Kenya as of June 2017. This study focused on 200 social media users in Nairobi who were interested in e-learning or have ever learned online. They were sampled by geographic cluster, simple random sampling technique with a focus on Nairobi. Online questionnaire was used by Google form and 93% responded. In the first objective of self-efficacy, the correlation result revealed positive correlation between perceived ease of use with self-efficacy (r=0.441, p<0.05) and perceived usefulness with self-efficacy(r=0.337, p<0.05). On the CFA, there was a strong model equation but on the SEM it was not. The path coefficient for the relationship between SE and adoption of e-learning was weak. In the second objective, the correlation result revealed positive correlation between perceived ease of use with objective usability (r=0.598, p<0.05) and perceived usefulness with SE (r=0.456, p<0.05). Based on SEM, the path coefficient for the relationship between objective usability and adoption of e-learning was significant. Without any latent/intervening variable, OU and PEOU was positive and significant at the 0.05 level (βeta=0.938, T-value =3.658, p<0.05). The positive relationship indicates that one unit increase in OU will result in 0.938 increases in PEOU. In the last objective of system accessibility, the correlation result revealed positive correlation between perceived ease of use with system accessibility (r=0.441, p<0.503) and perceived usefulness with system accessibility (r=0.514, p<0.05). The path coefficient for the relationship between system accessibility and adoption of e-learning was weak and not significant hence dropped from the model.The research established that Self-efficacy had little to no effect on adoption of e-learning technology in Kenya. Objective usability was the strongest factor affecting the adoption of e-learning technology while system accessibility had correlation but was not strong enough to impact the model and as such impact the adoption of e-learning technology in Kenya was weak. These findings provided some useful insights for governments, potential instructors or educators, e-learning platforms and policy makers. This recommends and highlights the need to shift from the metropolitan areas to the rural areas in order to get a holistic view of the e-learning environment in Kenya. This research shed light on objective usability as a strong factor on perceived ease of use and perceived usefulness and as such on the adoption of e-learning technology in Kenya. Based the responses received and the SEM analysis further research should focus on the two variables of system accessibility and self-efficacy involving a larger number of variables to examine, as well as larger numbers of respondents to support the factor analysis. Research should also focus on attitude and behavioral intention and their interaction with perceived eases of use and perceived usefulness. The research needs to now shift from the metropolitan areas to the rural areas in order to get a holistic view of the e-learning environment in Kenya.

Investing in ICTs in educational institutions in developing countries: An evaluation of their impact in Kenya - Wims, Pádraig; Lawler, M. (undefined, 2007)
ABSTRACT The incorporation of Information and Communication Technologies (ICT) into the educational curriculum has been promoted as a key step in bridging the digital divide. Despite considerable growth in the numbers of computers acquired by schools in Kenya in recent years and the sacrifices made to finance these, there has been little evaluation of their effectiveness. Consequently, this research seeks to redress this by examining the impact of ICT projects in educational institutions in Kenya. Teaching staff, current students and former students together with parents of current students were surveyed. Key informants were also interviewed to establish the current policies concerning ICT in education in Kenya. An absence of educational software was found, as was the lack of Internet access and use of e-mail. Some 35-40% of secondary school teachers had never used a computer. The research revealed tangible benefits to students from exposure to ICT. It was also found that exposure to computers in schools influenced the career choices of former students. It was concluded that reform of the telecommunications sector is necessary to hasten the rollout of computer technology in educational institutions in Kenya. At school level, the key issues which arose included staff training, mainstreaming of ICT across the curriculum and provision of adequate ICT equipment. Keywords: ICTs; Developing Countries; Education INTRODUCTION This paper investigates the use of computers in educational institutions in the Rift Valley province in Kenya. The adoption of Information and Communication Technologies (ICT) has been promoted as a key step in bridging the digital divide. Despite considerable growth in the numbers of computers acquired by schools in Kenya in recent years and the sacrifices made to finance these, there has been little evaluation of their effectiveness. Consequently, this study examines ICT projects in educational institutions in Kenya, in order to establish normal practice and to determine the effects of adopting ICTs at school level. BACKGROUND TO THE RESEARCH The country of Kenya experiences many of the problems typical of sub Sahara Africa enumerated by Langmia (2006) in that it is lagging behind in information superhighway technology. In terms of telecommunications infrastructural developments, the growth of the fixed telephone network throughout Kenya has been below expectations; according to the Central Bureau of Statistics (2006), the fixed line tele-density was 1.02% (number of fixed lines per one hundred population) during the year 2003 but this has actually deteriorated since then due to the steady population increase in the absence of infrastructural developments. Most of these fixed line subscribers are concentrated in urban areas which account for 94% of the fixed lines while 6% are in rural areas (ibid). In contrast, cellular services have expanded rapidly from under 15,000 customers in 1999 to over 2.8 million in 2004 (Export Processing Zones Authority, 2005). By April 2004, there were an estimated one million internet users and over one thousand cyber cafes throughout the country (ibid.). Keiyo District is one of 18 districts of the Rift Valley Province and lies just north of the equator, at its centre approximately 350km north west of Nairobi. The western and southern areas of the district are fertile and support the highest population. Livestock rearing and tillage farming are the main occupations of the community. To the north of Iten, the administrative centre, the land gradually rises through forests of indigenous trees and bleak high merino-sheep country. Lumbering is also carried on in this area. The total population of Keiyo District was estimated at 144,000 in 2004, and the population density was estimated to be 100 persons per square km (CKRC, 2004). Keiyo District is the eighth most densely populated district in the Rift Valley Province and has an average life expectancy of 61 years. …
Keywords: ⛔ No DOI found

Spatial models for the rational allocation of routinely distributed bed nets to public health facilities in Western Kenya - Macharia, Peter M.; Odera, Patroba A.; Snow, Robert W.; Noor, Abdisalan M. (Malaria Journal, 2017)
In high to moderate malaria transmission areas of Kenya, long-lasting insecticidal nets (LLINs) are provided free of charge to pregnant women and infants during routine antenatal care (ANC) and immunization respectively. Quantities of LLINs distributed to clinics are quantified based on a combination of monthly consumption data and population size of target counties. However, this approach has been shown to lead to stock-outs in targeted clinics. In this study, a novel LLINs need quantification approach for clinics in the routine distribution system was developed. The estimated need was then compared to the actual allocation to identify potential areas of LLIN over- or under-allocation in the high malaria transmission areas of Western Kenya.
Keywords: ANC utilization; Equity; LLINs allocation; Spatial modelling

Challenges Facing Adoption of Information Communication Technology (ICT) In Educational Management in Schools in Kenya - Kipsoi, Emmy; Chang'ach, Dr; Sang C, Hellen (Journal of Sociological Research, 2012)
ICT has contributed greatly to educational management in schools globally (Zhao and Frank, 2003). However, in Kenya schools hardly use ICTs to manage the quality of output, or to raise teacher productivity, or to reduce costs through analyzing spending. This is attributed to a myriad of challenges facing most schools in Kenya with regard to adoption of ICTs in educational management. This has resulted to a slow rate of adoption of technology despite its promise and potential for use in educational management in schools. As such, this paper analyses the lethargy that has surrounded education management in schools with respect to acquisition of Information Communication Technology. Education and training sector has a major role to play in the implementation of the proposed ICT policy. First, the sector itself is a major user of ICT, not only in education, training and research but also in the management of the sector. The paper argues that ICT policies must be dynamic, cost-effective, adaptable, and differentiated between sectors and between the various segments of educational management in order to contribute effectively to education management. The recommendations of this paper provide a basis for the urgent need for the integration of ICTs in educational management in schools in Kenya.

An E-Learning Approach to Secondary School Education”: E-Readiness Implications in Kenya - Redempta, Kiilu (Journal of Education and Practice, 2012)
Information and Communication Technology (ICT) has the potential to enhance access, quality, and effectiveness in education. This paper examines the E-readiness implication on the adoption of e-learning in secondary schools in Kenya. The paper provides an opportunity for reflection on e-learning adoption and the potential role ICT can plays in education. The review has established that up to date, less than 10% of secondary schools in Kenya offer computer studies as a subject in the curriculum despite its perceived potential. The few schools that have an ICT programme limit the number of candidates who take up the subject considering it a specialty irrespective its being an essential subject as other compulsory subjects like Mathematics and Languages. Whereas the processing of information to build knowledge is one of the essential literacy skills vital for the workforce in the 21st century, it is often overlooked in current educational practices. the question of ereadiness of Kenyan schools cannot be overlooked if Kenya plans to use education as a platform for becoming an e-society of the 21st century as envisaged in Vision 2030.Therefore, it is imperative that E-Readiness issues be effectively addressed lest new technology introduced further marginalizes the already deprived Kenyan children. Desktop review of relevant literature was guided by Current Situation Analysis (CSA) which is equivalent to Strength, Weakness, Opportunities and Threats (SWOT) Analysis.
Keywords: ⛔ No DOI found

Testing Digital Timer Tools to Support Early Grade Lesson Delivery - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the second in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates whether introducing a timer alongside digitised lesson plans impacts upon teachers’ lesson plan usage. The A/B test found that providing a timer did not influence how much time teachers spent on digitised lesson plans. While, on average, teachers in the timer group tended to spend less time on lesson plans for literacy and more for numeracy, this was not statistically significant. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; timer; lesson plan An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

National Information, Communications and Technology (ICT) Policy - Ministry of Information, Communications and Technology, Kenya (Government of Kenya, 2019)

The impact of online learning as emerging technology on parents: Case study of parents of primary school children in Nairobi, Kenya. - Emmanuel, Jadesola; Oduor, Collins (Journal of Language, Technology & Entrepreneurship in Africa, 2021)
Kenya, as a nation has a stable schooling system based on synchronous classroom learning. The advent of the COVID 19 pandemic has led to the sudden shift in paradigm to remote schooling learning systems. Several studies have been carried out on remote schooling systems and the impact of parent’s involvement in children’s remote school, but none has been sighted on its impact on parents. The objective of this study was to determine the impact of the sudden paradigm shift on parents of remote schooling pupils in Kenya during this pandemic. A descriptive survey design was utilized. Primary data was collected by online questionnaires and secondary data from past studied. The analysis was done with a statistical application. It was found out that, remote schooling may be easily accepted by many Kenyan parents with 39.8% of parents indicating that they will recommend remote schooling having indicated some benefits derived from it and 24.8% indicating that they will not. It was therefore recommended that the national government should address factors that may hinder effective remote learning, thus encouraging parental involvement and support. It was also recommended that the government and education practitioners should officially develop and implement standards and curriculum for the implementation of remote learning in Kenya in preparation for future pandemics. Keywords: remote schooling, remote learning, descriptive survey design
Keywords: ⛔ No DOI found

The County Allocation of Revenue Bill, 2019 - Government of Kenya (2019)

Kenya: Registered refugees and asylum-seekers as of 31 March 2025 - UNHCR (UNHCR Kenya, 2025)

Professional Development on Digital Literacy and Transformative Teaching in a Low‐Income Country: A Case Study of Rural Kenya - Kerkhoff, Shea N.; Makubuya, Timothy (Reading research quarterly, 2022)
In recent years, the government of Kenya has implemented programs with the hope of moving the country to middle‐income status. The government has implemented the Digital Literacy Programme, distributing tablets to schools across the country, and also a new curriculum, promoting innovative teaching that includes digital literacy, learner‐centered teaching, and relevance to students’ lives. Our purpose in this research was to explore culturally sustaining teaching methods in line with the Kenyan government’s push for innovative teaching and digital literacy attainment for all students. We used case study methods to describe Kenyan teachers’ perceptions of innovative teaching and digital literacy while participating in the Inquiry Initiative, a three‐day professional development series. Participants included preschool, primary, and secondary teachers from Trans Nzoia County. Data sources were pre‐ and post‐surveys, participant‐generated artifacts, and interviews. Our participants perceived the following needs: new literacies for learners, creativity for learners, collaboration and group work, and creativity to overcome technological challenges. Overall, participants embraced learner‐centered teaching theoretically but found that the lack of technological resources created barriers to teaching digital literacy in a learner‐centered fashion. We found that teachers reported mostly using technology for teaching preparation and record keeping rather than engaging students in digital literacy practices. To solve technological challenges, teachers described having students work in groups and using smartphones. Future research could share more creative solutions to technical challenges in low‐income countries.
Keywords: 1‐Early childhood; 2‐Childhood; 3‐Early adolescence; 4‐Adolescence; 6‐Adult; Case Studies; Collaboration; Collaborative Learning; Computer literacy; Constructivism; Creative ability; Creativity; Critical Pedagogy; Culturally Responsive Pedagogy; Digital Literacies; Digital literacy; Digital/media literacy; Education & Educational Research; Educational technology; Gloablization and Literacy; Group work in education; Information literacy; Instructional strategies; methods and materials; Kenya; Literacies; Literacy; Literacy programs; Policy; Postcolonialism; Professional Development; Psychology; Psychology, Educational; Qualitative Research; Social Constructivism; Social Sciences; Socio‐cultural; Students; Study and teaching; Survey Research; Teacher attitudes; Teacher education; Teacher education; professional development; Teachers; Teaching; Teaching methods; Team learning approach in education; Transformative

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: ___working_potential_duplicate

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: Evaluation; Implementation; Literacy; National; Reading; Reform; Systems

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Disaster Management Preparedness in the Education Sector in Kenya – A Case of the COVID-19 Pandemic. - Ngari, Prof Fr Stephen Mbugua; Ndung’u, Stephen W. (Editon Consortium Journal of Educational Management and Leadership, 2020)
This study examined the disaster management preparedness in the education sector in Kenya, with a focus on the COVID-19 pandemic period. The study adopted destktop literature review for data collection. The collected data pertains e-learning in Kenya and in other countries during the time of  the novel coronavirus pandemic. Notably, the education sector, like in many other countries, seeks to actualise the Millennium Development Goals (MDGs) in line with the United Nations and the Education for All (EFA) movement lead by UNESCO (MacEwen, et al., 2011). Examples of these events are; accidents such as the one evident in Kakamega Primary School where the school closed for about two weeks (Daily Nation, 2020), attack by militia groups as was the case of Garissa University in 2015, intercommunity wars that lead to displacements, famine, and fires. These disasters and events, whenever they strike, have led to the closure of affected institutions of learning to pave the way for interventions. Garissa University is a leading example since it had to close for about nine months in 2015-2016 (BBC, 2016). In Kenya, disasters and other events disrupt the progress towards achieving MDGs and EFA time to time, and that was the inspiration for this study. The study concludes that disasters like nature patterns, militia groups, electricity faults, and those instigated by learners can derail learning in education and cause loss of lives. As such, online learning comes in handy to lessen such disasters. The possibility of such learning model has been tested and proved during COVID-19 pandemic and it has been successful in many institutions of higher learning and middle level colleges.
Keywords: COVID-19 Pandemic; Disaster Management; Education Sector; Preparedness

Investigating the Impact of Content Repetition on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the third in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the impact of repeating learning content for pre-primary learners on learner device usage and learning outcomes. The A/B test found that content repetition had an impact on literacy and numeracy outcomes for PP2 learners. PP2 learners’ usage of the DPL tool was significantly reduced with content repetition. However, considering the small size of the mixed-methods sample, caution should be taken when interpreting these results. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; repetition An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Optimising Session Duration on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the first in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the optimal number of minutes for pre-primary learners on a classroom-integrated digital personalised learning tool to optimise learning outcomes. The A/B/C test found different levels of session duration impacted on literacy and numeracy outcomes, with the findings for numeracy dependent on grade level. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; session duration An output of EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G.C.; Nyadimo, E. (Survey Review, 2011)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision making. Such databases contain data such as the geographic location of schools, the numbers of existing schools of different levels in the public and private sectors, their capacities, physical condition and facilities, enrolment and the number of teachers and their attributes. Also often included are data on related natural features and infrastructure such as rivers, roads, economic and administrative centers, medical facilities, religious facilities, etc. This paper describes the Kenyan School Mapping Project, whose objective was to collect such data for all Kenyan learning institutions and to integrate them in a GIS database that could be queried to provide useful information for educational planners, other professional users and average citizens. Results show that at the time of the project, there were nearly 73000 learning institutions in Kenya, ranging from early childhood schools to universities; useful information products on important educational indicators such as schools distribution, enrolments, pupil-teacher ratios and gender parity indices have also been generated from GIS analysis of the data. These results have demonstrated the utility of the database for its stated purpose and therefore shown the project to be a useful model that can be emulated by other developing countries.
Keywords: EMIS; GIS; KENYA; SCHOOL MAPPING

She called, she Googled, she knew: girls' secondary education, interrupted school attendance, and educational use of mobile phones in Nairobi - Zelezny-Green, Ronda (Gender & Development, 2014)
Girls in Kenya commonly face multiple barriers to school attendance. At the same time, mobile phone use is growing throughout the country, and particularly in urban centres including Nairobi. As this technology spreads, the possibility increases of people using mobile phones for their own development purposes, including for education and learning. This article examines mobile phone use by girls at one secondary school in Nairobi, and in particular their attempts to mediate interrupted school attendance using this technology.
Keywords: ICT4D; Kenya; ___working_potential_duplicate; gender; girls' education; international education and development; mobile learning; school attendance

The Effect of Computer-Assisted Instruction on Student’s Attitudes and Achievement in Matrices and Transformations in Secondary Schools in Uasin Gishu District, Kenya - Mwei, Philip K.; Too, Jackson K.; Wando, Dave (2011)
Performance in Mathematics in secondary school Education in Kenya remains poor. Consequently the Kenya secondary school examination (KCSE) Mathematics results continue to cause concern to all the stakeholders in the education sector. Therefore, there is serious and urgent need for intervention. Although research has indicated that computer-assisted instruction (CAI) enhances student achievement, promotes positive attitudes towards Mathematics and instruction, and improves interpersonal relations, few studies have focused on CAI in Kenyan secondary schools Mathematics teaching/learning. The purpose of this study was to investigate the effects of CAI on students’ attitude and achievement in matrices and transformations between form four students who received instruction using CAI module or conventional instruction methods. The pretest – posttest control group experimental research design was used. Six classes selected at random with 205 students participated in the study. Results of this study indicated higher achievement and positive attitudes with CAI treatment groups. Making connections between the goals of Mathematics education and CAI offers a valuable means for improving mathematical knowledge and skills and hence performance in Mathematics.
Keywords: ⛔ No DOI found

Take advantage of demographic dividend - Kibaru-Mbae, Josephine; Chatterjee, Siddharth (UNFPA Kenya, 2016)
Kenya is at the cusp of a “demographic dividend” that could change the country’s fortunes in the first half of the 21st century, but only if the country takes the right steps towards investing in its youth.

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Does community involvement affect teacher effort? Assessing learning impacts of Free Primary Education in Kenya - Atuhurra, Julius F. (International Journal of Educational Development, 2016)
While the impressive school participation impacts of Universal Primary Education policies in Sub-Saharan Africa are widely recognized, attempts to measure learning gains from schooling remain minimal. Utilizing a unique international test score dataset, we measure and explain grade six reading and math learning outcomes in Kenya. By comparing competences between public and private schools before and after the introduction of free primary education, we find large achievement declines and inequalities based on gender and socioeconomic status. The declines are associated with low teacher efforts and community disengagement. Policy studies on community involvement in schools will likely lead to improved learning.
Keywords: Community involvement; Educational policy; Learning achievement; Teacher effort

Integrating Information Communication Technology Skills in Preschool Education in Kenya - Kaindio, Mauta; Wagithunu, Margaret (Mediterranean Journal of Social Sciences, 2014)
The study aimed at investigating the preparedness and attitude of ECDE teachers in preschools, and find out the current situation as far as ICT is concerned. The researchers adopted descriptive design. To obtain information on the current status of the ICT on whether there was any significant difference in preschool teachers’ preparedness in terms of age, qualifications, and experience on ICT. 52 preschool teachers were randomly selected and a questionnaire administered to them. The data was analyzed using SPSS computer software. It was clear from the finding that Kenya is not ready to integrate ICT in preschool curriculum, since the physical facilities, electricity, poverty, trained personnel and teachers’ attitudes towards ICT need to be addresses first. DOI: 10.5901/mjss.2014.v5n5p89

Integrating information communication technology skills in Preschool Education in Kenya - Kaindio, M.P.; Wagithunu, M.N. (Mediterranean Journal of Social Sciences, 2014)
The study aimed at investigating the preparedness and attitude of ECDE teachers in preschools, and find out the current situation as far as ICT is concerned. The researchers adopted descriptive design. To obtain information on the current status of the ICT on whether there was any significant difference in preschool teachers' preparedness in terms of age, qualifications, and experience on ICT. 52 preschool teachers were randomly selected and a questionnaire administered to them. The data was analyzed using SPSS computer software. It was clear from the finding that Kenya is not ready to integrate ICT in preschool curriculum, since the physical facilities, electricity, poverty, trained personnel and teachers' attitudes towards ICT need to be addresses first.
Keywords: ⚠️ Invalid DOI

Peer Effects, Teacher Incentives, and the Impact of Tracking: Evidence from a Randomized Evaluation in Kenya - Duflo, Esther; Dupas, Pascaline; Kremer, Michael (American Economic Review, 2011)
To the extent that students benefit from high-achieving peers, tracking will help strong students and hurt weak ones. However, all students may benefit if tracking allows teachers to better tailor their instruction level. Lower-achieving pupils are particularly likely to benefit from tracking when teachers have incentives to teach to the top of the distribution. We propose a simple model nesting these effects and test its implications in a randomized tracking experiment conducted with 121 primary schools in Kenya. While the direct effect of high-achieving peers is positive, tracking benefited lower-achieving pupils indirectly by allowing teachers to teach to their level. (JEL I21, J45, O15)
Keywords: Analysis of Education, Public Sector Labor Markets, Economic Development: Human Resources; Human Development; Income Distribution; Migration

Adoption of education technologies for learning during COVID-19 pandemic: The experiences of marginalized and vulnerable learner populations in Kenya - Ochieng, Vollan Okoth; Waithanji Ngware, Moses (International Journal of Educational Reform, 2022)
The onset of COVID-19 made governments and other education actors prioritize distance learning, particularly through education technologies (EdTechs). Most sub-Saharan African countries adopted and adapted this approach. This paper examines the extent of EdTechs’ deployment in Kenya during the COVID-19 pandemic among marginalized and vulnerable populations. A cross-sectional study design was adopted for the study from which this paper drew its data, with both secondary and primary data utilized. The findings show that marginalized/vulnerable learner populations are still left out on EdTech supported learning. This article proposes salient recommendations that could help advance inclusive education discussion and related EdTechs’ discourse.

Low-connectivity Educational Technology: A Case Study of Supporting Learning during Covid-19 via SMS with ‘Keep Kenya Learning’ - Jordan, Katy; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (Journal of Learning for Development, 2024)
The use of Short Messaging Service (SMS) for education has grown in recent years, drawing particular attention to supporting school-level learners, due to the Covid-19 pandemic. This renewed interest has prompted questions about how this form of educational technology could be used in the longer term. However, despite being used in many Covid-19 responses, there are few documented examples of innovative applications in this field during the pandemic, which represents a gap in the literature. As a medium for education, SMS offers potential benefits such as being cost-effective and having positive impacts on learning. In this paper, we present a case study of an educational programme rapidly implemented during the pandemic as part of the ‘Keep Kenya Learning’ program, to support learners remotely in terms of literacy, numeracy, and social and emotional learning topics. Through the case study, we describe the innovative process used to rapidly develop content for SMS, and draw upon usage statistics, quiz scores and user feedback to gain insights into its implementation with learners and caregivers in Kenya. The case study demonstrated that educational television content can be effectively adapted to mobile delivery. Furthermore, we present practical reflections on the development and implementation of SMS educational technology which will help inform future initiatives. These include considering timing in relation to school terms when planning a supporting intervention, and designing content in a modular way to allow flexibility for learners in navigating through courses.

Stakeholders’ perspectives of enablers and barriers to successfully implementing an integrated early childhood development program in an informal urban settlement in Kenya - Ssewanyana, Derrick; Martin, Marie-Claude; Angwenyi, Vibian; Kabue, Margaret; Proulx, Kerrie; Zhang, Linlin; Malti, Tina; Njoroge, Eunice; Nasambu, Carophine; Marangu, Joyce; Odhiambo, Rachel; Ombech, Eunice; et al. (SAGE Open, 2023)
Integrated early childhood development (ECD) programs boost child health and developmental outcomes. However, the factors contributing to the successful implementation of such programs in informal urban settlements are not well researched. We conducted 14 focus group discussions and 13 key informant interviews with 125 caregivers of children under the age of 5 years and stakeholders, exploring their views on enablers and barriers to implementing an integrated ECD program in an informal settlement in Kenya. Strategic engagement, capacity building, transparency, fair compensation of ECD workforce, communication skills, and the need to tailor ECD programs to local realities were discussed. An equity-focused implementation approach for integrated ECD programs is timely.

She called, she Googled, she knew: Girls' secondary education, interrupted school attendance, and educational use of mobile phones in Nairobi - Zelezny-Green, Ronda (Gender & Development, 2014)
Girls in Kenya commonly face multiple barriers to school attendance. At the same time, mobile phone use is growing throughout the country, and particularly in urban centres including Nairobi. As this technology spreads, the possibility increases of people using mobile phones for their own development purposes, including for education and learning. This article examines mobile phone use by girls at one secondary school in Nairobi, and in particular their attempts to mediate interrupted school attendance using this technology.
Keywords: ICT4D; Kenya; gender; girls' education; international education and development; mobile learning; school attendance; ⛔ No INSPIRE recid found

Relationship between Teacher - Educator Characteristics and the Integration of Information and Communication Technologies in Teaching and Learning in Teacher Education Institutions in Kenya - Chemwei, B.; Kiboss, J.; Njag, Kageni (undefined, 2016)
It is a government policy that all institutions of learning in Kenya, across the curricula embrace Information Communication Technology (ICT) as the world moves towards knowledge based economy. The evidence in literature reveals positive effects of information and communication technology in instruction. But teachers have a challenging task in integrating the tools of ICT in teaching especially those teacher educators not quite exposed to technology. This is because so many factors influence ICT integration. In this paper, we explore the the relationship between teacher-educators’ age, gender, level of education, and teaching experience and the integration level of ICTs in teaching in primary teacher training colleges in Kenya. The simple random sampling technique was used to select six teacher training colleges in Kenya and 169 respondents who participated in the study. Data was collected using a questionnaire, an interview schedule and an observation schedule. The data collected was analyzed descriptively with the help of SPSS program version 17.0 for frequencies, means, standard deviation and percentages. The inferential statistics used to determine relationships among variables was the Pearson moment Correlation. Regression analysis was used to determine the best predictors of ICT integration among the independent variables. A p-value of less than 0.05 was interpreted as significant. Results indicated that there is a significant relationship between teacher-educators’ level of ICT integration in teaching and their age. However, the findings showed no relationships between teacher educators’ level of ICT integration in teaching and gender as well as their level of education. Teacher-educators’ years of teaching are insignificant in explaining teachereducators’ integration ICT in teaching. Based on the findings, we recommended that information and communication integration be made part of undergraduate training in universities in order to equip future teacher educators with ICT skills; planning for the implementation of ICT integration into teaching in teachers’ training programmes early would increase the pre-service teachers’ expertise and lead to an increase in the level of ICT integration during the earlier years of their careers. There is also need to hire young teacher-educators to the field, especially female teachers. This would also increase the representation of the female perspective toward the improvement of the level of ICT integration into teaching.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Lower Primary Levels Curriculum Designs, Volume 1: Kiswahili, Literacy and Indigenous Languages and English Activities - Kenya Institute of Curriculum Development (Kenya Institute of Curriculum Development, 2017)

Integrating ICT into Teaching and Learning Biology: A Case for Rachuonyo South Sub-County, Kenya - Mwanda, Gideon; Mwanda, Samwel; Midigo, Ronnie; Maundu, John (American Journal of Education and Information Technologies, 2017)
The purpose of this study was to find out the extent of integration of computer technology into teaching and learning Biology in secondary schools of Rachuonyo South Sub-County, Kenya. The target population consisted of students and biology teachers in the Sub-County. Data was collected by use of questionnaires and an observation check list. From the study, most schools had few computers; teachers had inadequate training on use of computer applications; most teachers did not use computer technology for personal growth and instructional purposes. Inadequate number of computers in the sampled schools was the major challenge facing the integration of computer technology into the instruction process. The study recommends increased accessibility of computers, adequate training on use of computer technology and development of a policy framework to guide on the path to effective computer integration into instruction process.
Keywords: ⚠️ Invalid DOI

Computer Laptop Project Strategy for Basic Education Schools in Kenya - Wambugu, Geoffrey M.; Ogenga, Stephen; Shikali, Casper; Muliaro, Joseph (2017)
Kenya’s Vision 2030 recognizes the enabling role of Information and Communication Technology (ICT) and anchors some of its key aspirations upon the availability and adoption of computers for schools. The overall objective of this strategy paper is to provide direction for acquisition of equitable and efficient laptop computers to all pupils in public primary schools. The existing education policy on ICT is imbedded in three documents namely; e-Government Strategy, National ICT Policy and Sessional Paper No. 1 of 2005 which is a Policy Framework for Education, Training and Research. There is a need therefore to consolidate these documents into one. The overall objective of the consolidation is to merge and integrate education policy on ICT including the scope, usage, administration and ways to address innovations and attendant Intellectual Property Rights. In the process of strategic planning for utilizing ICT in education, key stakeholders require to be consulted. In addition to the above mentioned, specific stakeholders include the National ICT integration and innovation Centre, Kenya Institute for Curriculum Development, Center for Mathematics, Science and Education in Africa, Teacher Service Commission, Primary Teacher Training Institutions, Universities and the National ICT Steering Committee. The strategy identifies the following as key weaknesses that hamper the implementation of ICT projects: slow integration of ICT in operations and programs; inadequate human and financial resources in some key service areas to meet the rapidly growing work-related demands. In addition there exists lack of appropriate learning facilities and/or infrastructure in some education and training institutions and inadequate number of trainers in modern technology coupled with a mismatch of skills learnt and demands of the labour market. It is also noted that the legal framework is non-harmonized and this inhibits the performance of Ministry of Education, Science and Technology. Further, a number of policy frameworks are yet to be operationalized thus hampering delivery of services. The strategy also identifies a Strategic Model for Laptop Project and an implementation matrix.
Keywords: ⛔ No DOI found

Implementing mother tongue instruction in the real world: Results from a medium-scale randomized controlled trial in Kenya - Piper, Benjamin; Zuilkowski, Stephanie S.; Ong’ele, Salome (Comparative Education Review, 2016)
Research in sub-Saharan Africa investigating the effect of mother tongue (MT) literacy instruction at medium scale is limited. A randomized controlled trial of MT literacy instruction was implemented in 2013 and 2014 as part of the Primary Math and Reading (PRIMR) Initiative in Kenya. We compare the effect of two treatment groups—the base PRIMR program teaching literacy in English and Kiswahili and the PRIMR-MT program, which taught literacy in English, Kiswahili, and mother tongue—in two different language environments. Implementation of the MT program faced challenges because many educators were not speakers of the languages, some communities resisted mother tongue instruction, and some areas were more language heterogeneous. Effect sizes on MT literacy averaged between 0.3 and 0.6 standard deviations. The base PRIMR program also increased MT learning outcomes in some measures but had smaller effects than the PRIMR-MT program in oral reading fluency and comprehension.

Teachers' professional development in a challenging educational context -- a study of actual practice in rural western Kenya - Onguko, Brown (University of Calgary, 2012)
This research adopted a design research approach, utilizing a mixture of methods including narratives, ethnographic observations, qualitative interviews and documentation of design artifacts. It was implemented in a challenging context in Western Kenya. The first research question for this study was: How might professional development (PD), offered through a blended learning approach and delivered by appropriate technologies, inform potential change to teaching practice in a challenging context in Kenya? Research question two sought to understand the implications of the professional development implemented in this study for teachers and professional development teachers (PDTs). Question three sought to understand the sustainability and scalability of the professional development approach The theoretical framework informing this research is based on activity theory- a needs-driven and goal directed process through tool mediation, and entails division of labor and isolation of partial tasks in a community of relationships (Vygotsky, 1978; Leont’ev, 1978; Engestrom, 1987; 1999; 2000; 2008). Key features of activity theory are active engagement and social interaction, which enabled teachers to collaboratively work with each other, studying through appropriate technologies to inform their teaching practices. Based on a review of literature, interviews with teachers and observation of teachers during face-to-face meetings in professional development and in their classroom practice, this study suggests that teachers in a challenging context can inform potential change to their teaching as a result of participation in locally developed content, delivered through blended learning on appropriate technologies. This study observes that through self-directed study on tablets, and occasional face-to-face interaction, teachers can transform into a community of learners that support each other in planning for their lessons. Content development involving local experts is critical to such interventions in challenging contexts, while drawing from global web content, harnessing open educational resources and being sensitive to local culture. Reflective conversations, professional dialogues and technology stewardship were all critical in informing teachers’ practice.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2457443; __finaldtb; ⛔ No DOI found

Pro-Poor PRIMR: Improving Early Literacy Skills for Children from Low-Income Families in Kenya - Piper, Benjamin; Jepkemei, Evelyn; Kibukho, Kennedy (Africa Education Review, 2015)
Children from low-income families are at risk of learning outcome difficulties, particularly in literacy. Various studies link poor literacy results with performance later in primary and secondary school, and suggest that poverty, literacy skills and weak instructional methods combine to drastically limit the educational opportunities for many poor children. The Primary Math and Reading (PRIMR) Initiative was designed to support the learning gains of Class 1 and 2 pupils in seven counties across Kenya. PRIMR uses a randomised controlled trial design to establish the effect of its intervention and employs basic literacy measures to estimate causal effects. This study shows that PRIMR has been effective for children from low-income families and that early literacy interventions can mitigate socio-economic effects. The findings suggest that efforts to improve literacy outcomes for the poor should begin early in primary school. Strategies for ensuring that instruction is equitable across socio-economic status are advocated.
Keywords: Achievement Gains; Causal Models; Control Groups; Early Intervention; Early Reading; Educational Improvement; Effect Size; Emergent Literacy; Experimental Groups; Foreign Countries; Grade 1; Grade 2; Low Income Students; Oral Reading; Poverty; Randomized Controlled Trials; Reading Comprehension; Reading Fluency; Reading Tests; Regression (Statistics); School Effectiveness; Skill Development; Socioeconomic Status

Availability of Resource Materials and Facilities for ICT Integration in the Public Primary School Curriculum in Kitui County, Kenya - Mwendwa, Nzwili K. (2017)
Throughout the world, the Information and Communications Technology (ICT) is changing the face of education. This paper is a report of a study that was carried out in the months of May and June 2016 on the availability of resources and facilities for ICT integration in the public primary school curriculum in Kitui County in Kenya. The research purpose and objective of the study was: To find out the availability of resources and facilities for ICT integration in the public primary school curriculum in Kitui County. This study was guided by the Technology Acceptance Model (TAM). It was informed by the pragmatic philosophy and the Mixed Method (MM) research approach. Data was collected from 388 public primary schools in Kitui County selected through stratified and simple random sampling methods. A total of 388 head teachers and 776 teachers participated in the study giving a total of 1114 respondents. The research instruments used were questionnaires for teachers, interview schedules for head teachers and observation checklists. The data collected was analyzed qualitatively and quantitatively. The findings revealed that most of the schools were connected to electricity but lacked ICT resources such as desk computers, whiteboards, CD-ROMs and anti-viruses. Laptops were available in some of the schools but were not being used by teachers in direct instruction. They were mainly used in the storage of school records, teacher plans, examination questions and for examination registration exercises. Another finding was lack of internet connectivity in most of the schools that affected ICT integration in the curriculum. The study recommended that the education stakeholders and the government should partner in provision of ICT resources and facilities to facilitate integration of ICT in schools. It is hoped that this study will be useful in education policy making on ICT integration in schools in Kenya and other parts of the world.
Keywords: ⛔ No DOI found

Supporting equitable access to learning via SMS in Kenya: Impact on engagement and learning outcomes - Jordan, Katy; Myers, Christina; Damani, Kalifa; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (British Journal of Educational Technology, 2024)
Abstract The use of SMS messaging for education has grown in recent years, with particular attention recently during the Covid‐19 pandemic. Mobile phones often have high levels of ownership in low‐income contexts compared to computers, and lower connectivity requirements, which arguably make this a more equitable medium than data‐heavy online instruction, for example. However, given that gender can be a factor to influence mobile device access and use, it is also important to consider educational applications through a gender lens, to avoid further exacerbating digital divides. In this paper, we present an analysis of server log and evaluation data in relation to a literacy‐focused initiative for primary‐aged learners carried out in Kenya as part of the Tusome programme and through the SMS‐based M‐Shule education platform, which does not require an Internet connection or smartphone to run. The extent of engagement with the platform varies according to gender and location within the country. The data also demonstrate a positive impact on learning outcomes regardless of learners' gender and location. Furthermore, the learning gains are shown to be relatively cost‐effective in comparison with educational technology interventions in similar contexts. The findings show that this low‐connectivity adaptive model has a positive impact on learning outcomes. It is a scalable approach to support a range of learners in Kenya, providing more support to learners who need it, and leading to increased foundational learning outcomes overall. As such, the findings will also be of highly relevant to other low‐connectivity contexts. Practitioner notes What is already known about this topic Mobile phones can be used as a means to support learning, through mobile learning and SMS, particularly in low‐connectivity contexts, although there is a lack of rigorous evidence of impact upon learning outcomes. Mobile phone device ownership tends to be higher than computer or wired Internet connections in many low‐income contexts. Software applications which adapt to the learners' level have shown good potential for gender‐equitable learning outcomes in low‐income contexts; however, these often require an Internet connection in addition to computers or tablets to be run on. What this paper adds There is a lack of contextually relevant evidence of the impact of SMS‐based mobile learning applications in low‐resource and low‐connectivity contexts upon learning outcomes. Through analysis of data generated via an experimental design, this study provides evidence that literacy materials delivered through an SMS‐based educational platform—M‐Shule—can have a positive impact upon learning outcomes. Furthermore, gains are equitable in terms of learners' gender, and location, within Kenya. Implications for practice and/or policy Mobile phones can be an effective way of reaching learners to provide additional educational support as part of existing education programmes in low‐connectivity environments. Learning gains using M‐Shule are evidenced as significant and relatively cost‐effective. Existing high‐quality learning materials developed in other media can be effectively adapted to SMS to reach learners particularly who are out‐of‐school or during periods of educational disruption.

Role of ICT in Enabling High Quality OERs for Teacher Education and Training in Dadaab Refugee Settlement in Kenya - Ndalo, Agumba Musa (Research Journal of Education, 2016)
ICT and OER have the potential for uplifting the quality of refugee education across the world. Sustainable education in refugee camps/settlements is difficult to achieve in many countries that host refugees. This is because most international agencies that come to aid of the refugees are mostly concerned with basic humanitarian assistance like health, food and shelter. Quality education is a key determinant of students’ participation rates and achievement levels. It also remains an important ingredient towards attainment of social justice in terms of equity in educational quality for students. One contributing factor to quality education is availability of ICT infrastructure and quality OERs to create equity for many refugee learners in their camps. This paper describes how ICT and OER initiatives are appropriate tools for improving access, equity, and quality training and education of refugees in Dadaab refugee settlement schools in north eastern part of Kenya.
Keywords: Google Scholar/ "refugee education" ICT; RER theme_supporting educators; ⛔ No DOI found

LEAP From Pilot to Scale: Embedding Digital Reading within the Kenya National Library Service - Heavner, Rachel; Lowe, Zev; Mwachi-Amolo, Joan (2017)
Mobile technologies have become more normalized for data collection, education for displaced communities and interventions at a distance. Yet, questions remain around how to effectively bring these technology interventions from pilot efforts to broad scale adoption. Worldreader is demonstrating operational success in its digital reading programs in Kenya. In 2014, Worldreader, in partnership with the Kenyan National Library Service (knls), launched its digital reading program, called LEAP (Libraries E-reading Activities Partnership) in eight libraries. By December 2017, LEAP had successfully scaled to all 61 public libraries in the country. This paper outlines five key insights for moving from pilot to country-level scale: 1. Start slow, start smart 2. Leverage economies of scale 3. Step by step: Implement in phases 4. Manage change: Creating a unified vision of success 5. Implement sustainability from the start. These learnings can inform others leveraging technology to improve education around the world and contribute to strengthening an effective, responsible and efficient ecosystem of technology-enriched educational programs.
Keywords: ⛔ No DOI found

Does private schooling narrow wealth inequalities in learning outcomes? Evidence from East Africa - Alcott, Benjamin; Rose, Pauline (Oxford Review of Education, 2016)
In many low- and lower-middle-income countries, private schools are often considered to offer better quality of education than government schools. Yet, there is a lack of evidence to date on their role in reducing inequalities: namely, the extent to which private schooling improves learning among the most disadvantaged children. Our paper uses household survey data from Kenya, Tanzania, and Uganda to identify whether any observed impact of private schooling on core literacy and numeracy skills differs according to children’s household wealth. We demonstrate wealth gaps in access to private schooling, and use inferential models to account for observable differences between those who do and do not enrol in private schools. In Kenya and Uganda, we find that private schooling appears to improve the chances of children learning relative to their peers in government schools, but the chances of the poorest children learning in private schools remains low and is at best equivalent to the richest learning in government schools. In Tanzania, private schooling does not seem to improve poorer children’s learning, whereas it does for richer children. These findings raise a caution about the extent to which private provision can help narrow learning inequalities.
Keywords: CitedIn:OER4Schools-HHH3-B; CitedIn:PhD_Thesis; East Africa; Kenya; Learning outcomes; Tanzania; Uganda; education policy; inequality; private schooling

Perspectives on underutilisation of ICT in education in Tanzania, Uganda and Kenya - Oroma, J. O.; Kiden, S.; Maghendha, M. W.; Ntiyani, S. (2013 IST-Africa Conference, 2013)
Developing countries in Africa have experienced considerably high growth in education that is witnessed by high enrolments at all levels, and brought forth several critical challenges like limited learning space, insufficient learning materials, and inadequate human capacity, forcing governments to build more schools and encourage the private sector to invest in education at all levels because education is pivotal to growth in other sectors. To overcome these challenges and improve the quality of education, these governments enacted several policies that integrate information and communication technologies in the curriculums at all levels of education and encouraged institutions to embrace these technologies because they enhance the teaching and learning processes. However, in reality, the adoption, ICT integration and implementation of these policies is inadequate and hindered by numerous factors. This study therefore focuses on exploring and comparing these factors leading to the underuse of ICT in education in these three countries.
Keywords: Africa; Computers; East Africa; Educational institutions; Government; ICT; ICT integration; ICT underutilisation; Internet; Kenya; Libraries; Materials; Tanzania; Uganda; Uganda and Kenya; challenges; computer aided instruction; context; countries; developing; developing countries; e-learning. Tanzania; education; education quality; educational institutions; excuses; human capacity; information and communication technologies; learning materials; learning process; learning space; private sector; teaching; teaching process; utilisation; ⛔ No DOI found

Internet Utilization: A Case of Connected Rural and Urban Secondary Schools in Kenya - Kiptalam, George Kibet; Rodrigues, Anthony Joachim (2013)
This paper looks at the utilization of the Internet among teachers and students in connected rural and urban secondary schools in Kenya. A conceptual framework composed of variables which can explain Internet utilization in Kenyan secondary schools is established and measured. Instruments based on this framework were used in the survey and covered 11 schools with school principals, teachers and students as respondents. Findings show that use of the Internet and its integration in teaching and learning in secondary education is increasing with its use more pervasive among students and teachers as a means of communication and for information searching. Internet access rates for teachers and students have been observed to be much higher in educational institutions that have made effective ICT investments in education, translating into better utilization of ICT related technologies. Strategies are suggested on how to utilize the Internet to improve educational outcomes, and recommendations given on issues that touch on ICT access and infrastructure; human resources and training; policy environment; financing and ICT investment; curriculum development and locally relevant content
Keywords: ⛔ No DOI found

An Evaluation of the Implementation of Information Technology in Secondary Schools in Kenya - Mbogo, Gracemary; Anne, Onunga; Kirathi, Miriam (Mediterranean Journal of Social Sciences, 2014)
Education is the best legacy a nation can give to her citizens especially the youth. This is because the development of any nation depends on the quality of education of such a nation. While ICT continues to advance in western Asia countries, African countries still experience a lag in its implementation and continues to widen the digital and knowledge divides. In a recent study by Kiptalam et .al (2010), observed that access to ICT facilities is against the ratio of 1:15 students in developed countries. This study was carried out to investigate the extent to which Information Technology has been implemented in secondary schools in Kenya. 30 teachers were sampled out from various counties. A questionnaire was administered to the sample. Descriptive statistics were used to analyze the data. The fidings indicated that most teachers appreciated the need to implement ICT in schools to enhance their effectiveness during the instructional processes. However, most of the teachers had limited ICT skills and rarely used ICT during their teaching. DOI: 10.5901/mjss.2014.v5n5p215

An Investigation into Implementation of ICT in Primary Schools, in Kenya, in the Light of Free Laptops at Primary One A Case Study of Teachers Implementing ICT into Their Teaching Practice - Tonui, Betty; Kerich, E; Koross, R (Journal of Education and Practice, 2016)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley region of Kenya. It examines views in pertinent literature as well as teachers’ perceptions of the benefits of integrating ICT into teaching-learning, the success factors and obstacles encountered in their endeavours to do this. Conclusions are drawn and suggestions made to address the challenges and improve on the use of ICT for teaching-learning in teaching institutions.
Keywords: ⛔ No DOI found

Learners and caregivers barriers and attitudes to SMS-based mobile learning in Kenya - Jordan, Katy; Damani, Kalifa; Myers, Christina; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (African Educational Research Journal, 2023)
The use of mobile phones has been identified as a potential way to bring the benefits of educational technology to a wider audience, including in low-connectivity settings. This is a topic that has received renewed interest recently as a result of the COVID-19 pandemic and school closures. While a number of recent studies have demonstrated good potential for mobile phones and SMS to be used to support learning, there are also questions about how equitable this medium is in practice. We conducted a telephone survey with learners (n = 122) and their caregivers (n = 124) who use M-Shule, an SMS-based educational platform in Kenya, in order to understand their attitudes towards mobile learning, and the benefits and constraints. In particular, we consider whether there are differences in responses according to gender and/or location, to shed light on whether use is equitable. We find that girls and boys face similar barriers to use, and the technology is perceived to be equally beneficial. We identify some areas for potential further support for all learners through mobile learning.

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge (European Scientific Journal, ESJ, 2013)
Studies conducted in the field of ICT use in secondary schools reveal that, although in the past few years teachers and students have enjoyed adequate access to an assortment of ICTs such as computers, laptops, projectors printers, e-blackboards, mobile phones for use n integration of teaching and learning in schools, the level of utilization of the ICTs by teachers and students in Kitui District is still minimal. This study sought to examine the relationship between Principals, teachers’ and students’ attitude on utilization of ICTs and the readiness to adopt e-learning in curriculum implementation at secondary school level. The major objective of the study was to establish the extent to which the attitude of principals, teachers and students influence readiness to adopt e-learning in secondary schools in Kitui District. Cross–sectional survey research design was adopted for the study. A sample of 66 principals, 66 teachers and 347 students, were involved in the study. The multiphase sampling procedure was adopted for this study. Data were collected using questionnaires and an observation schedule. The resultant information was analyzed by employing the quantitative approach which involved descriptive and inferential statistical procedures. The findings of the study reveal that the attitude held by secondary school Principals and Teachers had no significant influence on the schools’ readiness to adopt e-learning. However, the attitude held by students had a significant influence on the schools’ readiness to adopt e-learning. The study recommends that the government should plan to address the issue of e-learning infrastructure by availing e-learning equipment, enhancing connection to reliable sources of power, improving connectivity to various internet services and augmenting Human Resource ﻿capacity by organizing training programmes for Principals, Teachers and Students. Secondary schools should employ support staff members such as computer laboratory technicians or assistants before embarking on full-scale implementation of e-learning in schools in Kitui District and, indeed, all other remote semi-arid districts in Kenya. This will enhance positive attitude and confidence that e-learning can be successfully adopted in secondary schools in Kenya regardless of the location of the school.
Keywords: ___working_potential_duplicate; ⚠️ Invalid DOI

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge (European Scientific Journal, ESJ, 2013)
Studies conducted in the field of ICT use in secondary schools reveal that, although in the past few years teachers and students have enjoyed adequate access to an assortment of ICTs such as computers, laptops, projectors printers, e-blackboards, mobile phones for use n integration of teaching and learning in schools, the level of utilization of the ICTs by teachers and students in Kitui District is still minimal. This study sought to examine the relationship between Principals, teachers’ and students’ attitude on utilization of ICTs and the readiness to adopt e-learning in curriculum implementation at secondary school level. The major objective of the study was to establish the extent to which the attitude of principals, teachers and students influence readiness to adopt e-learning in secondary schools in Kitui District. Cross–sectional survey research design was adopted for the study. A sample of 66 principals, 66 teachers and 347 students, were involved in the study. The multiphase sampling procedure was adopted for this study. Data were collected using questionnaires and an observation schedule. The resultant information was analyzed by employing the quantitative approach which involved descriptive and inferential statistical procedures. The findings of the study reveal that the attitude held by secondary school Principals and Teachers had no significant influence on the schools’ readiness to adopt e-learning. However, the attitude held by students had a significant influence on the schools’ readiness to adopt e-learning. The study recommends that the government should plan to address the issue of e-learning infrastructure by availing e-learning equipment, enhancing connection to reliable sources of power, improving connectivity to various internet services and augmenting Human Resource ﻿capacity by organizing training programmes for Principals, Teachers and Students. Secondary schools should employ support staff members such as computer laboratory technicians or assistants before embarking on full-scale implementation of e-learning in schools in Kitui District and, indeed, all other remote semi-arid districts in Kenya. This will enhance positive attitude and confidence that e-learning can be successfully adopted in secondary schools in Kenya regardless of the location of the school.
Keywords: ___working_potential_duplicate; ⚠️ Invalid DOI

Distance learning during COVID-19 crisis: Primary and secondary school parents experiences in Kenya - Mabeya, Mary Theodorah (East African Journal of Education Studies, 2020)
The COVID-19 disease outbreak in 2020 was declared by the World Health Organization as a Public Health Emergency (PHEIC). Human symptoms of the Coronaviruses among others are commonly spread through droplets (coughing) and close personal unprotected contact with an infected person through toughing. Based on the speed at which the disease spreads, learning institutions were distinguished as high-risk areas with prospective of exposing both learners and instructors the spreading the virus. This had a serious effect on the academic programs in all learning institutions worldwide where learning was abruptly discontinued and all students and instructors send home. The Government of Kenya (GOK) through the President’s directives suspended all learning institutions as one of the measures taken by the Ministry of Health to mitigate the spread of COVID-19. This affected the learning since most of the schools had not even started their syllabus that academic year. Alternative measures to ensure that curriculum implementation progressed well; various mechanisms were suggested including remote learning which was actualised in some instances. Virtual lessons and Open and Distance e-learning (ODeL) has mainly been adopted by institutions of higher learning (colleges and universities) globally in offering online classes. However, this was not the case in many public primary and secondary institutions where the common form of learning involves a very interactive physical relationship between teachers and their learners in classrooms. In Kenya, since all institutions of learning were closed as a result of the breakout of the COVID-19 pandemic, the Ministry of Education (MOE) opted for remote learning across the country. Research results from Rangwe Sub-county have shown that most learners have not benefited much from the online classes due to the network and other related challenges reported in this paper. This has created education inequity since parents who have children in private schools and those from well of backgrounds are the ones enjoying distance learning programmes offered. The research has also found out that parents did no proper supervision to ensure that their children were committed in their studies in remote settings. Lack of supportive infrastructure (electricity and internet network access) limited children participation in distance learning programmes in Rangwe Sub-county. The paper recommends that government to properly educate parents, teachers and learners on modalities of distance and remote learning programmes. There is need for government to provide children from disadvantaged families with technological appliances to enable them to participate in distance education.

Teachers’ Perception About Integration of ICT in Teaching and Learning of Kiswahili Language in Secondary Schools in Kenya. - Miima, Florence; Ondigi, Dr Samson; Mavisi, Rose (2013)
This article discusses the results of exploratory study of integration of ICT in teaching and learning of Kiswahili language in Kenyan secondary schools taking the case of Kakamega county in western part of Kenya. A survey design technique was adopted. Forty five teachers were selected to act as sample size for the study. Questionnaires and interview protocols were used to collect the data. The data collected was analyzed through descriptive statistical techniques. The results are summarized and presented through tables and graphs. The findings established that most Kiswahili teachers understand the benefit of integrating ICT in teaching and learning of Kiswahili language but they are not willing to adopt it due to various challenges. The paper examines how Kiswahili language teachers integrate ICT into everyday classroom practice, their perceptions, constrains, and their reservations. It also considers use of ICT along with the influences of established curriculum practice and policy upon Kiswahili language teacher’s willingness to develop new forms of activity and pedagogy. The case study provides some information on integration of ICT at all level of language teaching and learning in education.

Evaluation of the application of mobile phone technology in teaching and learning: A case study of Kamwenja Teacher' college, Nyeri County, Kenya. - Gitome, Mwangi Joseph (Mount Kenya University, 2015)
This research was designed to investigate the application of mobile phone technology in teaching and learning among tutors and students of Kamwenja Teachers College in Nyeri County in Kenya. The problem this study addressed was to establish whether mobile phones in the hands of students and tutors were beneficial for teaching and learning or if they impede learning process in Teacher Training Colleges in Kenya. The variables under consideration were: quality teaching and learning as dependent variable and owning mobile phones, awareness of educational potential of mobile phones, acceptance of mobile phones, and mobile phones influence as alternative learning and instructional methods as independent variables. The data was collected from 71 tutors and 498 students. The sample size was worked out at 20% to be 15 tutors and 100 second year teacher trainees in the college. Stratified random sampling was used to ensure the sample was a true representation of the whole population. Data was collected through questionnaires that were both quantitative and qualitative to ensure high quality of information for the study where 98.2% response rate was achieved. To ensure Validity and Reliability of Research Instruments a pre-test of the questionnaire was conducted on tutors and students of Kagumo Teachers College. A reliability coefficient of 0.7 was adopted for the items while an expert, the supervisor, guided in validity of the items. The study was guided by the activity theory also known as Cultural Historical Activity Theory. Primary data was analysed with the aid of Statistical Package for Social Sciences (SPSS version 20) software to generate descriptive statistics, correlation and multiple regression analysis. The findings of the study revealed that ownership of mobile phone had a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly and even when regressed together with other factors. Further, the study revealed that awareness of the educational potential of mobile phone technology, acceptance of mobile phone technology and mobile phone technology as an alternative learning and instructional methods were found to have a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly, however when all the factors were regressed together they were found to have a positive and but insignificant effect on application of mobile phone technology in teaching and learning. In order to enhance use of mobile phone technology in teaching and learning students and teachers should be encouraged to acquire mobile phones with internet connectivity features. The general usage of mobile phone in teachers training colleges was found to be very high. However the rate at which mobile phones are used for exchanging learning information is low. The researcher recommends that policies be put in place on use of mobile phone technology in teaching and learning and train tutors on how to teach differently using mobile phone technology. Future researchers should try to establish hindrances of application of mobile phone technology in teaching and learning.

A Cautionary Tale of Tutoring Hard-to-Reach Students in Kenya - Schueler, Beth E.; Rodriguez-Segura, Daniel (EdWorkingPaper, 2021)
Covid-19-induced school closures generated great interest in tutoring as a strategy to make up for lost learning time. Tutoring is backed by a rigorous body of research, but it is unclear whether it can be delivered effectively remotely. We study the effect of teacher-student phone call interventions in Kenya when schools were closed. Schools (n=105) were randomly assigned for their 3rd, 5th and 6th graders (n=8,319) to receive one of two versions of a 7-week weekly mathfocused intervention—5-minute accountability checks or 15-minute mini-tutoring sessions—or to the control group. Although calls increased student perceptions that teachers cared, accountability checks had no effect on math performance up to four months after the intervention and tutoring decreased math achievement among students who returned to their schools after reopening. This was, in part, because the relatively low-achieving students most likely to benefit from calls were least likely to return and take in-person assessments. Tutoring substituted away from more productive uses of time, at least among returning students. Neither intervention affected enrollment. Tutoring remains a valuable tool but to avoid unintended consequences, careful attention should be paid to aligning tutoring interventions with best practices and targeting interventions to those who will benefit most.

The potential and prerequisites of effective tablet integration in rural Kenya - Heinrich, Carolyn J.; Darling-Aduana, Jennifer; Martin, Caroline (British Journal of Educational Technology, 2020)
This study investigates how pedagogical, cultural and institutional factors interact with technical knowledge in educational technology integration and how they relate to equitable and effective technology use in low-resource settings. In the context of a one-to-one tablet initiative in rural Kenya, we explore how these factors constrain or support access to technology, instructor capacity, student engagement and student learning, as well as their implications for reducing educational and digital divides. We employ a mixed methods, such as a quasi-experimental (prepost, nonequivalent control group) research design that draws on data from classroom observations, teacher interviews, student surveys and focus groups, and assessments of student academic performance to generate evidence on classroom practices and student learning in schools with access to tablets, while also highlighting core challenges to successful technology integration. Our findings contribute to the identification of prerequisites and supporting factors for successful educational technology integration, as well as policy levers and school-based strategies that are likely to increase equitable access to quality learning experiences in schools in low-resource contexts. Practitioner Notes What is already known about this topic A lack of funding, planning and infrastructure hinder information and communication technology (ICT) integration. Procurement of educational technology and infrastructure improvement efforts has reduced digital divides, but learning divides persist in implementation. Insufficient teacher technology expertise and professional development constrain teacher's effective use of educational technology in classrooms. What this paper adds We employ mixed methods—triangulating the student assessment data with data from student surveys and focus groups, teacher interviews and classroom observations—to identify how pedagogical, cultural and institutional factors interact with technical knowledge in ICT integration in ways that support or constrain student learning in low-resource contexts. We find that more attention is needed for cultural factors that interact with pedagogical and technical skills to ensure that the classroom instructors' attention is equitability distributed in ways that discourage in-class “tracking” and differential access to quality learning experiences, such as some teachers' disregard of “slow learners” in the classroom. In low-resource contexts, providing even basic levels of infrastructure (eg, a consistent power source) and access to general technical knowledge requires more creative and concerted efforts from school leadership and instructors, such as the offer of tutorials and reading clubs outside of the class to expand access and improve the use of devices. Implications for practice and/or policy We find that device sharing can have positive effects on peer-to-peer learning, which suggests that policymakers in Kenya should weigh the benefits of achieving one-to-one device access against the potential advantages of alternative investments, such as expanding professional development on the integration and use of currently available devices. Increasing opportunities for peer-to-peer learning and exchange (among teachers and students) and building shared capacities for ICT integration can help reduce technical issues and lost instructional time.

Leadership Roles in Managing Education in Crises: The Case of Kenya During Covid-19 Pandemic - Mbogo, Rosemary Wahu (2020)
Covid-19, a disease caused by a novel coronavirus (SARS-CoV-2) was first reported in Wuhan, China, in December 2019 and in Kenya in March 2020. In Kenya, the Covid-19 pandemic has brought to light some unknown talents among the stakeholders at different levels. The economic sector has had manufacturing potential for goods, and from mass media reports, this has been demonstrated through production of Personal Protective Equipment (PPEs), ventilators and innovations in technology in the creation of apps such as the Linda App for contact tracing and Gumzo, a video conferencing app. Similarly, the education sector has also demonstrated potential for adaptation in some situations. For example, after all institutions of learning were closed to prevent the spread of coronavirus in March 2020, many universities have continued learning through Online, Distance and E-learning (ODEL) platforms, and some have even conducted virtual graduations. Others like Kenyatta University have reported innovations such as development of ventilators and modified testing swabs for Covid-19. This is admirable despite numerous limitations of internet accessibilities and other shortcomings. This remarkable achievement has been possible due to semi-autonomy in the university education sector, where Senates are given the right and power, by the Education Act, to make autonomous decisions for their universities which are regulated and monitored using the standards and regulations set by the Commission of University Education (CUE). However, other levels of the education sector do not have this autonomy and have had to depend on the ministry of education for guidance. On 8th July 2020, the ministry of education announced the result of a consultative meeting with stakeholders, to postpone the reopening of schools to January 2021. This was due to the rising cases of corona virus infections in May and June, steeping the infection curve, expected to reach the peak by November and to have flattened by January 2021 (Magoha, 2020). However, what surprised many was the additional and unforeseen announcement that all basic education students (apart from standard 8 and form 4 examination candidates whose details were not clarified) will repeat their current class levels in 2021. The pronouncement caused anxiety and has attracted mixed reactions from various stakeholders. The purpose of this paper is therefore to explain the leadership decisions made by the ministry of education analyze their impact on basic education and propose possible ways for educational leaders and administrators, community leaders and volunteers to facilitate home-based education during the Covid-19 pandemic. This should be done with a goal for progression and promotion of students to the next class level when the 2020 syllabus is eventually covered. The study method utilized desktop literature research where interactions with educational leaders, scholars and practitioners were used to investigate threats and opportunities in managing education during crises.  Article visualizations

Parent and implementer attitudes on gender-equal caregiving in theory and practice: Perspectives on the impact of a community-led parenting empowerment program in rural Kenya and Zambia - Okelo, Kenneth; Onyango, Silas; Murdock, Dawn; Cordingley, Kaylie; Munsongo, Kelvin; Nyamor, George; Kitsao-Wekulo, Patricia (BMC Psychology, 2022)
Fathers are often perceived to be mainly responsible for the provision of the family's economic needs. However, past studies have demonstrated that fathers’ involvement in parenting has great significance for the child’s holistic growth and development. Few studies have investigated fathers’ roles in the nurturing care of young children, particularly responsive care and stimulation, in sub-Saharan Africa. The study reported here was carried out as part of a larger study that sought to evaluate the effectiveness of the Moments That Matter (MTM) program in improving the nurturing care of young children in rural communities in Zambia and Kenya. The MTM program uses a parenting empowerment approach to promote bonding and interactions between caregivers and their children within the home, focusing on responsive care, early learning, and security and safety so that children reach their full developmental potential. Trained volunteers facilitated monthly primary caregiver support and learning groups and ECD home visits. Fathers were encouraged to participate in the home visits and to attend some of the group meetings on specific topics. The study reported in this paper aimed to establish the impact of the parenting empowerment program in promoting more gender-equal attitudes and practices on parenting among fathers (who were not the primary caregivers).
Keywords: And holistic development; Childcare; Early childhood development; Early learning; Fathers’ perceptions; Fathers’ practices; Fathers’ roles; Parenting; Responsive care; Stimulation

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, Eunice; Role, Jesse (2013)
The purpose of conducting this study was to determine the perception that students and teachers held on the utilisation of educational media in teaching and learning of History and Government subject in public secondary schools in Nandi Central Sub County, Kenya. The study involved participation of 10 secondary schools from the area. The target population for the study involved 48 teachers and 257 form IV students. The data for the research was collected through questionnaires. Research results showed that majority of student rated that educational media was very helpful in learning History and Government. Teachers had more positive perceptions towards the integration of educational media in teaching and learning of History and Government in secondary schools in Nandi Central Sub-County. There was a significant difference on the teachers perception and students perception on the use of educational media in teaching and learning History and Government in secondary schools (p<0.05). The study concluded that teachers and students perceived differently on the effect of utilisation of educational media in teaching and learning History and Government subject in secondary schools in Nandi Central. The study recommends that teachers should go for in-service training to be acquainted with new educational media resources. Teachers should also work closely with students when designing, improvising and utilising educational media resources in teaching and learning in schools.
Keywords: ___working_potential_duplicate

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, E.; Role, Jesse (2016)
The purpose of conducting this study was to determine the perception that students and teachers held on the utilisation of educational media in teaching and learning of History and Government subject in public secondary schools in Nandi Central Sub County, Kenya. The study involved participation of 10 secondary schools from the area. The target population for the study involved 48 teachers and 257 form IV students. The data for the research was collected through questionnaires. Research results showed that majority of student rated that educational media was very helpful in learning History and Government. Teachers had more positive perceptions towards the integration of educational media in teaching and learning of History and Government in secondary schools in Nandi Central Sub-County. There was a significant difference on the teachers perception and students perception on the use of educational media in teaching and learning History and Government in secondary schools (p<0.05). The study concluded that teachers and students perceived differently on the effect of utilisation of educational media in teaching and learning History and Government subject in secondary schools in Nandi Central. The study recommends that teachers should go for in-service training to be acquainted with new educational media resources. Teachers should also work closely with students when designing, improvising and utilising educational media resources in teaching and learning in schools.
Keywords: ___working_potential_duplicate

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, Eunice; Role, Jesse (2013)
The purpose of conducting this study was to determine the perception that students and teachers held on the utilisation of educational media in teaching and learning of History and Government subject in public secondary schools in Nandi Central Sub County, Kenya. The study involved participation of 10 secondary schools from the area. The target population for the study involved 48 teachers and 257 form IV students. The data for the research was collected through questionnaires. Research results showed that majority of student rated that educational media was very helpful in learning History and Government. Teachers had more positive perceptions towards the integration of educational media in teaching and learning of History and Government in secondary schools in Nandi Central Sub-County. There was a significant difference on the teachers perception and students perception on the use of educational media in teaching and learning History and Government in secondary schools (p<0.05). The study concluded that teachers and students perceived differently on the effect of utilisation of educational media in teaching and learning History and Government subject in secondary schools in Nandi Central. The study recommends that teachers should go for in-service training to be acquainted with new educational media resources. Teachers should also work closely with students when designing, improvising and utilising educational media resources in teaching and learning in schools.
Keywords: ___working_potential_duplicate; auto_merged

Impact of Information Communication Technology on Education-Kenya - Kirimi, Kagwiria Josephine (undefined, 2013)
Kenya has made remarkable progress putting in place an ICT policy framework and implementation strategy, complete with measurable outcomes and time frames. The process has had the benefit of sound advice from officials and stakeholders and, perhaps more importantly, strong leadership from the office of the permanent Secretary of the Ministry of Education. However, universal implementation is challenging given the lack of resources, national ICT infrastructure, and even electrical supply- particularly in the rural areas. As technology is bound to rule our present and future, it is good to obtain know-how of the technological reforms at the earliest. Children learn faster and can adapt to changes relatively easily. If they are trained during their school years, they have a high chance of becoming experts in technology. Computers can give lovelier explanations to various subjects. The internet is an ocean of information which can be harnessed for the rendition of information in school. The inclusion of technology in the learning process makes learning an enjoyable activity, thus inviting greater interest from the learners. The administration processes, the official procedures of the school can be simplified by the means of technology. School records, the information about all the students and the teachers and other school employees can efficiently be maintained by means of the advanced technology. Thus we see that technology not only benefits the school students but also eases the office work. It makes possible a more effective way of storage and distribution of information. The realization of the importance of technology in schools and its successful implementation is a necessity. The introduction of technology in schools is the means to bridge the long distance between the present and the future. DOI: 10.5901/jesr.2014.v4n1p435
Keywords: ⛔ No DOI found

Impact of Information Communication Technology on Education-Kenya - Kirimi, Josephine (Journal of Educational and Social Research, 2014)
Kenya has made remarkable progress putting in place an ICT policy framework and implementation strategy, complete with measurable outcomes and time frames. The process has had the benefit of sound advice from officials and stakeholders and, perhaps more importantly, strong leadership from the office of the permanent Secretary of the Ministry of Education. However, universal implementation is challenging given the lack of resources, national ICT infrastructure, and even electrical supply- particularly in the rural areas. As technology is bound to rule our present and future, it is good to obtain know-how of the technological reforms at the earliest. Children learn faster and can adapt to changes relatively easily. If they are trained during their school years, they have a high chance of becoming experts in technology. Computers can give lovelier explanations to various subjects. The internet is an ocean of information which can be harnessed for the rendition of information in school. The inclusion of technology in the learning process makes learning an enjoyable activity, thus inviting greater interest from the learners. The administration processes, the official procedures of the school can be simplified by the means of technology. School records, the information about all the students and the teachers and other school employees can efficiently be maintained by means of the advanced technology. Thus we see that technology not only benefits the school students but also eases the office work. It makes possible a more effective way of storage and distribution of information. The realization of the importance of technology in schools and its successful implementation is a necessity. The introduction of technology in schools is the means to bridge the long distance between the present and the future. DOI: 10.5901/jesr.2014.v4n1p435

Reward management strategies on employee performance in selected universities in Nakuru County, Kenya - Kathombe, Mary Wambui (Egerton University, 2018)
Rewards play an important role in increasing employee job satisfaction resulting in improving organizational performance. Motivated employees are the cornerstone of any successful organization. The main objective of this study was to establish the effects of reward management strategies on employee performance in selected universities in Nakuru County. The specific objectives were: to determine the effect of financial rewards on employee performance, to determine the effect of non-financial rewards on employee performance and to determine the combined effect of financial and non-financial rewards on employee performance. Descriptive survey design was adopted in conducting this study, as it was suitable for collecting information that described an existing phenomenon. The target population was 620 lecturers in two universities in Kenya namely Egerton and Kabarak Universities, which comprised a sample of 242 lecturers. The study primarily used a questionnaire to gather data from the respondents. Data from the questionnaire were systematically analyzed according to the research objectives and hypotheses. All hypotheses were tested using regression statistics and the results of the findings established that there is a strong positive association between combined effect of financial and non-financial rewards on employees‟ performance. According to the findings of this study, financial and non-financial rewards motivate employees to better performance. Thus, employee performance will be high in Kenyan universities that adopt an integrated effort on both financial and non-financial reward measurements. The study recommends the following: First, lecturers‟ promotion should be done regularly on merit. Secondly, Universities establish a competitive retirement benefit scheme to its employees. Third, Universities should engage their lecturers on regular training programs.

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Fathers’ engagement in a parenting program primarily intended for female caregivers: An early qualitative process evaluation in Western Kenya - Jeong, Joshua; McCann, Juliet K.; Bhojani, Alina; Maguet, Zane; Uyehara, Malia; Ochieng, Michael (PLOS Global Public Health, 2024)
Parenting programs predominantly target one caregiver of the child or most commonly the child’s mother. However, fathers are also important caregivers whose engagement in interventions can benefit child health, nutrition, and development. In August 2023, a qualitative process evaluation was conducted during the first quarter of implementation to assess initial fidelity, quality, and outcomes of a parenting program in rural Western Kenya. In-depth interviews were conducted with female and male caregivers along with in-depth interviews and focus group discussions with program delivery agents. This secondary analysis specifically focused on stakeholders’ perceptions of father involvement in the program and aimed to identify barriers and facilitators to fathers’ participation, initial program impacts when fathers were involved, and recommendations for increasing father inclusion. Thematic content analysis was conducted, and data were triangulated across stakeholder groups. Overall, relatively few fathers participated in the program. Nevertheless, for the rare cases of participating fathers, stakeholders highlighted positive changes in fathers’ caregiving attitudes and practices. Key barriers to fathers’ program engagement included restrictive gender norms and perceived opportunity costs. Stakeholders suggested several strategies for better reaching fathers, including providing financial incentives and flexible scheduling of sessions. Overall, we found that fathers’ participation and program experiences were starkly different from those of mothers. Gender-responsive program adaptations and father-targeted implementation strategies are likely to increase the fathers’ engagement in parenting programs, which in turn may facilitate greater program impacts on family caregiving and child outcomes. Future evaluations of parenting programs should combine qualitative and quantitative approaches to more comprehensively assess program impacts on fathers and over time.

The Role of Language in the Teaching and Learning of Early Grade Mathematics: An 11-year Account of Research in Kenya, Malawi and South Africa - Essien, Anthony (African Journal of Research in Mathematics, Science and Technology Education, 2018)
The purpose of this study was to provide a systematic review of research that has been carried out between 2006 and 2016 on the role of language in early grade (Grades 1–4) mathematics teaching and learning in three countries—Kenya, Malawi and South Africa. These countries were selected because they have similar characteristics: teaching and learning occur in a multilingual context; their language in education policies are similar; transition from mother tongue to English happens during the early grades; and most of the learners learn mathematics in English—a language which for most is not their first/home language. Research outputs between 2006 and 2016 from the three countries were sourced from peer-reviewed mathematics and general education journals, monitoring and evaluation reports, and book chapters. Findings from the study revealed that there is a lack of longitudinal studies that investigate the impact of language on the teaching and learning of mathematics and that there are few studies on how teachers are and should be trained to teach mathematics in the early grades. The study also found that the implementation of the language in education policies in the three different focus countries is fraught with difficulties owing to a number of factors, amongst them the fact that the indigenous languages are not yet fully developed as academic languages. Finally, existing literature highlights the importance of the use of code switching and the provision of materials in the home language(s) of early graders. Recommendations regarding policy/curriculum, teacher education and pedagogic practices are made.

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Challenges facing principals in Integrating Information Communication Technology (ICT) for efficient management in secondary schools In Nyamira County, Kenya - Ombui, Silas Chester (2013)
This study examines the challenges faced by Kenyan secondary school principals in the use of ICT in enhancing school management. The study investigated computer literacy levels of secondary school principals, challenges faced by principals in integrating ICT for management and acquiring computer hardware and software, extent in which ICT is being used in management and the recommendations which can enhance the principals use ICT for management. The target groups of schools under the study were schools situated in a rural district where we have weak infrastructure and limited facilities in terms of transportation and other means of communication. The study was conducted in 30 secondary schools in Nyamira District in Kenya selected purposefully using availability of electricity as the criteria for selection. Data collection methods included closed and open ended questionnaires for the principals and observation. The data collected was analyzed by tabulating the responses from the 30 respondents and processed manually using frequency counts and percentages. The study findings showed that ICT as a management tool was not used effectively to address management issues. The study also revealed that ICT was being used for clerical issues and to a limited extent on little management issues particularly the processing of examinations. The major challenges facing the principals was lack of funds to acquire computer hardware and software, lack of exposure on the capabilities of ICT to ease management work, and lack of adequate training in ICT for the principals. The findings of the study suggest that for successful implementation of ICT for management in Kenyan secondary schools, strategies that include the financing of ICT infrastructure by the government and other stakeholders, capacity building and the formulation of an ICT policy is required to address the issue of management in secondary schools. Equally adaptation of strategies used elsewhere in the world could be employed.

Are Our Children Learning? The Status of Remote-learning among School-going Children in Kenya during the Covid-19 Crisis - Usawa Agenda (Usawa Agenda, 2020)

National Information and Communication Technology (ICT) Strategy for Education and Training - Ministry of Education (Government of Kenya, 2006)
This Strategy undertaking was prepared by the Ministry of Education (MoE) in collaboration with stakeholders from the public, private, civil society and development partner sectors. It outlines how Information and Communication Technologies (ICTs) will be adopted and utilized to improve access, quality and equity in the delivery of education services in Kenya. The Strategy is based on the vision that: “ICTs is a universal tool in education and training”. The mission statement that inspires it is: “to integrate ICTs in education and training to improve access, learning and administration.” The overall objective of the plan is to ensure that systematic efforts are made towards strengthening adoption and use of ICT in the education sector with appropriate attention given to education development priorities as outlined in the Economic Recovery Strategy for Wealth and Employment Creation (ERSWEC, 2003-2007); Sessional Paper No. 1 of 2005 entitled “A Policy Framework For Education”, Training and Research and the United Nations’ Millennium Development Goals (MDGs). The challenges that are outlined in these policy documents include; the need to achieve Education For All (EFA) by 2015 in tandem with the national and international commitment, Universal Primary Education (UPE) by 2010, and to increase transition rate from primary to secondary schools from 47% to 70%. Policy documents in the education sector have given considerable attention to priorities related to access, quality, equity and relevance at all levels. This strategic plan considers and proposes that ICT can contribute substantially towards realization of these objectives. In addition, ICT has considerable potential to support implementation of Free Primary Education (FPE) and to address emerging challenges such as; overcrowded classrooms, high Pupil Teacher Ratios (PTRs) particularly in densely populated and semi-arid areas, shortage of teachers on certain subjects or areas, and relatively high cost of learning and teaching materials

Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found

Teachers Learning Together: Large-scale approaches to teacher communities of practice - Rossignoli, Serena; Amenya, Donvan; Kamana, Dieudonne; Tiganescu, Andrea; Kudenko, Irina (Education Development Trust, 2020)
Keywords: C:Kenya / Rwanda

Strengthening Teacher Professional Development: Local and global communities of practice in Kakuma Refugee Camp - Mendenhall, Mary (Columbia University, 2017)
Keywords: C:Kenya / Rwanda

Preparedness of Public Secondary Schools on the Use of Information Communication Technology in Teaching and Learning in Mukurweini, Nyeri County-Kenya - Ngatia, Paul Kamau (Kenyatta University, 2015)
Globally the important role played by the use of Information and Communication Technology (ICT) in educational institutions has grown with states putting heavy investments in the purchase of ICT equipment and providing internet access for students and teachers. The Kenya government has been encouraging the adoption of ICT in schools. However, it is not clear to what extent this has been implemented. In Mukurwe-ini Sub County the implementation of ICT has not been effective as evidenced by Table 1.1. This study sought to assess the preparedness of public secondary schools on the Information Communication Technology (ICT) in Mukurwe-ini Sub County, Nyeri County. The study will assess the extent of use of ICT in secondary schools as well as investigate the school related and the teacher related preparedness to the use of ICT in their duties. The information obtained is helpful in assessing the implementation of government policy on ICT in schools. The study adopted descriptive survey design. The target population consisted; 31 public secondary school principals and 374 teachers in Mukurwe-ini Sub County. The researcher employed purposively, stratified random sampling techniques to select a sample of 15 schools, 15 principals and 120 teachers for the study. Data was collected using self-administered questionnaires. The questionnaires were assessed by experts in the field of educational technology to ensure validity while the reliability was tested using Cronbach’s alpha co-efficient calculated from the results of a pilot study and found to have a Cronbach’s Alpha Coefficient of 0.85. The study obtained both quantitative and qualitative data. Qualitative data were analysed thematically as per research objectives. Quantitative data were analysed by use of descriptive statistics in which measures of central tendencies such as mean, mode, and percentages were used for determination of extent of ICT, the level of school related and teacher related preparedness while inferential statistics specifically the independent sample t-test was used to test the relationship between variables using Statistical Package for Social Sciences (SPSS). It was found that teachers rarely used computers in teaching and learning. The school preparedness was poor with school environment and support being low while teachers had positive attitudes towards integration of ICT in teaching. However, teachers were found not to be well adequately trained and experienced in the use of ICT thus very low self confidence in use of ICT in teaching and learning. Conducive school environment that was supportive was found to have positive impact of integration of ICT, inadequate training and low self confidence hindered the adoption of ICT. The study recommended that the inclusion of ICT in curriculum in teacher training institutions, increased funding, provision up to date training of teachers and employment of technical support staff to improve ICT adoption in teaching and learning

The Data Protection Act (No. 24 of 2019) - Republic of Kenya (2019)

Report of the Standing Committee on Finance and Budget on the Third Basis for allocating among the counties the share of national revenue - Parliament of Kenya (2020)

ICT in Education and Training Policy - Republic of Kenya. (2021)

Kenya basic education COVID-19 emergency response plan - State Department of Early Learning and Basic Education (Republic of Kenya Ministry of Education, 2020)

Tusome and USAID Improve Access to Education - U.S. Embassy in Kenya (2016)

Guidelines on Parental Empowerment and Engagement - Kenya Institute of Curriculum Development (2019)

Pre Primary One Curriculum Designs - Kenya Institute of Curriculum Development (2017)

Standards for Competence Based Digital Course Materials - Kenya Institute of Curriculum Development (2018)

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

Basic education statistical booklet - Ministry of Education, Republic of Kenya (2019)

Assessment of public primary school teachers preparedness in the implementation of digital literacy programme in public primary schools in Imenti north sub-county, Kenya - Nyaga, Felistas (University of Nairobi, 2018)
The purpose of this study was to investigate the preparedness of public primary school teachers in the implementation of digital literacy programme in Imenti North Sub County Kenya. The study was guided by the following objectives; to establish infrastructural availability for the public primary school teachers’ usage in teaching and learning in implementation of digital literacy programme in public primary schools in Imenti North Sub County, to examine how public primary school teachers’ competence influence implementation of digital literacy program in public primary schools in Imenti North Sub County, The study sought to determine how public primary school teacher perception influence implementation of digital literacy program in public primary schools in Imenti North Sub County. The study also sought to establish how digital literacy content availability for the public primary school teachers influence implementation of digital literacy programme in public primary schools in Imenti North Sub County. The study adopted descriptive research design. The study was grounded on technology diffusion theory to explain the relationship between the independent and dependent variables. The study had a target population of 596 respondents who comprised 59 head teachers and 537 teachers. The respondents were selected using proportionate random sampling technique where by a sample size of 137 was used. Primary data was obtained using self-administered questionnaires that were made up of both open ended and closed ended questions, also unstructured interview was administered face-to-face or over the phone. The reliability of the study was measured using test retest method. The Data was analyzed using Statistical Package for Social Sciences and the data was presented in frequency tables, percentages and regression analysis. The study concluded that preparedness of public primary school teachers in the implementation of digital literacy programme was highly influenced by teacher competence followed by infrastructural preparedness and then by Teacher perception while digital literacy content had the least effect on implementation of digital literacy programme in public primary schools in Imenti North Sub County. The study concluded that infrastructural preparedness influences implementation of digital literacy program in public primary schools in Imenti North Sub County significantly. Even though the schools have electricity their computer lab have not been fully equipped. The implementation of digital literacy program has been delayed by inadequate internet connections coupled with inadequate digital literacy program devices for teaching and learning in the schools. Also, there being inadequate tablets for the learners and laptops for the teachers have negatively affected the implementation of digital literacy program in public primary schools. The study recommends that teachers and instructors need to be trained in basic ICT skills and ICT-based teaching methods to feel comfortable about using the materials. The study recommends that the governments should ensure that all the public primary schools are connected to wireless internet services; that primary schools should be assisted by both national and county government need to ensure that the schools have a complete computer lab that is fully equipped with enough laptops for the teachers and tablets for the learners. The study further recommends that head teachers and parents need to set up administrative committees to manage ICT facilities as proven to be very effective in ensuring the sustainability of initiatives.

Public Statement on the Status of Payments to County Governments FY 2021-2022 - Republic of Kenya National Treasury and Planning (2022)

Ministry of East African Community (EAC), ASALs And Regional Development - The Ministry of East African Community, Arid and Semi-Arid Lands, Republic of Kenya (2022)

"For us it was a learning experience": design, development and implementation of blended learning - Onguko, Brown; Jepchumba, Lucy; Gaceri, Petronilla (European Journal of Training and Development, 2013)
Purpose - The purpose of this paper is to share reflections of the three authors on the process of instructional design and implementation of blended learning for teachers' professional development (PD) in rural western Kenya. It proposes reforms in provision of teachers' professional development to enable professional development providers to access specialized skills in instructional design (ID) and blended learning. Design/methodology/approach - The paper resulted from a design-based research including 12 entry and 12 exit interviews, observations of three face-to-face meetings of blended learning sessions and ten classroom observations of teachers implementing new teaching approaches learned through blended learning. Findings - The paper provides insights into the authors' experiences in this research. They shared the following reflections: engagement in ID empowered them and they are confident that they can engage in systematic instructional design on a larger scale; they gained technical knowledge and skills in authoring content in HTML on eXe open source platform; uploading the content and processing audio and video content was equally enthralling to them. Research limitations/implications - Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to consider incorporating the design-based research, instructional design and blended learning approaches used in this study while conducting related research in their dissimilar contexts. Practical implications - The paper includes implications for the design, development and implementation of teachers' professional development for challenging contexts as a contribution towards achievement of both Millennium Development Goals (MDGs) and Education for All (EFA). Originality/value - This paper fulfils an identified need to study provision of professional development for teachers who lack opportunities for professional development.
Keywords: 5220:Information technology management; 8306:Schools and educational services; 9177:Africa; Appropriate technology; Audio recordings; Business And Economics--Management; Instructional design; Kenya; Personal development; Professional development; Research; Rural schools; Teaching; Technological change; Training; __:import:01; __:match:final; __:matched; __:study_id:2096396; ___working_potential_duplicate; __finaldtb

School governance, teacher incentives, and pupil–teacher ratios: Experimental evidence from Kenyan primary schools - Duflo, Esther; Dupas, Pascaline; Kremer, Michael (Journal of Public Economics, 2015)
Some education policymakers focus on bringing down pupil–teacher ratios. Others argue that resources will have limited impact without systematic reforms to education governance, teacher incentives, and pedagogy. We examine a program under which school committees at randomly selected Kenyan schools were funded to hire an additional teacher on an annual contract renewable conditional on performance, outside normal Ministry of Education civil-service channels, at one-quarter normal compensation levels. For students randomly assigned to stay with existing classes, test scores did not increase signiﬁcantly, despite a reduction in class size from 82 to 44 on average. In contrast, scores increased for students assigned to be taught by locally-hired contract teachers. One reason may be that contract teachers had low absence rates, while centrally-hired civil-service teachers in schools randomly assigned contract teachers endogenously reduced their effort. Civil-service teachers also captured rents for their families, with approximately 1/3 of contract teacher positions going to relatives of existing teachers. A governance program that empowered parents within school committees reduced both forms of capture. The best contract teachers obtained civil service jobs over time, and we estimate large potential dynamic beneﬁts from supplementing a civil service system with locally-hired contract teachers brought in on a probationary basis and granted tenure conditional on performance.

Literacy rate, adult total (% of people ages 15 and above) - World Bank (2020)

The National Treasury and Planning (@KeTreasury) - The National Treasury and Planning (Twitter, 2020)

Third Medium Term Plan 2018-2022 - The National Treasury and Planning (2018)

Teachers Service Commission (2020)

Centre for Mathematics, Science and Technology Education in Africa (2020)

Ministry of Information, Communications and Technology, Innovation and Youth Affairs (2019)

Loon (Loon, 2020)
Loon is a network of stratospheric balloons designed to bring Internet connectivity to rural and remote communities worldwide.

Microsoft (2020)
Microsoft, en tant qu’acteur de la transformation numérique en France, aide les individus et les entreprises du monde entier à exploiter pleinement leur potentiel.

The Centre for Innovative Teaching and Learning Approach - Mastercard Foundation (2019)

Kytabu – African Schools Online - Kytabu Company Ltd (2020)

EdTech East Africa (Edtech Meetup, 2017)

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
Keywords: _internal; _r:AddedByMyEducationEvidence

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Using innovative methods to train teachers of blind children: what we learned - Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Governments all over the world have closed learning institutions because of the Covid-19 pandemic, including in Kenya. This has exacerbated the global learning crisis and made it more difficult for teachers, parents, and caregivers to include children with disabilities in quality education. To ensure learners with disabilities were not left behind during Covid-19 school closures, eKitabu partnered with EdTech Hub…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Digital Personalised Learning to Improve Numeracy Outcomes in Kenyan Primary School Classrooms - EdTech Hub (EdTech Hub, 2021)

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Designing for Scale: Understanding design principles and learning process for a personalised learning platform in Kenya - EdTech Hub (EdTech Hub, 2022)

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
Keywords: _r:AddedByZotZen

An exploratory investigation into the factors related to EdTech use among Kenyan girls - Watson, Joe; Baier, Jasmin; Mughogho, Winnie; Millrine, Mark (British Journal of Educational Technology, 2023)
This paper contributes to the scarce literature on factors affecting EdTech use in households. These factors were considered through exploratory mixed-methods analyses of cross-sectional data on Kenyan girls and caregivers, captured during the COVID-19 pandemic. Quantitative analysis of the child dataset (n = 544) suggested the importance of both structural factors—such as technology hardware availability—and non-structural factors—including caregiver permission. Findings were supported by a thematic analysis of interview data from girls' caregivers (n = 58), which emphasised the role they play in girls' use of EdTech. Interviews also highlighted numerous caregiver concerns with EdTech, related to the relevance and rigour of educational content, the possibility of children accessing age-inappropriate material and child health (especially eyesight). Policy makers could alleviate these concerns by providing guidance on EdTech use and clearly signalling their approval of verified initiatives. Practitioner notes What is already known about this topic EdTech can benefit girls' education, yet there are various barriers to it being used. Existing research shows clearly that EdTech use can be impeded by structural factors (eg, hardware ownership). However, we find insufficient empirical evidence on the role of non-structural or behavioural factors. What this paper adds This paper addresses this gap, using a mixed-methods approach to explore the influence of 33 different measures (including non-structural factors) that could affect the number of hours girls spend using EdTech at home. Findings from a quantitative sample of girls (n = 544) and a qualitative sample of girls' caregivers (n = 58) highlighted the importance of non-structural factors, especially caregiver permission. The variable most strongly associated with girls' EdTech usage in our selected quantitative model concerned whether this was sanctioned by their caregivers. Our qualitative data suggested why caregiver permission to use EdTech might be withheld: caregivers emphasised perceived concerns about the risks and rigour of EdTech. Implications for practice and/or policy Our findings suggest the viability of policy interventions that provide EdTech guidance to caregivers. Caregivers uncertain about EdTech could be reassured of the appropriateness of verified initiatives, while those already convinced might be aided in their attempts to support EdTech learning. Such guidance could provide a low-cost means of further exploiting the benefits that household EdTech learning can provide.
Keywords: COVID-19; EdTech; Kenya; caregivers; girls' education; ⛔ No INSPIRE recid found

Research methods dictionary - Mugenda, Olive M; Mugenda, Abel G (Kenya Arts Press, 2012)

Keep Kenya Learning Project (2021)

Population, total - Kenya | Data - World Bank (2021)

Worldreader (2020)
With low-cost technology, culturally-relevant digital books, and a network of partners, we’re helping millions of people read more and read better.

Population growth (annual %) - Kenya | Data - World Bank (2021)

Kenya's pioneering eLearning programme - iMlango (iMlango, 2022)
iMlango aims to improve education outcomes in maths, literacy & life skills for 180,000 children in 245 schools by delivering access to digital education services & content.

Case Study Report: RET International Kenya - Boisvert, Kayla (University of Massachusetts Amherst, 2017)

School enrollment, primary (% net) - Kenya | Data - World Bank (2021)

Lessons from Kenya’s Education Reforms - World Bank (2022)

Can Education be Standardized? Evidence from Kenya - Gray-Lobe, Guthrie; Keats, Anthony; Kremer, Michael; Mbiti, Isaac; Ozier, Owen (Becker Friedman Institute for Economics at the University of Chicago, 2022)
We examine the impact of enrolling in schools that employ a highly-standardized approach to education, using random variation from a large nationwide scholarship program. Bridge International Academies not...

Digital 2020: Kenya – DataReportal – Global Digital Insights - DataReportal (2020)

Kenya Education Sector Support Programme 2005 - 2010 - Ministry of Education, Science and Technology (2005)

Implementing large scale instructional technology in Kenya | RTI - Piper, Ben; Oyanga, A; Meija, J; Pouezevara, S (2017)

Kenya lauded for achieving 75% electricity access rate - Common Market for Eastern and Southern Africa (COMESA) (2021)

End education crisis in Northern Kenya - The Standard - Guleid, Mohamed (2021)

After COVID-19, let’s reimagine education in Kenya - Zaman, Maniza (2021)
Digital learning should be part of a basic package of essential services for every child

Kenya Partnership Compact. 2021 | Documents | Global Partnership for Education - Global Partnership for Education (2021)

Impact evaluation of Tayari school readiness program in Kenya - Ngware, Moses; Hungi, Njora; Wekulo, Patricia; Mutisya, Maurice; Njagi, Joan; Muhia, Nelson; Wambiya, Elvis; Donfouet, Hermann; Gathoni, Grace; Mambe, Shem (APHRC, 2018)

KENYA GPE COVID 19 Learning Continuity in Basic Education Project - Global Partnership for Education (2020)

Alarm over teen pregnancies as Kenya ranked third worldwide | Nation - Maichuhie, Kamau (2022)

Boosting Prosperity, Improving Equity in North and North Eastern Kenya - World Bank (2018)

Low-tech personalised learning to improve girls' education in Kenya. - Jordan, K; Damani, K; Khagame, P; Mongeau, C; Mumbi, A; Myers, C; Njuguna, L; Otieno, J; Zhao, A (EdTech Hub and M-Shule, 2023)

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Human Development Reports - UNDP (2020)

Unlocking Literacy: Navigating Parental Engagement with Worldreader’s BookSmart in Kenya - Smith, Wendy; Nicolai, Susan; Kartha, Ashwati; Kimani, Olivia (EdTech Hub, 2024)
Globally, just one-third of 10-year-olds can read and understand basic written stories. Can EdTech and parental engagement change this? Read on to learn more.

Exploring the Landscape for Digital Education: Observations from Kenya, Nigeria, and Senegal - USAID (2022)

Impact of Covid-19 on the right to education In Kenya - Jelimo, Catherine (Right to Education Initiative, 2020)
On March 15, 2020, the Kenyan government abruptly closed all schools and colleges nationwide in response to COVID-19, disrupting nearly17 million learners countrywide. The closure of institutions not only affected learners and teachers but it also brought forth numerous economic and social issues, including interrupted and loss of learning, education exclusion, homelessness, nutrition and economic crisis, childcare challenges and increase in teenage pregnancy cases, financial cost implication to households, and sexual exploitation among others.

Accessibility and Utilization of ICTs Among Secondary School Teachers in Kenya - Kiptalam, GK; Rodrigues, AJ (2010)
Keywords: ⛔ No DOI found

Teachers’ attitudes towards the utility of computers in education in Kenya - Buliva, Newton (African Educational Research Journal, 2018)

Mobile phone-based cash transfers: lessons from the Kenya emergency response - Datta, Dipankar; Ejakait, Anne; Odak, Monica (Humanitarian Practice Network, 2008)

Application and program document for COVID-19 accelerated funding for Kenya - Global Partnership for Education (2020)

Concept on mapping technical and vocational educational and training data in Kenya - Ministry of Education (State Department for Vocational and Technical Training, 2021)

A spatial database of public primary day schools in western Kenya - Macharia, Peter M.; Moturi, Angela; Mumo, Eda; Snow, Robert W. (Harvard Dataverse, 2022)
Understanding the location of primary schools relative to population is important to contextualize the time, or distance, that students must travel...
Keywords: Other

Kenya: How Rogue Officials Inflated Enrolment, Used Ghost Schools to Steal Billions - Muchunguh, David (The Nation in Allafrica.com, 2021)

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Report: The Impact of COVID-19 Across Africa - Elliott, Roxana (GeoPoll, 2020)
New report on coronavirus in sub-Saharan Africa including data from Kenya, Ghana, South Africa, Nigeria. COVID-19 and food security, economic impact.

In Bringing a Literacy Project to Scale, has Kenya Found a Holy Grail? - Bruns, Barbara (Center For Global Development, 2018)
An article of faith among development economists is that “evidence-based policy” holds the promise of faster progress. Barbara Bruns set out to find a rigorously evaluated pilot whose evidence had led to a program at scale. It wasn’t easy.

Mobile Data Plans in Kenya. Quantifying Women's Access to the Digital World - Gemeda, B.T.; Thakur, D. (Alliance for Affordable Internet, 2017)

Educational technology to improve capacity - integrating adaptive programmes in public schools in Kenya - Kaye, Tom (2021)

246 6 Accessibility and Utilization of ICTs Among Secondary School Teachers in Kenya - University, G. (2010)
This paper looks at levels of access and extent of use of Information and Communication Technologies (ICTs) among teachers in selected Kenyan secondary schools. For the past few years, an assortment of ICTs such as computers, lap tops, projectors, printers, e-blackboards and mobile phones have been available to teachers for use in integration of teaching and learning in schools. The paper attempts to establish how many teachers have access to the schools’ computers, their ICT literacy skills level and the level of ICT integration in subjects taught. The findings show that the use of ICT and its integration in the teaching and learning in secondary education is getting more widespread; and increasingly used among teachers as a means of communication and for information searching. Access rates for teachers have been observed to be much higher in educational institutions that have made effective ICT investments in education, translating into better utilization of ICT related technologies. Strategies have been suggested on how to utilize ICT to improve educational outcomes and recommendations given, on issues that touch on ICT access and infrastructure; human resources and training, policy environment, financing and ICT investment, curriculum development and locally relevant content.

Abolishing School Fees in Africa: Lessons Learned in Ethiopia, Ghana, Kenya and Mozambique - Birger, Fredriksen; Craissati, Di (The World Bank, 2009)

The Kenya Ministry of Education’s response to the COVID-19 pandemic: Case study - Gichuhi, Loise; Kallsta, Jane (UNESCO IIEP, 2022)

Pivoting in a Pandemic: eKitabu Provides Sign Language Video Content For Students in Kenya - eKitabu (2020)

Systems Implications for Core Instructional Support Lessons from Sobral (Brazil), Puebla (Mexico), and Kenya - Crouch, Luis (Research on Improving Systems of Education (RISE), 2020)
As this note was being written in April and May 2020, the Coronavirus pandemic was sweeping the world. Children were out of school. Researchers around the world are now estimating a severe learning gap due to loss of school attendance. While the first priority is getting children back to school safely, the discussion in this note regarding foundational learning is all the more relevant, as it is this kind of learning that is likely most affected. Key Points The case studies in this document highlight five tips that may be beneficial to other countries or situations: Focus on just a very few achievable indicators, foregrounding foundational learning, for a country emphasising learning. Use data to drive both initial “wake-up” and stock taking but also to support teaching as the process goes along. Emphasis on the teaching by the teachers who are already in place. Provide strong motivation through support that works. Use tight management so there is some degree of centralism and prescriptiveness as to pedagogy and other inputs, but after having iterated and adapted to context.

Educational Technology to Improve Capacity – Integrating Adaptive Education Programmes in Public School in Kenya - Kaye, Tom (Trust, Accountability and Capacity in Education System Reform, 2020)
Keywords: ___working_potential_duplicate

Kenya GPE 19 Learning Continuity in Basic Education Project - Implementation Status and Results Report - World Bank (2021)

Parental Involvement in Primary Schools in Kenya as a Major Strategy for Academic Success - Muigai, Jecinta W. (European Journal of Education Studies, 2018)
Keywords: ⚠️ Invalid DOI

Technology Enabled Learning in Kenya: KWA Ground Insights on Building Resilient Distance Learning Ecosystems - Otieno, Jennifer; Ward, Rebecca (IREX, 2022)
Keywords: ⛔ No INSPIRE recid found

Mathematics from the beginning: Evaluating the Tayari preprimary program’s impact on early mathematics skills - Piper, Benjamin; Sitabkhan, Yasmin; Nderu, Evangeline (Global Education Review, 2018)
Given the dearth of research on early numeracy interventions in low- and middle-income countries, this paper presents the instructional methodology and impact results of the Tayari program. Tayari is a preprimary intervention in Kenya (2014–2019) that prepares children aged four and five for entry into primary school through materials for students, training for teachers, and continuous in-classroom support. Evidence points to the long-term benefits of developing an early foundation in mathematics. The few preprimary mathematics studies in sub-Saharan Africa have not described the instructional methodology in enough detail to add to our knowledge of best practices. The Tayari methodology was built on the Kenyan government’s preprimary syllabus to produce instruction that was developmentally sequenced, linked to out-of-school experiences, and supportive of children’s number sense. Tayari is evaluated using a randomized controlled trial (RCT) and collection of longitudinal data from 2,957 children in treatment and control schools at three time points. Pupil assessment items were drawn from a growing body of research on preprimary numeracy in developing contexts, plus instruments and techniques from the Measuring Early Learning and Quality Outcomes (MELQO) program (UNESCO, UNICEF, Brookings Institution, & World Bank Group, 2017). The endline impact evaluation of the longitudinal RCT results showed statistically significant effects in the numeracy tasks of producing sets, identifying numbers, and naming shapes, while revealing no initial effects in the areas of oral and mental addition. We present recommendations for Tayari’s improvement in terms of mathematics instruction, as well as preprimary policy implications for Kenya and similar contexts.
Keywords: Sub-Saharan Africa; ⛔ No DOI found

A Dialogic Design-Based Research Partnership Approach: Developing Close-to-Practice Educational Technology Theory in Kenya - Major, Louis; Daltry, Rebecca; Rahman, Asad; Plaut, Daniel; Otieno, Mary; Otieno, Kevin (Global Perspectives on Teaching with Technology, 2024)
Design-based research (DBR) has promise for investigating educational technology in low- and middle-income contexts. However, DBR is implemented infrequently in such settings, highlighting a need for guidance on implementation. This chapter critically reflects on innovative DBR involving Kenyan teachers and research partners over two years. This focused on the iterative evaluation of a ‘digital personalised learning’ tool to improve its integration into classroom practice. This DBR promoted teacher-researcher engagement by adopting a dialogue-informed ‘intermediate theory building’ framework, bridging the theory-practice gap. Additionally, it enhanced inclusivity by broadening the concept of partnership through an ‘integrated’ approach. Lessons learned and practical implications are highlighted. Outcomes establish a novel foundation for applying DBR to enhance educational technology for marginalised learners.

Maintaining learning continuity during school closure: Community Health Volunteer support for marginalised girls in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Page, Ella; Naylor, Ruth; Jones, Charlotte; McAleavy, Tony (Education Development Trust, 2020)

Integrating ICT into Teaching and Learning Biology: A Case for Rachuonyo South Sub-County, Kenya - Mwanda, Gideon (International Journal of Education, Culture and Society, 2017)

Opportunities and Challenges: Integration of ICT in Teaching and Learning Mathematics in Secondary Schools, Nairobi, Kenya - Amuko, Sheila; Miheso, Marguerite; Ndeuthi, Sophie (Journal of Education and Practice, 2015)
This presentation is based on a larger study whose purpose was to explore the various opportunities and challenges influencing integration of ICT in teaching and learning Mathematics in secondary schools in Nairobi County. The study, adopted a descriptive survey design. Three instruments questionnaires’, a structured interview schedule and an observation checklist were used to collect data. The study was carried out in twelve public secondary schools in Nairobi County. Data was analysed using descriptive statistics. Findings from the study indicated that, teachers face major challenges such as developing their own technological skills and knowledge as well as self-training in the use ICTs in their teaching. This lack of capacity building support was found by the study to contribute to teacher lax in integrating technology in their teaching inspite of the enthusiasm. This study recommends that new frontiers on technology integration be made accessible to both teachers and students for learning purpose to increase access to information and that, capacity building in technology integration be increased for teachers and awareness be built among pre-service teachers trainees integrating ICT in teaching and learning Mathematics.
Keywords: Barriers; Check Lists; Foreign Countries; Knowledge Level; Mathematics Instruction; Observation; Public Schools; Questionnaires; Secondary School Mathematics; Secondary School Teachers; Statistical Analysis; Structured Interviews; Surveys; Teacher Attitudes; Teacher Competencies; Teacher Education; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; ___working_potential_duplicate; ⛔ No DOI found

Teachers’ Perception About Integration of ICT Tools in Kiswahili Language Pedagogy in Homabay County, Kenya - Ochieng, BENSON ONYANGO; Miima, FLORENCE ABUYEKA (International Journal of Arts and Commerce, 2019)

Measuring the Impact of COVID-19 on Learning in Rural Kenya’ by Whizz Education (April 2021 - Whizz education (2021)

Promoting gender equality in education in Kenya: A case for innovative programmes to bridge the divide - Kinyanjui, Joyce (Buwa, 2016)
This issue of BUWA explores these questions and provides space for African women and men to define the kind of education that can meet SDG goals. Articles in the issue assess the existing policy frameworks and the officially stated drivers which are shaping them as well as those which are not stated. The various tested and emerging untested models for delivering quality education for women and girls on the continent are considered, as well as key questions around innovative, robust financing models and challenges for education. The main focus here is the extent to which the provision of quality education has to be fully catered to through domestic finances and resources – both for sustainability and ownership purposes.
Keywords: Equity through Access; ⛔ No DOI found; ⛔ No INSPIRE recid found

Teacher-AI Collaboration in Content Recommendation for Digital Personalised Learning among Pre-primary Learners in Kenya - Sun, Chen; Major, Louis; Daltry, Rebecca; Moustafa, Nariman; Friedberg, Aidan (L@S '24: Eleventh ACM Conference on Learning @ Scale, 2024)

An Improved Model for the Implementation of Web-Based Learning in Adult Secondary School Education in Kenya - Ng’ang’a, Ms Martha Muthoni; Kimani, Prof Stephen; Kimwele, Dr Michael W. (International Journal of Computer (IJC), 2020)
The development of technology, which evolves continuously, has led to the transformation of traditional courses into web-based courses. However, as these e-learning systems grow more complex, involving numerous users with different levels of need, there is a need to have web-based learning models that adequately address such users’ needs, taking into consideration their levels of expertise, access and ability to interact with such systems. Most of the existing models present the adult learners with difficulties, as most of them have to concentrate mostly on learning the technology rather than learning the desired content. Most of the difficulties arise from the web-based learning model configurations in use in the country. The majority lack features and capabilities of highly interactive, fast-paced multimedia-supported learning currently demanded by most learners and tutors. Therefore, the main aim of this research was to devise an improved model for implementing a web-based learning programme in adult secondary school education. After analysing the existing models and establishing their operational challenges, an improved model was proposed. The proposed model was statistically tested using sample data. The results showed that recognizing both technological and user attributes along the recognized theoretical frameworks was important in increasing the users’ behavioural inclination to use the improved model. Therefore, it is recommended that more sensitization to web-based learning should be implemented by the adult education department in the Ministry of Education among adult learners in the country. It is also recommended that system developers should find ways of incorporating additional features into the model without affecting its architecture and function. Finally, there is need for future studies on the causal antecedents of the constructs presented in this research model to provide more precise practical implications.
Keywords: Adult Learners; Model; Web Based Learning; ⛔ No DOI found

The effect of free primary education policy on late school entry in urban primary schools in Kenya - Ngware, Moses W.; Oketch, Moses; Ezeh, Alex C.; Mutisya, Maurice (International Review of Education, 2013)

How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Effects of Special E-Learning Program on Hearing-Impaired Learners' Achievement and Perceptions of Basic Geometry in Lower Primary Mathematics: - Kiboss, Joel Kipkemboi (Journal of Educational Computing Research, 2012)
Achievement in mathematics is an issue of great concern not only to students and parents but also to employers and researchers in Kenya. This is because the Ken...

Anasoma Mid-Term Report - Worldreader; R4D (Worldreader, 2017)
This report shows the initial findings of the first sprint of the Anasoma Research aimed at identifying barriers of and drivers to female mobile readership in Kenya.

Tusome Early Grade Reading Activity - RTI International (RTI, 2016)
Across Kenya, literacy rates in primary schools are significantly lower than expected despite increased access and enrollment. The Kenyan education system is seeking to improve learning outcomes by instilling better instructional practices, expanding resources for teacher training, and developing learning materials that support multilingual literacy. Kenya’s approach to the challenge of raising literacy and learning outcomes is unique in its ambitious goals and well-researched methods for achieving its goal at a national scale.

Influence Of Hidden Costs In Education On Students’ Participation In Public Secondary Schools In Kikuyu Sub County, Kenya - Kingori, Joseph Ndirangu (School of Education Department of Educational Administration and Planning of Nairobi University, 2015)
Keywords: ⛔ No DOI found

Kids hacker camps in Kenya | Proceedings of the Seventh International Conference on Information and Communication Technologies and Development - Ndaiga, Wachira; Salim, Anne (2015)

ICT in secondary school administration in rural southern Kenya: An educator’s eye on its importance and use - Makewa, Lazarus; Meremo, Jackson; Role, Elizabeth; Role, Jesse (2013)
This study investigated whether there was a significant difference between teachers’ and administrators’ perceptions on the importance of Information and Communications Technologies (ICT) in secondary school administration and evaluated the extent to which it was used by administrators. In this study, administrators are those involved in the day to day running of secondary school duties such as: the principal, deputy principal and heads of departments. The researchers used a descriptive-comparative research design to obtain information on the current status of ICT. The t-test was used to establish whether there was any significant difference in perceptions while a Pearson product-moment correlation coefficient was used to find whether there was any significant relationship between educators’ perceptions of the importance and extent of ICT use in secondary school administration. Both teachers and administrators rated the use of ICT in secondary school administration as important. Teachers and administrators viewed the use of ICT in student administration as equally important. Administrators rated the importance of using ICT in supervision of instruction and in student administration more highly. There was a significant difference between the perceptions of teachers and administrators on the importance of ICT use in the following areas of secondary school administration: student administration, general administration and supervision of instruction.
Keywords: ⛔ No DOI found

Influence Of Hidden Costs In Education On Students’ Participation In Public Secondary Schools In Kikuyu Sub County, Kenya - Kingori, Joseph Ndirangu (School of Education Department of Educational Administration and Planning of Nairobi University, 2015)

Impact of non-financial reward strategies on teachers’ performance: A study of secondary schools in Nyamira County, Kenya - Mochengo, Sylvester Nyageo; Atambo, Wallace; Abuga, Mogwambo Vitalis (European Journal of Business and Management, 2016)
Keywords: ⛔ No DOI found

Integrating digital personalised learning into pre-primary classroom practice: A teacher-researcher multiple-case study partnership in Kenya - Daltry, Rebecca; Major, Louis; Otieno, Mary; Otieno, Kevin; Jordan, Katy; Moustafa, Nariman (Education Sciences, 2025)
Keywords: ⛔ No DOI found

Are Our Children Learning? The status of remote-learning among school-going children in Kenya during the Covid-19 Crisis - Uwezo (Usawa Agenda, 2020)

Implementing Parental Empowerment and Engagement Strategies in Times of Crisis: Experiences from Regional Educational Learning Initiative members in Kenya - Angoye, James (Regional Education Learning Initiative Africa, 2021)

Enhancement of Science Performance through Computer Assisted Instruction among Selected Secondary School Learners in Kenya | Dr. Samuel N Jesse - Academia.edu - Jesse, Samuel (2014)

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 3: Skills taxonomy - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the third of five reports on the development of a proof of concept for the Hub and describes our observations during the creation of a skills taxonomy. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Dr Angeline Sabina; Kyalo, Dr Dorothy Ndunge (2013)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Distanced and Disadvantaged: A Study on the Effects of COVID-19 on Education for Learners with Disabilities in Kenya, October 2020 - Angoye, James; Mbari-Kirika, Irene; Walker, Bruce; Kavua, Martin (inABLE.org, 2020)

Design and development of a Web Based Learning System in lower primary schools: A Case study of Makini Primary School, Kenya - Akinyi, Beatrice Ochieng (Moi University, 2015)
Web design technology arises from continued technological trend of computing. Globally the rise of application of information communication technology to the learning programme of primary schools is not much emphasized on. There is empirical evidence to prove that information communication technology is highly beneficial wherever it is applied. The study aimed at designing and developing a web based system of learning that can enhance the academic and social growth of lower primary school pupils. The objectives of the study were: to examine the correlation between the increased use of web based systems of learning and learner‟s academic performance; to identify the set of skills required for lower primary pupils to fully exploit the potential of web based systems of learning; to find out the specification and technical attributes of web based systems of learning that facilitate learning and lastly to design a web based learning system for lower primary school pupils. The study focused on Makini lower primary school in Nairobi County. The study employed case study method and qualitative approach. Rapid Application Development life cycle was used in software development process. Purposive sampling method was used to identify the respondents. Data was collected using interviews and focus group discussions. Findings of the study were: increased use of web based system that enhanced the learner‟s academic performance, the web based system of learning was able to identify games which exploit the pupils‟ skill in learning hence reducing monotony and lastly the web based system was able to identify some technical attributes such as use of graphics and access rights that facilitated learning and testing. The conclusion showed that developing of a web based learning system would reduce monotony in learning and enabled pupils to be in control and also increased the creativity and thinking level. The study recommends that: additions be made to the system such as a module to generate a feasible master timetable for each teacher; the web application of the system be further expanded to help attendance recording by the class teacher and for the parents to be able to view the status of their children performance using the Internet or Intranet of the school and lastly the system be made for every teacher to have some specific free periods or some part of days off and that will require an efficient search technique.
Keywords: ___working_potential_duplicate

Use of Information communication technology in teaching and learning processes in secondary schools in Rachuonyo South District, Homa-Bay County, Kenya - Obonyo, Samson O. (University of Nairobi, 2013)
The purpose of this study was to investigate the use of Information Communication Technology (ICT) in teaching and Learning in Rachuonyo South District secondary schools. The focus was on three main subject matters: on ICT use and competence, on teacher and student and on ICT infrastructure and teaching practices. The study is closely connected to the national educational policy, which has aimed strongly at supporting the implementation of ICT in pedagogical practices at all institutional levels. Six research questions were formulated to guide the researcher investigate the phenomena. A descriptive survey design was used to collect data from the field through the use of questionnaire and an observation schedule. The result indicated that ICT has not been successfully integrated in teaching and learning in schools. In general, students are capable and motivated users of computers. Some students have the skills to use new kinds of applications and their ICT skills are wider although not necessarily adequate. Teachers’ skills are more heterogeneous. The large majority of teachers have sufficient skills for everyday and routine working practices, but many of them still have difficulties in finding a meaningful integration of ICT into teaching and learning. Most teachers reported that the use of ICT in learning and teaching was slow in the past years and proposed upgrading of students computer labs and accelerating internet connectivity in the schools. Further, teachers’ good ICT competence helps them to adopt new pedagogical practices and integrate ICT in a meaningful way. The results also showed that students are capable and motivated users of new technology and their ICT skills are wide, although not necessarily adequate; the working habit might be ineffective and wrong. Some students have a special kind of ICT related adaptive expertise, which develops in a beneficial interaction between students and teachers, and individual interest and activity. The most common goal to student use of ICT is challenged by the internet, digital communication and the need to filter information. Since students’ ICT skills can be translated to increased creativity, which include innovation and productive workforce, to develop capacity to ICT which support the country’s knowledge base. The findings further indicated that ICT integration realized some challenges such as availability of sufficient number of ICT tools, lack of motivation and support and lack of technical support. The challenges are either teacher-level (Microlevel), school level (Meso-level) or system level (Macro-level). These barriers have hindered successful implementation of ICT into teaching and learning processes. The study also recommended that teachers should be given sufficient training on how to use ICT tools to enhance teaching and learning in schools. The study also recommended that students should be equipped with ICT skills such as Microsoft software applications such as word, excel and access. Finally, further research on the perception of teachers and students towards the use of ICT in enhancing teaching and learning and relevant strategies for using ICT to improve teaching and learning practices should be conducted.

The Influence of Principals’, Teachers’ and Students’ Attitude on Readiness to Adopt e-Learning in Secondary Schools in Kitui District, Kenya - Mulwa, Dr Angeline Sabina; Kyalo, Dr Dorothy Ndunge (2013)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Is 2020 a lost academic year? The impact of COVID-19 on education in eastern Africa: a case study of Kenya - Cordeiro, Vanessa Cezarita (Humanium, 2020)
Despite national efforts and strict measures designed to curb the spread of the virus, the country continues to suffer from the knock-on effects of the pandemic.

‘Now I want to use it to learn more’: Using mobile phones to further the educational rights of the girl child in Kenya - Zelezny-Green, Ronda (Gender & Development, 2018)
Keywords: Equity through Access; ⛔ No INSPIRE recid found

Teachers as Guides: The role of teachers in the facilitation of technology-mediated learning in an alternative education setting in western Kenya - Radhakrishnan, Dhinesh; DeBoer, Jennifer; Kimani, Samuel (Purdue University, 2018)

Teachers and Students Perceptions on the Utilisation of Educational Media in Teaching and Learning History and Government in Secondary Schools in Kenya - Rugut, Eunice; Jesse, Role (International Journal of Science and Research (IJSR), 2016)
Call for Papers - International Journal of Science and Research (IJSR) is a Fully Refereed - Peer Reviewed International Journal. Notably, it is a Referred, Highly Indexed, Online International Journal with High Impact Factor.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

JiFUNzeni: a blended learning approach for sustainable teachers' professional development - Onguko, Brown Bully (Electronic Journal of e-Learning, 2014)
JiFUNzeni blended learning approach is a sustainable approach to provision of professional development (PD) for those in challenging educational contexts. JiFUNzeni approach emphasizes training regional experts to create blended learning content, working with appropriate technology while building content repositories. JiFUNzeni approach was fieldtested though a design-based research intervention conducted in rural western Kenya. The field test included design, development and implementation of a blended learning course for teachers’ professional development utilizing appropriate technologies including tablets powered by solar energy, open educational resources and open source software. One year after the intervention, follow-up interviews were conducted with eight of the ten teachers and two professional development tutors (PDTs) who participated in the research. The findings from the follow-up interviews shared in this paper revealed that: teachers still used cooperative learning and activity-based learning strategies in their teaching. The PDTs on the other hand designed, developed and implemented one other jiFUNzeni blended learning course for twelve teachers in one school in Korogocho slum in Nairobi city. Implementation by PDTs of jiFUNzeni approach confirmed that they had learned through a sustainable way of delivering professional development in challenging educational contexts. The PDTs utilized the instructional design approaches learned through their participation in the research in designing blended learning content, while they also innovated new ways of developing self-study content as an important creative addition to what they had previously learned. Two teenage children participated in digital content development by advising the PDTs on some appropriate ways of applying technology thus, attesting to the fact that digital natives are important reciprocal supporters to digital immigrants and vice versa.
Keywords: Blended Learning; Computer Software; Computers; Cooperative Learning; Cooperative learning; Course Content; Design; Disadvantaged Environment; Distance learning; Education--Computer Applications; Educational Technology; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; Instructional Design; Internet; Interviews; Kenya; Learning Activities; Multimedia Materials; Open Source Technology; Program Development; Qualitative Research; Rural Areas; Self Evaluation (Individuals); Sustainability; Teacher Attitudes; Teaching Methods; Training; __:import:01; __:match:final; __:matched; __:study_id:2096405; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

UIS Statistics - UNESCO Institute for Statistics (2018)
Keywords: ___working_potential_duplicate

UIS Statistics - UNESCO Institute for Statistics (2018)
Keywords: ___working_potential_duplicate

Use of low cost wireless communication technology for education in rural Kenya | Proceedings of the 4th ACM Workshop on Networked Systems for Developing Regions - Mayeku, B.; Kilwake, J.; Bertarelli, F (2010)

Innovation: Instant Network Schools open up a new world for Somali refugees - Ostermann, Silja (United Nations High Commissioner for Refugees, 2015)
DADAAB, Kenya, February 4 (UNHCR) - Thirty pairs of fascinated eyes watch the big white screen; fingers glide across new tablet computers. A class of students at the Nasib Secondary School in north-east Kenya's Dadaab refugee camp complex, is enjoying a history lesson about the Portuguese in Africa. Most have spent their whole life in the arid camps of Dadaab. They have never even visited the closest Kenyan city, Garissa, which is located two hours away by road. But today they are travelling through Africa and the past - online.

Assessment of parent’s engagement in implementation of competency-based curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County, Nithi County, Kenya - Njeru, Atanasia Ikoore; Kirimi, Josephine (European Journal of Education Studies, 2023)
Education is a shared responsibility and all stakeholders need to understand and appreciate what is being done and what is required of them to make meaningful contributions to the process. Because the Competency-Based Curriculum shifted its focus from teaching-centric to collaborative-centered, parents are important stakeholders for its successful implementation. Therefore, empowering and engaging a parent in the learning process is essential to the learner’s growth and development. The study examined parents’ engagement in CBC implementation. This study specifically aimed to determine parents’ engagement in the implementation of Competency-Based Curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County. To get this, the researcher went to private primary schools in Tharaka South Sub County to observe how parents are embracing CBC and randomly selected some parents for interviews, teachers, and head teachers to fill out questionnaires. The study adopted a descriptive survey design where the targeted population was drawn from the 30 private schools in the sub-county. The study targeted 528 respondents. 66 respondents were sampled: 42 parents, 18 teachers and 6 head teachers. Simple random sampling was then used to select the participant. The study conducted a pretest study in 3 private primary schools for the purpose of validating the research instruments. Data was collected using questionnaires for head teachers and teachers and interview schedules for parents. The validity of the research instruments was determined through expert judgment whereas the reliability of the questionnaires was determined through a Cronbach’s alpha coefficient of 0.7982 was obtained. Qualitative data was analyzed thematically whereas quantitative data was summarized using percentages, mean, standard deviation and frequencies were used. This was facilitated by the Statistical Package for Social Sciences (SPSS) Version 21. The study established a significant relationship between the parent’s literacy and the implementation of CBC with a significance value of p=0.000<0.05. The study concluded that the implementation of CBC is greatly challenged by a lack of sensitization on the implementation of the CBC and perceived CBC as expensive, demanding and time-consuming. Thus, recommended that the private schools get more time with their parents to sensitize them on the CBC implementation and get to know their role in the academic performance of their children and also try to change their perception of CBC as expensive, demanding and time-consuming.  Article visualizations:
Keywords: competency-based curriculum; curriculum implementation; parent’s engagement

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Project Appraisal document on a Global Partnership for Education Fund grant in the amount of US$88.4 million to the Republic of Kenya for a primary education development project - World Bank (2015)

Teaching literacy to youth in Dadaab - Rich, Sam (eLimu, 2020)
According to what statistics you use, Dadaab refugee camp is the fifth or sixth biggest city in Kenya. In the middle of 2017, its population was 250,000 and Norwegian Refugee Council (an international humanitarian organisation that focuses on displaced people) was running…

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Eneza Education website - Eneza Education (Eneza Education, 2020)
Eneza Education is an ed-tech company that provides curriculum aligned revision material in all subjects for primary and secondary learners on any device. Our virtual tutor provides access to curriculum-aligned ... Read More

Four cautionary lessons about education technology - Evans, David (World Bank Blogs, 2017)
Technology in education is often seen as a solution. It holds promise, but caution is warranted.Photo: Charlotte Kesl / World Bank There is no denying that governments around the world are expanding investments in education technology, from inputs that students use directly (like Kenya’s project to put tablets in schools) to ...

A Study on the Implementation of the Strengthening Innovation and Practice in Secondary Education Initiative for the preparation of Science, Technology, English and Mathematics (STEM) Teachers in Kenya to integrate Information and Communication Technology (ICT) in Teaching and Learning - Hooker, Mary (2017)

This BRCK Will Revolutionize Education In Africa - Shapshak, Toby (Forbes, 2015)
In a scene not unlike classrooms around the world, the faces of 40 children glow from the light of their tablets as their teacher leads them through the morning's lesson. Except this happened yesterday inside a converted shipping container in a low-income area of Kenya, in a country where the price [...]

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Assessing the Impact of Early Learning Programs in Africa - Gove, Amber; Brunette, Tracy; Bulat, Jennae; Carrol, Bidemi; Henny, Catherine; Macon, Wykia; Nderu, Evangeline; Sitabkhan, Yasmin (New Directions for Child and Adolescent Development, 2017)
We present results from early learning programs in six African countries: Ethiopia, Kenya, Liberia, Malawi, Tanzania, and Uganda. In partnership with ministries of education, RTI International has worked within government systems to support the design and deployment of locally contextualized materials, training, and assessment tools, with the goal of improving outcomes for early learners in primary schools, and in Kenya and Tanzania preprimary as well. Here we report on the experience and evidence of impact from specific programs in each country, including summary assessment results when available. In several countries with completed impact evaluations, there are significant and important learning gains of between 0.2 and 2.57 SD in effect size; in one case the percentage of students reaching grade‐level reading proficiency increased from 12% to 47%. In the context of increased urgency surrounding what UNESCO has called a “global learning crisis,” these experiences provide useful lessons for policymakers and practitioners alike.

A Kenyan Cloud School. Massive Open Online & Ongoing Courses for Blended and Lifelong Learning - Jobe, William (Open Praxis, 2013)
This research describes the predicted outcomes of a Kenyan Cloud School (KCS), which is a MOOC that contains all courses taught at the secondary school level in Kenya. This MOOC will consist of online, ongoing subjects in both English and Kiswahili. The KCS subjects offer self-testing and peer assessment to maximize scalability, and digital badges to show progress and completion to recognize and validate non-formal learning. The KCS uses the Moodle LMS with responsive web design to increase ubiquitous access from any device. Access is free and open, and the KCS intends to be a contextualized open educational resource for formal secondary institutions to support blended learning and a free source of non-formal education for lifelong learning. The expected outcomes are that this effort will reduce secondary school dropout rates, improve test scores, become a quality resource for blended learning, as well as validate and recognize lifelong learning in Kenya.

Ed-Tech landscape and challenges in Sub-Saharan Africa - Adeniran, Adedeji; Adedeji, Abdulfatai; Nwosu, Emmanuel; Nwugo, Emmanuel; Nnamani, Great (Southern Voice, 2023)
This study examines the adoption of education technology (ed-tech) in primary and secondary education in 10 sub-Saharan African countries: Nigeria, South Africa, Sierra Leone, Uganda, Kenya, Tanzania, Cameroon, Benin, Malawi, and Senegal. The study assesses the development and implementation of ed-tech policies and programmes in the region, exploring how far ed-tech has advanced learning outcomes, improved access, and reduced education inequalities within and between countries in sub-Saharan Africa.

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.

Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Principals' Instructional Leadership Styles and their effect on Tutors on ICT integration in teaching Science - Omwenga, Ezekiel (2016)
The study was carried out to determine the influence of the Principals' leadership style and its effect on the tutors' ICT integration in teaching in Nyanza Region Kenya. One research question and research hypothesis guided the study. The population comprised of 30 Principals and 160 Tutors. A questionnaire and an interview schedule were used to collect data from the Principals and Tutors. Cronbach alpha reliability computation was done to determine the overall reliability of the instrument. Cronbach alpha coefficient of 0.9 and higher was considered reliable. Pearson correlation coefficient, mean and standard deviation were used to analyze data collected and the hypothesis was tested at 0.01 alpha levels. The results from the data analysis indicated there was a direct linear relationship between principal's instructional leadership styles and the teachers' integration of ICT in teaching of science. Based on the findings of the study, it was recommended that the Government of Kenya should develop policies to guide the instructional leaders, KICD, TSC, MOEST and KESI to develop guidelines for Tutors in ICT integration during the teaching of Science.

Connecting africa using the TV white spaces: from research to real world deployments - Roberts, Sidney; Garnett, Paul; Chandra, Ranveer (2015 IEEE International Workshop on Local and Metropolitan Area Networks (LANMAN), 2015)
More than 4 billion people are not connected to the Internet. This is either because there is no infrastructure or because Internet access is not affordable. This digital divide is extreme in Africa. At Microsoft, we have been investigating various technologies to bridge this divide. In this paper we describe our research around the TV White Spaces, and how we have leveraged it, and worked with our partners to connect communities in Kenya, Tanzania, Ghana, Botswana, Namibia and South Africa.

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guidance Note 3 Digital technologies and girls’ education From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Critical perspectives on the use of technology with refugees and displaced communities: The case of Dadaab - Leomoi, Ochan (Journal of Interactive Media in Education, 2025)
Dadaab Refugee Complex hosts refugees from the Horn of Africa and the Great Lakes region. According to a UNHCR (2023) report, at 31 January 2023 Dadaab refugee camps were host to a total population of 233,828 registered refugees and asylum seekers, representing 41% of the total recognized forcibly displaced people in Kenya. This paper will explore Dadaab as the context for connected learning in addition to the author’s first-hand accounts. The author provides a reflexive account of the perspectives of refugees in Dadaab refugee camps and Dadaab host-communities on the role of higher education for individual and social transformation, and how technology could be embraced to leverage learning despite challenges to the access and use of the internet, and computers. In this paper, the author makes a reflexive account of the role of education in transforming refugee learners and communities, and how technology was employed, albeit with challenges, to connect Dadaab with other higher education institutions within and beyond Kenya’s boundaries. The author is further concerned with how technology in higher education in crisis contexts is conceived as the agent that builds networks of scholars, generates connections for development, and promotes exchange of knowledge and ideas among students and faculty across all geographical borders.

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning Equity Requires More than Equality: Learning Goals and Achievement Gaps between the Rich and the Poor in Five Developing Countries - Working Paper 504 - Akmal, Maryam; Pritchett, Lant (RISE Programme Working Paper, 2019)
Achieving some absolute standard of learning for all children is a key element of global equity in education. Using the Annual Status of Education Report (ASER) data from India and Pakistan, and Uwezo data from Kenya, Tanzania, and Uganda that test all children of given ages, whether in school or not, on simple measures of learning in math, reading (local language), and English, we quantify the role of achieving equality between the richest 20% and the poorest 40% in terms of grade attainment and learning achievement toward accomplishing the global equity goal of universal numeracy and literacy for all children.

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Research on the response to COVID19 - Haßler, Björn; Fitzpatrick, Rachael (BE2, 2020)
Presentation given at BE2, 2020-10-06.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _yl:u; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Building Stronger Education Systems: Stories of Change (Global Partnership for Education, 2019)
The Global Partnership for Education (GPE) supports close to 70 developing countries to ensure that every child receives a quality education. The featured stories in this report show the progress that developing country partners are making in getting more children, especially girls, in school and learning. The results are not only evidence of their commitment to improve education, but also of the sustained and targeted support provided by GPE. Feature stories are included from the following countries: (1) Afghanistan; (2) Benin; (3) Burkina Faso; (4) Djibouti; (5) Eritrea; (6) Ethiopia; (7) Guyana; (8) Kenya; (9) Pakistan; (10) Papua New Guinea; and (11) Sudan.
Keywords: Access to Education; Barriers; Developing Nations; Disadvantaged; Early Childhood Education; Economic Development; Educational Change; Educational Improvement; Educational Needs; Educational Practices; Educational Quality; Equal Education; Foreign Countries; Reading Instruction; Reading Skills; Refugees; Rural Education; Technology Uses in Education; Womens Education

Learning Curve: Progress in the Replication Crisis - Angrist, Noam; Cullen, Claire; Ainomugisha, Micheal; Bathena, Sai Pramod; Bergman, Peter; Crossley, Colin; Letsomo, Thato; Matsheng, Moitshepi; Panti, Rene Marlon; Sabarwal, Shwetlena; Sullivan, Tim (AEA Papers and Proceedings, 2023)
We present detailed monitoring data across a five-country randomized trial of phone-based targeted tutoring–one of the largest multicountry replication efforts in education to date. We study an approach shown to work in Botswana and replicated in India, Kenya, Nepal, the Philippines, and Uganda. While the existing literature often finds diminishing effects as proof-of-concept studies are replicated and scaled, we find the opposite: implementation fidelity (the degree of targeted educational instruction) improves across replications and over time. This demonstrates that replication is not intractable; rather, equipped with mechanisms to learn from experience, organizational “learning curves” can enable effective replication and scale-up.

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Improving teaching and learning of basic maths and reading in Africa: Does teacher preparation count? - Akyeampong, Kwame; Lussier, Kattie; Pryor, John; Westbrook, Jo (International Journal of Educational Development, 2013)
Teacher education has an important role in ensuring quality of learning especially for the poorest children. The article draws on a study of teacher preparation for the early primary grades in six African countries – Ghana, Kenya, Mali, Senegal, Tanzania and Uganda – in reading and mathematics. Initial teacher education had the strongest impact on newly qualified teachers but also induced misplaced confidence leading to standardised teacher-led approaches that failed to engage learners. Learning to read was divorced from meaning while mathematical activities were not linked to learning concepts. We suggest that teacher education is reconstructed as a study of classroom practice that places children's learning at its centre.

Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan (International Journal of Educational Development, 2021)
We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year’s worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.
Keywords: COVID-19; Education; Foundational skills; Learning loss; Recovery

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Technical and vocational education and training (TVET) for young people in low- and middle-income countries: a systematic review and meta-analysis - Tripney, Janice S; Hombrados, Jorge G (Empirical Research in Vocational Education and Training, 2013)
The world is facing a worsening youth employment crisis. In response, technical and vocational education and training (TVET) is back on the development agenda after years of neglect. This systematic review examined the evidence from studies evaluating the impacts of TVET interventions for young people in low- and middleincome countries (LMICs). The 26 included studies evaluated 20 different interventions, predominantly from Latin America. Meta-analyses of the effectiveness of TVET on five outcome measure categories were conducted. The overall mean effects on overall paid employment, formal employment, and monthly earnings were small, positive, and significant; however, significant heterogeneity was observed. Moderator analysis was performed in an attempt to explain between-study differences in effects. The overall paucity of research in this area, together with specific gaps and methodological limitations, affirm the need for strengthening the evidence base. Implications for policy, practice and research are discussed.
Keywords: -AB-Review; -AB-Review-SSA; -RQAsummary; -codedOrSummarised; -review; C:Kenya; CLL:en; FF1.1/3; FF2.2; FF2.7.a; interesting; keyReview en; onLongList; retain_obsolete; revofrevSummarisedSeptember2018; summarised

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Context and Appropriate Technology: The Unavoidable Partnership - Onguko, Brown (2012)
Teachers in rural parts of Kenya lack opportunities for professional development (PD). In addition, the teachers have no access to eLearning opportunities like their colleagues in urban parts. Among the factors that do not favor Kenyan rural teachers’ access to PD through eLearning include: lack of access to relevant technologies and lack of electricity. This paper shares research findings on provision of teachers’ PD through a blended learning approach, utilizing appropriate technologies in a rural school in western Kenya. Ten teachers and two Professional Development Teachers (PDTs) participated in this research. In the study, teachers’ needs assessment was done, to inform the instructional design on the topic: How to teach a large class of mixed ability students. The PD was implemented by engaging teachers in a variety of activities including: pairs of teachers collaboratively using a tablet to access self-study content; teachers studying through multimedia content; teachers planning and delivering lessons using activity-based learning and cooperative learning approaches; and PDTs and teachers participating in fortnightly face-to-face meetings. The findings of the study suggest that teaching practices of rural educators can be improved working with local experts to create locally-relevant content for needs-based PD, implemented in a blended learning approach while providing technology stewardship. Teachers accessed and studied through offline content; planned for and implemented cooperative learning and activity-based learning in lessons, using locally available materials; engaged in reflective conversations on successes and challenges; and spontaneously engaged in very lively professional dialogues. While teachers appreciated that it took long to prepare for active learning lessons, it was less strenuous to implement the lessons, because the students took responsibility for their own learning.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096499; __finaldtb; ⛔ No DOI found

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Pathways to Educational Success Among Refugees: Connecting Locally and Globally Situated Resources - Dryden-Peterson, Sarah; Dahya, Negin; Adelman, Elizabeth (American Educational Research Journal, 2017)
This study identifies pathways to educational success among refugees. Data are from an original online survey of Somali diaspora and in-depth qualitative interviews with Somali refugee students educated in the Dadaab refugee camps of Kenya. This research builds on Bronfenbrenner’s ecological model to consider both the locally and globally situated nature of resources across refugees’ ecosystems. Analysis examines the nature and content of student-identified supports and their perceived influence on access to and persistence in school as well as the mediating role of technology. The findings suggest consideration of both locally situated relationships and globally situated relationships as critical educational supports. Implications include leveraging naturally occurring virtual relationships to support educational success of refugees and other young people who are physically isolated from access to needed supports in their local region.
Keywords: Google Scholar/ refugee education technology; RER theme_pedagogies and modalities

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Studying engagement and performance with learning technology in an African classroom - Mutahi, Juliet; Kinai, Andrew; Bore, Nelson; Diriye, Abdigani; Weldemariam, Komminist (Association for Computing Machinery, 2017)
In this paper, we study the engagement and performance of students in a classroom using a system the Cognitive Learning Companion (CLC). CLC is designed to keep track of the relationship between the student, content interaction and learning progression. It also provides evidence-based engagement-oriented actionable insights to teachers by assessing information from a sensor-rich instrumented learning environment in order to infer a learner's cognitive and affective states. Data captured from the instrumented environment is aggregated and analyzed to create interlinked insights helping teachers identify how students engage with learning content and view their performance records on selected assignments. We conducted a 1 month pilot with 27 learners in a primary school in Nairobi, Kenya during their maths and science instructional periods. We present our primary analysis of content-level interactions and engagement at the individual student and classroom level.
Keywords: developing countries; education; engagement; learning analytics; mobile development

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guidance on Community Mobilisation for Girls’ Education - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Can A/B Testing at Scale Accelerate Learning Outcomes in Low- and Middle-Income Environments? - Friedberg, Aidan (Springer Nature Switzerland, 2023)
On current trends the world will fail to reach the objectives set in the UN’s Sustainable Development Goals for Education by 2030 or even within the 21st century. Changing this trend will require a significant acceleration in learning outcomes. Digital personalised learning (DPL) tools are a potentially cost-effective intervention that can contribute to this acceleration. In particular, the continuous experimentation afforded by these tools through software A/B testing, has considerable potential to create compounding improvements in learning outcomes. This paper provides an overview of EIDU, an educational platform combining student focused DPL content with digital structured pedagogy programmes in public pre-primary schools in Kenya. Collection of student’s longitudinal unsupervised assessment data at scale creates the possibility of learning outcome focused A/B testing. This is a novel contribution to the development and research field as up until now this type of capability has largely been confined to students in high-income environments.

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Perceptions of autism spectrum disorder among the Swahili community on the Kenyan coast - Greer, J. M. H.; Sood, S. S. M.; Metcalfe, D. R. (Research in Developmental Disabilities, 2022)
Background In high-income and Western societies there is great understanding and awareness of autism spectrum disorder (ASD); however, for many low-middle income countries, research and knowledge is notably lacking. In Africa, there is a growing prevalence of ASD due to increased diagnosis, yet it is still a poorly understood condition. Aims Emerging literature has emphasised how cultural and societal beliefs underpin the level of understanding of ASD, and which typically results in lack of awareness and acceptance. As such it is important to investigate the cultural perceptions towards ASD within low-middle income communities of African culture, to further understand the challenges and barriers individuals with ASD face. The aim of the current study was to probe participants from the Swahili community, on the coast of Kenya, of their cultural views towards ASD. Method Semi-structured interviews were conducted with seven participants, and the data analysed using thematic analysis. Results Three key themes developed from the data; stigma, lack of awareness, and Government responsibility. Conclusion Cultural perceptions negatively impacted awareness and are exacerbated by lack of directive from the Government in providing appropriate diagnostic and educational support.
Keywords: ASD; Government responsibility; Lack of awareness; Stigma; Swahili community

Perceptions of autism spectrum disorder among the Swahili community on the Kenyan coast - Greer, Jo; Sood, S. S. M.; Metcalfe, Dale (Research in Developmental Disabilities, 2022)
Background: In high-income and Western societies there is great understanding and awareness of autism spectrum disorder (ASD); however, for many low-middle income countries, research and knowledge is notably lacking. In Africa, there is a growing prevalence of ASD due to increased diagnosis, yet it is still a poorly understood condition. Aims: Emerging literature has emphasised how cultural and societal beliefs underpin the level of understanding of ASD, and which typically results in lack of awareness and acceptance. As such it is important to investigate the cultural perceptions towards ASD within low-middle income communities of African culture, to further understand the challenges and barriers individuals with ASD face. The aim of the current study was to probe participants from the Swahili community, on the coast of Kenya, of their cultural views towards ASD.Method: Semi-structured interviews were conducted with seven participants, and the data analysed using thematic analysis. Results: Three key themes developed from the data; stigma, lack of awareness, and Government responsibility. Conclusion: Cultural perceptions negatively impacted awareness and are exacerbated by lack of directive from the Government in providing appropriate diagnostic and educational support.
Keywords: ASD; Government responsibility; Lack of awareness; Stigma; Swahili community; ⛔ No INSPIRE recid found

Integrating ICT into schools in Sub-Saharan Africa: from teachers’ capacity building to classroom implementation - Agyei, D. D (Education and Information Technologies, 2021)
This study followed up on a selected cohort of 4945 Science, Technology, English and Mathematics (STEM) teacher participants from six Sub-Saharan African countries namely: Kenya, Tanzania, Uganda, Ethiopia, Ghana and Nigeria. The teachers were involved in an instructional digital professional development programme targeted at building their capacity to embed ICT into school organizational and curriculum practices. This study sought to evaluate the impact of the ICT- instructional professional development programme in relation to the quality and the extent of the teachers’ transfer of the programme’s ideas from capacity building to classroom instructional practices. Data for the study were collected using semi-structured survey instrument and diaries kept to maintain records of activities and events during the period of implementation. Findings revealed that the teachers expressed general satisfaction with content and processes of the training programme; however, essential conditions to support transfer of the training’s ideas to school level seemed not adequate during the period of implementation. Implications for effective professional development in integrating ICT into school organization and curriculum practices that have sustainable impact on teaching and learning particularly in Sub-Saharan regions and similar contexts are discussed.

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Guidance Note 7 Ensuring resilient connectivity From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Using educational technology to develop early literacy skills in Sub-Saharan Africa - Abrami, Philip C.; Wade, C. Anne; Lysenko, Larysa; Marsh, Jonathon; Gioko, Anthony (Education and Information Technologies, 2016)
The research explores the impact of interactive, multimedia literacy software (ABRA) on the reading skills of early elementary students in Kenya. Twelve grade two English teachers and their students from six schools were randomly divided in half: an experimental group (N = 180) where ABRA was part of their English Language instruction and a control group (N = 174) where regular instruction was used. After the pre-test student data were collected, a three-day initial training and planning session were held for the experimental teachers on how to use ABRA to teach literacy. Every week each experimental class was bussed to a computer lab with full access to ABRA for one 90-min lesson. Teacher support included the alignment of ABRA lesson plans with the Kenyan English Language norms, weekly web conferences with the trainer, as well as technical and pedagogical help from staff at the lab site. After the 13-week intervention, significant and substantial gains in reading comprehension were found for ABRA students as measured by GRADE, a standardized test of literacy. In addition, ABRA students outperformed their peers in control classes on the core end-of-year subject exams including English, Mathematics, Science and Social Studies.
Keywords: Developing countries; Early literacy; Educational technology; Primary education

Support to children’s education in the urban slums of Nairobi: community and parents’ perceptions with an expanded phase of an education intervention program - Abuya, Benta A.; Wekulo, Patricia; Muhia, Nelson (Qualitative Research in Education, 2018)
The objective of this paper is to examine the perceptions of community elders and parents on their roles regarding support to their children’s education. Data come from the qualitative component of a baseline survey conducted in Korogocho and Viwandani, two urban informal settlements in Nairobi, Kenya. Data were collected in April-May 2016 through in-depth interviews, key informant interviews and focus group discussions. Results demonstrated that community elders internalized their role as the face of government in their respective communities, and enforced the implementation of education policies on behalf of all children. The community leaders also saw as part of their role the need to encourage parents to be active participants in their children’s education. Female parents with boys in the program perceived that parental monitoring and follow-up was important to ensure that their children attended school, and completed work assigned by the teachers, more so in Korogocho. Overall, parents recognized the importance of the role they played in their children’s education. This is a good entry point as parental support will ensure the success and sustainability of the intervention to improve educational outcomes for children, which in turn will help their children navigate the challenging period that adolescence presents.
Keywords: teachers

Policy interventions for attraction and retention of female teachers in rural secondary schools - Kamere, Isabela M.; Makatiani, M. I.; Nzau, Arthur Kalanza (Msingi Journal, 2019)
The potential role of female teachers in achieving the Education for all (EFA) and the Sustainable Development Goals, specifically on  ensuring  inclusive and equitable quality education and promoting life-long learning opportunities for all (Goal 4), achieving gender equality and empowering  all women and girls(Goal 5 ) is well documented. Available evidence, however, suggests that attraction and retention of female teachers in secondary schools located in rural areas remains a significant and on-going challenge. In response, policy makers in Kenya have recommended three key policy interventions namely decentralization of teacher recruitment, payment of hardship allowance and provision of housing. A literature search reveals a dearth of information on the perspectives of rural educators on the effectiveness of these interventions. The paper presents findings based on one objective of a broader study which was to: Establish the views of female teachers’ and other stakeholders’ regarding the effectiveness of strategies for attraction and retention of female teachers in Makueni County. This study adopted a mixed methods design. The paper presents findings from the qualitative component of the study. Interviews were used to gather data. Based on their interpretations, the authors provide useful   insights and offer suggestions on how the implementation of these policies could be improved.
Keywords: Attraction; female teachers; retention

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
Keywords: ⛔ No INSPIRE recid found

GraphoGame – a catalyst for multi-level promotion of literacy in diverse contexts - Ojanen, Emma; Ronimus, Miia; Ahonen, Timo; Chansa-Kabali, Tamara; February, Pamela; Jere-Folotiya, Jacqueline; Kauppinen, Karri-Pekka; Ketonen, Ritva; Ngorosho, Damaris; Pitkänen, Mikko; Puhakka, Suzanne; Sampa, Francis; et al. (Frontiers in Psychology, 2015)
GraphoGame (GG) is originally a technology-based intervention method for supporting children with reading difficulties. It is now known that children who face problems in reading acquisition have difficulties in learning to differentiate and manipulate speech sounds and consequently, in connecting these sounds to corresponding letters. GG was developed to provide intensive training in matching speech sounds and larger units of speech to their written counterparts. GG has been shown to benefit children with reading difficulties and the game is now available for all Finnish school children for literacy support. Presently millions of children in Africa fail to learn to read despite years of primary school education. As many African languages have transparent writing systems similar in structure to Finnish, it was hypothesized that GG-based training of letter-sound correspondences could also be effective in supporting children’s learning in African countries. In this article we will describe how GG has been developed from a Finnish dyslexia prevention game to an intervention method that can be used not only to improve children’s reading performance but also to raise teachers’ and parents’ awareness of the development of reading skill and effective reading instruction methods. We will also provide an overview of the GG activities in Zambia, Kenya, Tanzania, and Namibia, and the potential to promote education for all with a combination of scientific research and mobile learning.

An Investigation into Implementation of ICT in ECD and Primary Schools, in the Light of Free Laptops at Primary One: a case study of teachers implementing ICT into their teaching practice - Tonui, Betty C.; Kerich, E.; Koross, R.; J, K.; Moi, Too (2018)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Combining school-catchment area models with geostatistical models for analysing school survey data from low-resource settings: Inferential benefits and limitations - Macharia, Peter M.; Ray, Nicolas; Gitonga, Caroline W.; Snow, Robert W.; Giorgi, Emanuele (Spatial Statistics, 2022)
School-based sampling has been used to inform targeted responses for malaria and neglected tropical diseases. Standard geostatistical methods for mapping disease prevalence use the school location to model spatial correlation, which is questionable since exposure to the disease is more likely to occur in the residential location. In this paper, we propose to overcome the limitations of standard geostatistical methods by introducing a modelling framework that accounts for the uncertainty in the location of the residence of the students. By using cost distance and cost allocation models to define spatial accessibility and in absence of any information on the travel mode of students to school, we consider three school catchment area models that assume walking only, walking and bicycling and, walking and motorized transport. We illustrate the use of this approach using two case studies of malaria in Kenya and compare it with the standard approach that uses the school locations to build geostatistical models. We argue that the proposed modelling framework presents several inferential benefits, such as the ability to combine data from multiple surveys some of which may also record the residence location, and to deal with ecological bias when estimating the effects of malaria risk factors. However, our results show that invalid assumptions on the modes of travel to school can worsen the predictive performance of geostatistical models. Future research in this area should focus on collecting information on the modes of transportation to school which can then be used to better parametrize the catchment area models.
Keywords: Catchment area models; Disease mapping; Missing locations; Model-based geostatistics; Prevalence; School survey

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

SUMMARY Learning through the crisis: Helping decision-makers around the world use digital technology to combat the educational challenges produced by the current COVID-19 pandemic - Traxler, John; Scott, Howard; Smith, Matt; Hayes, Sarah (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Providing access to education in Sub-Saharan countries through Content-Oriented technology - Kiboro, Angelica; Bailey, Sheena; Nair, Mrinay; Salam, Tomisin; Dwhytie, Alex (2014 IEEE Canada International Humanitarian Technology Conference - (IHTC), 2014)
Access to education has been a growing concern for children in developing economies, namely lack of access to quality customized online content in the classroom and at home; lack of tools that make learning fun and effective in key subject areas; and lack of state resources to meet educational demands. The Rumie Initiative was founded to tackle these concerns. It is a non-profit organization bringing educational content to the world's underprivileged children through low-cost technology. The Rumie Initiative's vision is to redefine the way education is provided, and through this, significantly reduce poverty and drive economic development. The primary advantage of The Rumie Initiative over all other educational technology solutions is that its content is specifically tailored to meet the local educational needs and curriculum standards. Utilizing the vast reserves of free online updated educational content available today; these android driven tablets are an affordable and intuitive way to deliver pre-loaded content without the requirement of internet access. Through mass global volunteerism, The Rumie Initiative collaborates with educators in choosing appropriate educational content and distributes content-loaded tablets through local Non-Governmental Organizations, communities and government entities. The Rumie Initiative has started a program of trials around the world and recently received a positive response at a Computer - Based Math Education Summit in New York hosted by UNICEF from November 21st to 22nd 2013. The initiative was first launched in Haiti on 25th October 2013 and has since, been gaining momentum, currently exploring opportunities in Sub-Saharan countries such as Ghana, Kenya, Uganda, Rwanda, Burundi, South Africa and Nigeria. This paper focuses on The Rumie Initiative's unique business model to reach the masses, emphasizing issues relating to the power of volunteer ism, the forging of strategic development partners, and content-oriented technologies in increasing access to education.
Keywords: Blogs; Communities; Education; Internet; Internet access; Monitoring; Organizations; Rumie initiative; Servers; Terminology; authorisation; computer aided instruction; content management; content-oriented technology; curriculum standards; economics; economies; educational content; educational demands; government entities; non-governmental organizations; online content; standards; sub-Saharan countries

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Advancing Learning Outcomes for Transformational Change III - African Population and Health Research Center (African Population and Health Research Center, 2021)

Evaluating the Learner Experience of the TCPD Learning Management System for Primary School Teachers in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Simmons, Hannah; Komba, Aneth (2025 IST-Africa Conference (IST-Africa), 2025)

Technology for Inclusive Education (TFIE) Pilot Report - Digital Literacy Trust (2018)

Gender responsive pedagogy: A toolkit for teachers and schools. 2nd ed. - FAWE (Forum for African Women Educationalists (FAWE)., 2018)

Accelerated Education Programme Youth Education Programme: NRC Education Scale-up and Quality Fund, EdTech for Rapid Response in Acute Emergencies Project - Kipruto, Amos; Denny, Kathleen (Norwegian Refugee Council, 2019)

How Can Decision-Makers Assess EdTech Interventions for Cost-Effectiveness to Enable Better Investments? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how decision-makers should consider cost-effectiveness when contemplating investing in EdTech programmes. Cost-effectiveness is a critically important consideration for anyone planning investments in EdTech, but it is also a complex one, which requires understanding the total cost of an intervention and comparing it against the likely impact on education. We draw on work from EdTech Hub and other prominent researchers to distil key practical insights for decision-makers on how to apply cost-effectiveness analysis to their decision-making. Practical considerations include recommendations on gathering the right data for analysis; ensuring cost calculations are holistic; leveraging existing frameworks and tools for cost and impact calculations; and ensuring that comparisons are made against non-tech interventions as well as the broader resource envelope available for education to determine affordability in a given context. Finally, we explore areas where additional work is needed, including an increased understanding of the challenges faced by decision-makers in considering cost-effectiveness and the need for greater transparency and accountability in cost-effectiveness analysis in the sector. Keywords Cost-effectiveness; EdTech; education policy; total cost of implementation; affordability; Learning-Adjusted Years of Schooling An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Aid on the Edge of Chaos: Rethinking International Cooperation in a Complex World - Ramalingam, Ben (Oxford University Press, 2013)
It is widely recognised that the foreign aid system - which today involves every country in the world - is in need of drastic change. But there are conflicting opinions as to what is needed. Some call for dramatic increases in resources, to meet long-overdue commitments, and to scale up what is already being done around the world. Others point to the flaws in aid, and bang the drum for cutting it altogether - and argue that the fate of poor and vulnerable people be best placed in the hands of markets and the private sector. Meanwhile, growing numbers are suggesting that what is most needed is the creative, innovative transformation of how aid works. Aid on the Edge of Chaos is firmly in the third of these camps. In this ground-breaking book, Ben Ramalingam shows that the linear, mechanistic models and assumptions on which foreign aid is built would be more at home in early twentieth century factory floors than in the dynamic, complex world we face today. All around us, we can see the costs and limitations of dealing economies and societies as if they are analogous to machines. The reality is that such social systems have far more in common with ecosystems: they are complex, dynamic, diverse and unpredictable. Many thinkers and practitioners in science, economics, business, and public policy have started to embrace more 'ecologically literate' approaches to guide both thinking and action, informed by ideas from the 'new science' of complex adaptive systems. Inspired by these efforts, there is an emerging network of aid practitioners, researchers, and policy makers who are experimenting with complexity-informed responses to development and humanitarian challenges. This book showcases the insights, experiences, and often remarkable results from these efforts. From transforming approaches to child malnutrition, to rethinking processes of economic growth, from building peace to combating desertification, from rural Vietnam to urban Kenya, Aid on the Edge of Chaos shows how embracing the ideas of complex systems thinking can help make foreign aid more relevant, more appropriate, more innovative, and more catalytic. Ramalingam argues that taking on these ideas will be a vital part of the transformation of aid, from a post-WW2 mechanism of resource transfer, to a truly innovative and dynamic form of global cooperation fit for the twenty-first century.

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
This report captures what might be learnt from a selection of the world’s most interesting examples of technology-assisted in-service professional development in lower-income countries and from wider reflections about the potential of technology to enhance the professional learning of teachers.
Keywords: Africa; Bangladesh; Blended Learning; C:Low- and middle-income countries; Developing Nations; ERIC, Resources in Education (RIE); Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; India; Inservice Teacher Education; Kenya; Large Group Instruction; Nigeria; Online Courses; Pakistan; Policymakers; Practitioners; Refugees; Shared Resources and Services; Social Media; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; ⛔ No DOI found

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education in Conflict and Crisis in 2035: Twelve trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in the increase in global conflict and crises that might occur over the next 10 years. It begins by capturing twelve trends, relating to conflict and crisis, that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Evidence Coaching Handbook - Rahman, Asad (EdTech Hub, 2024)
This handbook captures EdTech Hub's approach to providing evidence coaching on the EdTech Hub Evidence-Led Entrepreneurship Course. Individuals and organisations who support EdTech entrepreneurs to scale their products impactfully (e.g., accelerators, entrepreneurship programmes, funders) can all provide evidence coaching to entrepreneurs. This Handbook is for anyone working within an EdTech startup, or an entrepreneur who wants to better apply evidence to key decisions. By sharing EdTech Hub’s approach and process for evidence coaching, we hope to nurture a more evidence-led EdTech entrepreneurship ecosystem, leading to more EdTech products that scale sustainably, and help children to read, write, and count. The Handbook contains EdTech Hub’s five-step process for generating and applying evidence as a startup, with specific tools we used along the way. The process is a guide for others to adapt and tailor to their unique context and challenges. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Approved Basic Education Statistical Booklet 2019 - Ministry of Education (2019)

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

The Use of Interactive Whiteboards to Support Refugee Learning - Ramesh Vasudevan, Sharanya; Handigol, Apoorva (EdTech Hub, 2025)
This EdTech Hub rapid scan outlines the efficacy of interactive whiteboards (IWBs) to better understand the potential impact of investment in the digitisation of teaching and learning materials to enhance access to education and learning for refugee children. The focus is on research that can highlight any evidence on the efficacy of interactive whiteboards in low- and middle-income country (LMIC) contexts characterised by high numbers of school-age refugees, with Turkey as a key case study. The scan highlights important and valid considerations that can be applied to broader learnings around IWBs. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Harnessing EdTech for Neurodivergent Learners in LMICs: A Rapid Evidence Synthesis - Layachi, Aida; Plaut, Daniel (EdTech Hub, 2025)
As neurodivergent learners continue to face multifaceted challenges that affect their education, education systems, environments, and practices have struggled to address their needs adequately. This rapid evidence synthesis explores the current state of evidence regarding the use of educational technologies (EdTech) for neurodivergent learners in low-and middle-income countries (LMICs). The review was conducted in two phases to offer complementary insights on the topic. The first phase presents the findings regarding the use of EdTech for neurodivergent learners in LMICs. The second phase expands the focus, offering evidence and examples that extend beyond LMICs, providing a global perspective on how EdTech could be applied and adapted to LMICs to address different challenges faced by neurodivergent learners. The holistic framework for EdTech for neurodivergence presented in this synthesis provides insights and recommendations regarding the potential of EdTech in optimising systems, environments, and education practices. Keywords: EdTech, Neurodivergence, LMICs, holistic framework, learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Are Our Children Learning? - Uwezo (Twaweza East Africa, 2016)

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Helpdesk Response; _r:AddedByZotZen

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

KEY FIGURES: 5th Rwanda Population and Housing Census (PHC) - National Institute of Statistics of Rwanda. (National Institute of Statistics of Rwanda., 2023)
The fifth Population and Housing Census in Rwanda, was conducted in August 2022. The Census operation was coordinated by the National Census Commission. Various census technical and administrative structures have been put in place to ensure a successful census operation.

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

O Efeito da COVID-19 na Educação em África e Suas Implicações para a Utilização da Tecnologia Um Inquérito sobre a Experiência e as Opiniões de Educadores e Especialistas em Tecnologia - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets